Glass containers having improved strength and improved damage resistance - Patents.com

By using compressive stress layer and low friction coating technology in glass pharmaceutical packaging containers, the problem of vulnerability to damage and delamination during production and filling is solved, achieving higher mechanical strength and durability.

JP7659364B2Active Publication Date: 2025-04-09CORNING INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023135451
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2013-11-08
Filing Date
2023-08-23
Publication Date
2025-04-09
Estimated Expiration
2033-11-22

AI Technical Summary

Technical Problem

Existing glass agent packaging containers are prone to scratches, damage and delamination problems during production and filling, resulting in reduced glass strength, unclean medicines or damaged packaging.

Method used

A glass container with a compressive stress layer extending from the outer surface of the container to the thick wall portion and having a surface compressive stress of 150 MPa or above. At the same time, the outer surface of the container is coated with a low friction smooth coating, with a friction coefficient not exceeding 0.7.

Benefits of technology

It improves the anti-scratch, damage and delamination properties of the glass container, enhances the mechanical strength and durability of the container, and reduces the risks of unclean medicines and damaged packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659364000004
    Figure 0007659364000004
  • Figure 0007659364000005
    Figure 0007659364000005
  • Figure 0007659364000006
    Figure 0007659364000006
Patent Text Reader

Abstract

To provide glass containers that have at least two performance attributes selected from resistance to delamination, improved strength, and increased damage resistance.SOLUTION: In one embodiment, a glass container may include a body having an inner surface, an outer surface and a wall thickness extending between the outer surface and the inner surface. A compressively stressed layer may extend from the outer surface of the body into the wall thickness. The compressively stressed layer may have a surface compressive stress greater than or equal to 150 MPa. A lubricous coating may be positioned around at least a portion of the outer surface of the body. The outer surface of the body with the lubricous coating may have a coefficient of friction less than or equal to 0.7.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application is a divisional application of Japanese Patent Application No. 2022-22733, filed under 35 U.S.C. § 119, claiming priority to U.S. Provisional Patent Application No. 61 / 731,767, filed November 30, 2012, entitled "Glass Containers With Improved Attributes," U.S. Patent Application No. 13 / 912,457, filed June 7, 2013, entitled "Delamination Resistant Glass Containers," U.S. Patent Application No. 13 / 780,754, filed February 28, 2013, entitled "Glass Articles With Low-Friction Coatings," and U.S. Patent Application No. 14 / 075,630, filed November 8, 2013, entitled "Glass Containers With Improved Strength and Improved Damage Tolerance." [Technical field]

[0002] TECHNICAL FIELD This disclosure relates generally to glass containers, and more specifically to glass containers used to store pharmaceutical formulations. [Background technology]

[0003] Historically, glass has been used as a preferred material for packaging pharmaceuticals due to its hermeticity, optical clarity, and superior chemical durability compared to other materials. In particular, glasses used for pharmaceutical packaging must have sufficient chemical durability so as not to affect the stability of the pharmaceutical formulations placed therein. Glasses having suitable chemical durability include glass compositions in the ASTM standard "Type IA" and "Type IB" glass compositions, which have a proven track record for chemical durability.

[0004] While Type IA and Type IB glass compositions are commonly used in pharmaceutical packaging, they suffer from a number of deficiencies, including a tendency for glass particulates to shed or "delaminate" on the interior surface of the pharmaceutical package after exposure to pharmaceutical solutions.

[0005] In particular, high process speeds in the production and filling of glass pharmaceutical packages can result in the packages coming into contact with processing equipment, handling equipment, and / or other packages, resulting in scratching or other mechanical damage to the surface of the package that can significantly reduce the strength of the glass pharmaceutical package and increase the likelihood of cracks propagating in the glass, compromising the sterility of the pharmaceutical product contained therein, or even destroying the package altogether. Summary of the Invention [Problem to be solved by the invention]

[0006] Thus, a need exists for alternative glass containers for use as pharmaceutical packaging that exhibit a combination of at least two of improved resistance to delamination, high strength and / or damage durability. [Means for solving the problem]

[0007] According to one embodiment, a glass container may include a body having an inner surface, an outer surface, and a wall thickness extending between the outer surface and the inner surface. A compressive stress layer may extend from the outer surface of the body into the wall thickness. The compressive stress layer may have a surface compressive stress of 150 MPa or more. A lubricious coating may be located about at least a portion of the outer surface of the body. The outer surface of the body including the lubricious coating may have a coefficient of friction of 0.7 or less.

[0008] In another embodiment, a glass container may include a body having an inner surface, an outer surface, and a thickened portion extending between the outer and inner surfaces. The body may be formed from Type 1, Class B glass conforming to ASTM standard E438-92. A compressive stress layer may extend from the outer surface of the body into the thickened portion. The compressive stress layer may have a surface compressive stress of 150 MPa or greater. A smooth coating may be located about at least a portion of the outer surface of the body. The outer surface of the body with the smooth coating may have a coefficient of friction of 0.7 or less.

[0009] Additional features and advantages of the glass container embodiments described herein are described in the detailed description below, and in part will be readily apparent to those skilled in the art from this description, or will be recognized by those skilled in the art by practice of the embodiments described herein, including the detailed description below, the claims, and the accompanying drawings.

[0010] It should be understood that both the foregoing summary and the following detailed description describe various embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated in and constitute a part of this specification. The drawings illustrate various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. [Brief description of the drawings]

[0011] [Figure 1] 1A-1C are schematic diagrams illustrating a cross-section of a glass container according to one or more embodiments described herein. [Diagram 2] 2 illustrates a schematic diagram of a compressive stress layer in a portion of a sidewall of the glass container of FIG. 1. [Diagram 3] 1 illustrates a schematic representation of a portion of a sidewall of a glass container formed from laminated glass. [Figure 4] 1 illustrates a schematic diagram of a horizontal compression apparatus for testing the horizontal compressive strength of glass containers. [Diagram 5] 1A-1C are schematic diagrams illustrating a glass container having a barrier coating disposed on at least a portion of the interior surface of the glass container according to one or more of the embodiments shown and described herein. [Figure 6] 1 illustrates a schematic representation of a portion of a sidewall of a glass container having a continuous layer homogeneity. [Figure 7] 1 illustrates a schematic representation of a portion of a sidewall of a glass container having continuous surface homogeneity. [Figure 8] 1 illustrates a schematic diagram of a glass container having a smooth coating disposed on an exterior surface of the glass container. [Figure 9] 1 shows a schematic diagram of a test fixture for measuring the coefficient of friction between two glass containers. [Figure 10] 1 illustrates a schematic of an apparatus for evaluating the thermal stability of a coating applied to a glass container. [Figure 11] FIG. 1 illustrates light transmission data measured in the visible light spectrum from 400 to 700 nm for coated and uncoated vials according to one or more of the embodiments shown and described herein. [Figure 12A] 1 illustrates a schematic diagram of a robust organic smooth coating disposed on an exterior surface of a glass container according to one or more of the embodiments shown and described herein. [Figure 12B] 1 illustrates a schematic diagram of a robust organic smooth coating disposed on an exterior surface of a glass container according to one or more of the embodiments shown and described herein. [Figure 13] 1 illustrates generally the chemical structures of diamine monomers that may be used to form a polyimide coating layer. [Figure 14] 1A-1C are schematic diagrams illustrating chemical structures of other diamine monomers that may be used to form a polyimide coating layer. [Figure 15]1 illustrates generally the chemical structures of several monomers that may be used as a polyimide coating applied to glass containers. [Figure 16] Illustrates the effect of composition and temperature on volatilization for Type IB and non-boron containing glasses. [Figure 17] 1 illustrates a schematic diagram of a reaction step for silane bonding to a substrate according to one or more of the embodiments shown and described herein. [Figure 18] 1 illustrates a schematic diagram of a reaction step for polyimide bonding to silane according to one or more of the embodiments shown and described herein. [Figure 19] 1 illustrates the probability of failure as a function of applied load in a horizontal compression test on a vial according to one or more of the embodiments shown and described herein. [Figure 20] Contains a table reporting the load and measured coefficient of friction for Type IB glass vials and vials formed from a reference glass composition that has been ion-exchanged and coated according to one or more of the embodiments shown and described herein. [Figure 21] FIG. 13 illustrates the probability of failure as a function of applied stress in four-point bending for tubes formed from a reference glass composition in the as-received, ion-exchanged (uncoated), ion-exchanged (coated and abraded), ion-exchanged (uncoated and abraded) conditions, and tubes formed from Type IB glass in the as-received and ion-exchanged conditions, according to one or more of the embodiments shown and described herein. [Figure 22] 13A-13C are schematic diagrams illustrating gas chromatography-mass spectrometry output data for an APS / Novastrat® 800 coating according to one or more of the embodiments shown and described herein; [Figure 23] 1 illustrates gas chromatography-mass spectrometry output data for a DC806A coating according to one or more embodiments shown and described herein. [Figure 24] 1 is a table reporting different lubricious coating compositions tested under freeze-drying conditions according to one or more of the embodiments shown and described herein. [Diagram 25] 1 is a chart reporting the coefficient of friction for glass vials without a coating and vials with a silicone resin coating tested in a vial stacking fixture according to one or more embodiments shown and described herein. [Figure 26] 1 is a chart reporting the coefficient of friction for vials coated with an APS / PMDA-ODA (poly(4,4′-oxydiphenylene-pyromellitimide) polyimide coating and scraped multiple times at different applied loads in a vial stacking fixture according to one or more of the embodiments shown and described herein. [Figure 27] 1 is a chart reporting the coefficient of friction for vials coated with an APS coating and scraped multiple times at different applied loads in a vial stacking fixture according to one or more embodiments shown and described herein. [Figure 28] FIG. 1 is a chart reporting the coefficient of friction for vials coated with an APS / PMDA-ODA (poly(4,4′-oxydiphenylene-pyromellitimide) polyimide coating and rubbed multiple times at different applied loads in a vial stacking fixture after the vials were exposed to 300° C. for 12 hours according to one or more of the embodiments shown and described herein. [Figure 29] 1 is a chart reporting the coefficient of friction for vials coated with an APS coating and rubbed multiple times at different applied loads in a vial overlapping fixture after the vials were exposed to 300° C. for 12 hours in accordance with one or more of the embodiments shown and described herein. [Diagram 30]1 is a chart reporting the coefficient of friction for a Type IB vial coated with a PMDA-ODA (poly(4,4'-oxydiphenylene-pyromellitimide) polyimide coating and rubbed multiple times at different applied loads in a vial stacking fixture according to one or more of the embodiments shown and described herein. [Diagram 31] 1 illustrates the coefficient of friction for APS / Novastrat® 800 coated vials before and after lyophilization according to one or more of the embodiments shown and described herein. [Diagram 32] 1 illustrates the coefficient of friction for APS / Novastrat® 800 coated vials before and after autoclaving according to one or more of the embodiments shown and described herein. [Diagram 33] 1 illustrates the coefficient of friction for coated and uncoated glass containers exposed to different temperature conditions. [Diagram 34] 1 illustrates the probability of failure as a function of applied load in a horizontal compression test on a vial according to one or more of the embodiments shown and described herein. [Diagram 35] 1 is a table showing the change in coefficient of friction with changes in the composition of the coupling agent of the lubricious coating applied to glass containers described herein. [Diagram 36] Illustrates the coefficient of friction, applied force and frictional force for a coated glass container before and after depyrogenation. [Figure 37] 1 illustrates the coefficient of friction, applied force, and frictional force for a coated glass container before and after depyrogenation according to one or more of the embodiments shown and described herein. [Figure 38] 1 illustrates the probability of failure as a function of applied load in a horizontal compression test on a vial according to one or more of the embodiments shown and described herein. [Figure 39]1 illustrates the coefficient of friction, applied force, and frictional force for a coated glass container before and after depyrogenation according to one or more of the embodiments shown and described herein. [Diagram 40] 1 illustrates the coefficient of friction, applied force, and frictional force for coated glass containers for different depyrogenation conditions. [Diagram 41] 1 illustrates the coefficient of friction after varying the number of heat treatments according to one or more of the embodiments shown and described herein. [Diagram 42] FIG. 1 illustrates light transmission data measured in the visible light spectrum from 400 to 700 nm for coated and uncoated vials according to one or more of the embodiments shown and described herein. [Diagram 43] 1 illustrates the coefficient of friction, applied force, and frictional force for a coated glass container before and after depyrogenation according to one or more of the embodiments shown and described herein. [Diagram 44] 1 illustrates the probability of failure as a function of applied load in a horizontal compression test on a vial according to one or more of the embodiments shown and described herein. [Diagram 45] 1 is a photomicrograph of a coating according to one or more of the embodiments shown and described herein. [Figure 46] 1 is a photomicrograph of a coating according to one or more of the embodiments shown and described herein. [Figure 47] 1 is a photomicrograph of a coating according to one or more of the embodiments shown and described herein. [Figure 48] 1 shows the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the length of the applied scratch (x coordinate) for comparative example bare coated vials. [Figure 49]1 shows the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the applied scratch length (x coordinate) for comparative heat treated vials. [Figure 50] 1 shows the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the length of the applied scratch (x coordinate) for comparative example bare coated vials. [Figure 51] 1 shows the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the applied scratch length (x coordinate) for comparative heat treated vials. [Figure 52] Illustrates the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the length of the applied scratch (x coordinate) for vials with an adhesion promoter layer in the as-coated state. [Figure 53] Illustrates the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the length of the applied scratch (x coordinate) for vials with an adhesion promoter layer in the as-coated state. [Figure 54] Illustrates the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the length of the applied scratch (x coordinate) for vials with an adhesion promoter layer after depyrogenation. [Figure 55] Illustrates the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the length of the applied scratch (x coordinate) for vials with an adhesion promoter layer after depyrogenation. [Figure 56] 1 illustrates the probability of failure as a function of applied load in a horizontal compression test for a vial having an adhesion promoter layer according to one or more of the embodiments shown and described herein. [Figure 57] 1 illustrates the probability of failure as a function of applied load in a horizontal compression test for a vial having an adhesion promoter layer according to one or more of the embodiments shown and described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] We now describe in more detail an embodiment of a glass container, examples of which are illustrated in the accompanying drawings. Whenever possible, the same reference numerals are used throughout the drawings to refer to the same or similar parts. The glass containers described herein have at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance. For example, the glass containers may have a combination of resistance to delamination and improved strength; improved strength and high damage resistance; or resistance to delamination and high damage resistance. In a particular embodiment, the glass containers described herein have at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance. In one embodiment, the glass container may comprise a body having an inner surface, an outer surface, and a thickened portion extending between the outer surface and the inner surface. The compressive stress layer may extend from the outer surface of the body into the thickened portion. The compressive stress layer may have a surface compressive stress of 150 MPa or more. The smooth coating may be located around at least a portion of the outer surface of the body. The outer surface of the body comprising the smooth coating may have a coefficient of friction of 0.7 or less. Glass containers having various combinations of resistance to delamination, improved strength, and high damage resistance are described in more detail herein with specific reference to the accompanying drawings.

[0013] In the glass composition embodiments described herein, concentrations of components (e.g., SiO, AlO, BO, etc.) are specified in mole percent (mol.%) on an oxide basis unless otherwise specified.

[0014] The term "substantially free," when used to describe the concentration and / or absence of a particular component in a glass composition, means that the component is not intentionally added to the glass composition. However, the glass composition may contain trace amounts of the component as contaminants or contaminants in amounts less than 0.1 mol.%.

[0015] As used herein, the term "chemical durability" refers to the ability of a glass composition to resist degradation when exposed to a particular chemical condition. Specifically, the chemical durability of the glass compositions described herein can be evaluated according to three established material testing standards: DIN 12116, entitled "Testing of glass-Resistance to attack by a boiling aqueous solution of hydrochloric acid-Method of test and classification", dated March 2001; ISO 695:1991, entitled "Glass--Resistance to attack by a boiling aqueous solution of mixed alkali--Method of test and classification; ISO 720:1985, entitled "Glass--Hydrolytic resistance of glass grains at 121 degrees C--Method of test and classification; and ISO 719:1985, entitled "Glass--Hydrolytic resistance of glass grains at 98 degrees C--Method of test and classification". Each standard and its classification are described in further detail herein. Alternatively, the chemical durability of a glass composition may be evaluated according to a USP Surface Glass Test entitled "Surface Glass Test" which evaluates the durability of a glass surface. <660> and / or may be evaluated in accordance with the European Pharmacopoeia 3.2.1 entitled "Glass Containers For Pharmaceutical Use."

[0016] "Strain point" and "T 歪み " as used herein means a glass having a viscosity of 3×10 14 This refers to the temperature at which the unit is in poise.

[0017] As used herein, the term "softening point" refers to the point at which the viscosity of a glass composition reaches 1×10 7.6 This refers to the temperature at which the unit is in poise.

[0018] Traditional glass containers used to store pharmaceuticals and / or other consumable products can become damaged during filling, packaging and / or shipping. Such damage can be in the form of surface abrasions, scrapes and / or scratches, and if too deep, can result in through cracks or even complete destruction of the glass container, thereby compromising the contents of the glass package.

[0019] In addition, certain conventional glass containers may be susceptible to delamination, especially when the glass container is made of alkali borosilicate glass. Delamination refers to the release of glass particles from the surface of the glass through a series of leaching, erosion and / or weathering reactions. Typically, the glass particles are silica-rich glass flakes that are derived from the inner surface of the package due to the leaching of modifier ions into the solution contained in the package. These flakes are typically about 1 nm to about 2 micrometers (μm) thick and can be greater than about 50 μm wide. Because these flakes are primarily composed of silica, the flakes generally do not further decompose after being released from the surface of the glass.

[0020] Previously, it was hypothesized that delamination was due to phase separation that occurs in alkali borosilicate glasses when the glass is exposed to the high temperatures used in reforming the glass into container shapes.

[0021] However, it is currently believed that delamination of silica-rich glass flakes from the interior surfaces of glass containers is due to compositional features of the glass containers as they are formed. Specifically, the high silica content of alkali borosilicate glasses results in relatively high melting and forming temperatures for the glass. However, the alkali and borate components in the glass composition melt and / or volatilize at much lower temperatures. In particular, the borate species in the glass are highly volatile and will vaporize from the surface of the glass at the high temperatures required for forming and reforming the glass.

[0022] Specifically, the glass stock is reformed into a glass vessel at high temperatures and in a flame. High temperatures are required at high tool speeds, which increases the evaporation of volatile borate species from some of the glass's surface. If this evaporation occurs within the interior space of the glass vessel, the volatilized borate species may redeposit on other areas of the glass vessel surface, resulting in compositional heterogeneity on the glass vessel surface, especially relative to near-surface areas inside the glass vessel (i.e., areas at or adjacent to the interior surface of the glass vessel). For example, because one end of a glass tube is sealed to form the bottom or floor of the vessel, borate species may vaporize from the bottom portion of the tube and redeposit elsewhere in the tube. Evaporation of material from the heel and floor of the vessel is particularly noticeable because these areas of the vessel are the most reshaped and therefore exposed to the highest temperatures. As a result, the vessel area exposed to higher temperatures may have a silica-rich surface. Other areas of the vessel that are prone to boron deposition may have a boron-rich layer on the surface. This can result in the incorporation of boron into the surface of the glass in areas where boron is likely to adhere that are above the anneal point of the glass composition, but below the highest temperature the glass will experience during reshaping. The solution contained in the container can leach the boron from the boron-rich layer. As the boron-rich layer leaches out of the glass, a high silica glass network (gel) remains, which swells and distorts during hydration, and eventually spalls off the surface.

[0023] The glass container described herein alleviates at least two of the above problems.Specifically, the glass container has at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance.For example, the glass container can have a combination of resistance to delamination and improved strength; improved strength and high damage resistance; or resistance to delamination and high damage resistance.Each performance characteristic and the method of achieving these performance characteristics are described in further detail herein.

[0024] 1 and 2, one embodiment of a glass container 100 for storing a pharmaceutical formulation is illustrated generally in cross-section. The glass container 100 generally comprises a body 102. The body 102 extends between an inner surface 104 and an outer surface 106 and generally encloses an interior space 108. In the embodiment of the glass container 100 illustrated in FIG. 1, the body 102 generally comprises a wall portion 110 and a floor portion 112. The wall portion 110 continues into the floor portion 112 via a heel portion 114. The body 102 includes a thickened wall portion T extending between the inner surface 104 and the outer surface 106 as illustrated in FIG. 1. W has.

[0025] 1 as having a particular geometric configuration (i.e., a vial), it should be understood that the glass container 100 may have other geometric configurations, including, but not limited to, Vacutainers®, cartridges, syringes, ampoules, bottles, flasks, vials, tubes, beakers, etc. Additionally, it should be understood that the glass containers described herein may be used in a variety of applications, including, but not limited to, pharmaceutical packaging, beverage containers, etc. strength 1 and 2, in some embodiments described herein, the body 102 has a wall thickness T WThe glass container 100 includes a compressive stress layer 202 extending from at least the outer surface 106 of the body 102. The compressive stress layer 202 generally increases the strength of the glass container 100 and also improves the damage resistance of the glass container. Specifically, a glass container having a compressive stress layer 202 is generally able to withstand more severe surface damage, such as scratches, chips, and the like, without destruction, than a non-strengthened glass container, because the compressive stress layer 202 reduces the propagation of cracks in the compressive stress layer 202 from the surface damage.

[0026] In the embodiments described herein, the depth of layer of the compressive stress layer may be about 3 μm or more. In some embodiments, the depth of layer may be greater than 10 μm, or even greater than 20 μm. In some embodiments, the depth of layer may be greater than about 25 μm, or even greater than about 30 μm. For example, in some embodiments, the depth of layer may be greater than about 25 μm and less than about 150 μm. In some other embodiments, the depth of layer may be greater than about 30 μm and less than about 150 μm. In still other embodiments, the depth of layer may be greater than about 30 μm and less than about 80 μm. In some other embodiments, the depth of layer may be greater than about 35 μm and less than about 50 μm.

[0027] The compressive stress layer 202 generally has a surface compressive stress (i.e., compressive stress measured at the outer surface 106) of 150 MPa or more. In some embodiments, the surface compressive stress can be 200 MPa or more, or even 250 MPa or more. In some embodiments, the surface compressive stress can be 300 MPa or more, or even 350 MPa or more. For example, in some embodiments, the surface compressive stress can be about 300 MPa or more and about 750 MPa or less. In some other embodiments, the surface compressive stress can be about 400 MPa or more and about 700 MPa or less. In still other embodiments, the surface compressive stress can be about 500 MPa or more and about 650 MPa or less. Stress in ion-exchanged glass articles can be measured with a Fundamental Stress Meter (FSM) instrument. This instrument combines light entering and exiting the birefringent glass surface. The measured birefringence is then related to stress via a material constant, the stress optical coefficient or the photoelastic coefficient (SOC or PEC). Two parameters are obtained: the maximum surface compressive stress (CS) and the exchange depth of layer (DOL). Alternatively, the compressive stress and the depth of layer can be measured using a refractive near field stress measurement technique.

[0028] The compressive stress layer 202 extends from the outer surface 106 to the wall thickness T W Although shown and described herein as extending into the wall thickness T of the body 102 from the inner surface 104, in some embodiments, the body 102 may extend from the inner surface 104 to the wall thickness T of the body 102. W It should be understood that the second compressive stress layer may further include a second compressive stress layer extending into the wall thickness T of the body 102. In this embodiment, the depth of layer and surface compressive stress of the second compressive stress layer is W 202. The compressive stress layer 202 may form a mirror image of the compressive stress layer 202 about its centerline.

[0029] A number of different techniques may be used to form the compressive stress layer 202 in the body 102 of the glass container 100. For example, in embodiments where the body 102 is formed from an ion-exchangeable glass, the compressive stress layer 202 may be formed in the body 102 by ion exchange. In these embodiments, the compressive stress layer 202 is formed by placing the glass container in a molten salt bath to promote the exchange of relatively large ions in the molten salt with relatively small ions in the glass. A number of different exchange reactions may be used to achieve the compressive stress layer 202. In one embodiment, the bath may contain molten KNO3 salt, while the glass from which the glass container 100 is formed contains lithium and / or sodium ions. In this embodiment, potassium ions in the bath are exchanged for relatively small lithium and / or sodium ions in the glass, thereby forming the compressive stress layer 202. In another embodiment, the bath may contain NaNO3 salt, while the glass from which the glass container 100 is formed contains lithium ions. In this embodiment, sodium ions in the bath are exchanged for relatively small lithium ions in the glass, thereby forming the compressive stress layer 202.

[0030] In one particular embodiment, the compressive stress layer 202 may be formed by immersing the glass container in a molten salt bath of 100% KNO3 or a mixture of KNO3 and NaNO3. For example, in one embodiment, the molten salt bath may include KNO3 with about 10% or less NaNO3. In this embodiment, the glass from which the container is formed may include sodium ions and / or lithium ions. The temperature of the molten salt bath may be greater than or equal to 350°C and less than or equal to 500°C. In some embodiments, the temperature of the molten salt bath may be greater than or equal to 400°C and less than or equal to 500°C. In yet other embodiments, the temperature of the molten salt bath may be greater than or equal to 450°C and less than or equal to 475°C. The glass container may be held in the molten salt bath for a time sufficient to promote exchange of relatively large ions in the salt bath with relatively small ions in the glass to achieve the desired surface compressive stress and depth of layer. For example, the glass may be held in the molten salt bath for a time of greater than or equal to 0.05 hours and less than or equal to about 20 hours to achieve the desired depth of layer and surface compressive stress. In some embodiments, the glass container may be held in the molten salt bath for a period of 4 hours or more and about 12 hours or less. In other embodiments, the glass container may be held in the molten salt bath for a period of 5 hours or more and about 8 hours or less. In one exemplary embodiment, the glass container may be ion-exchanged in a molten salt bath containing 100% KNO3 at a temperature of about 400° C. or more and about 500° C. or less for a period of about 5 hours or more and about 8 hours or less.

[0031] Typically, the ion exchange process is carried out at a temperature above the strain point (T 歪み), however, in some embodiments, the compressive stress layer 202 is formed in a molten salt bath at a temperature above the strain point of the glass. This type of ion exchange strengthening is referred to herein as "high temperature ion exchange strengthening." In high temperature ion exchange strengthening, the smaller ions in the glass are exchanged with larger ions from the molten salt bath, as described above. When the smaller ions are exchanged with the larger ions at a temperature above the strain point, the stresses that develop are relieved or "relaxed." However, the replacement of the smaller ions in the glass by the larger ions creates a surface layer in the glass that has a lower coefficient of thermal expansion (CTE) than the rest of the glass. As the glass cools, the difference in CTE between the surface of the glass and the rest of the glass creates the compressive stress layer 202. This high temperature ion exchange technique is particularly well suited for strengthening glass articles such as glass containers having complex geometries, and typically allows for faster strengthening process times and greater layer depths compared to typical ion exchange processes.

[0032] 1 and 2, in an alternative embodiment, a compressive stress layer 202 may be introduced into the body 102 of the glass container 100 by thermal strengthening. The compressive stress layer is formed via thermal strengthening by heating the glass container and differentially cooling the surface of the glass compared to the bulk of the glass. Specifically, glass that is cooled quickly will have a larger molar volume (or a lower density) than glass that is cooled slowly. Thus, if the surface of the glass is intentionally cooled quickly, the surface of the glass will have a larger volume, and the interior of the glass (i.e., the remainder of the glass below the outer surface) will necessarily cool at a slower rate because heat must be removed from the bulk through the surface. The compressive stress layer 202 is formed by thermal strengthening from the outer surface 106 of the body 102 to the thickened wall T WBy forming a continuous gradient of molar volume (or thermal history / density) from 0.1 to 0.5, a compressive stress layer 202 is formed that has a radial stress profile (i.e., compressive stress drops radially with increasing distance from the exterior surface 106 of the body 102). Thermal strengthening processes are generally faster and less expensive than ion exchange processes. However, the surface compressive stress from thermal strengthening processes is generally lower than the surface compressive stress from ion exchange processes. In embodiments where a glass container is thermally strengthened, the resulting compressive stress layer is at the thickness T of the glass container. W For example, in some embodiments, the DOL extends from the outer surface 106 to a depth of thickness DOL of 22% or less of the thickness T W or even about 5% to about 22% of the thick portion T W The amount of the ion exchange resin may be about 10% to about 22% of the total amount of the ion exchange resin

[0033] In a typical thermal tempering process, the glass container 100 is first heated to its softening point, and then the exterior surface 106 of the body 102 is rapidly cooled below the softening point by a fluid, such as a gas jet, to create a temperature differential between the exterior surface 106 of the body 102 and the remainder of the body 102, as described above. This temperature differential between the exterior surface 106 and the remainder of the body causes a temperature difference between the exterior surface 106 and the thickened portion T of the body 102 to form a thin wall T W A compressive stress layer 202 is formed that extends along the glass. For example, the glass may be first heated to a temperature 50-150° C. above its softening point and then rapidly cooled to room temperature by directing a fluid at the glass. The fluid may include, but is not limited to, air, oil, or an oil-based fluid.

[0034] 1-3, in another embodiment, the glass container 100 may be formed from a laminated glass tube, which is convenient for forming a compressive stress layer 202 on at least the outer surface 106 of the body 102. The laminated glass generally comprises a glass core layer 204 and at least one glass cladding layer 206a. In the embodiment of the glass container 100 illustrated in FIG. 3, the laminated glass comprises a pair of glass cladding layers 206a, 206b. In this embodiment, the glass core layer 204 generally comprises a first surface 205a and a second surface 205b opposite the first surface 205a. The first glass cladding layer 206a is fused to the first surface 205a of the glass core layer 204, and the second glass cladding layer 206b is fused to the second surface 205b of the glass core layer 204. The glass cladding layers 206a, 206b are fused to the glass core layer 204 without any additional materials, such as adhesives, coating layers, etc., between the glass core layer 204 and the glass cladding layers 206a, 206b.

[0035] In the embodiment shown in FIG. 3, the glass core layer 204 has an average core thermal expansion coefficient CTE core and the glass cladding layers 206a, 206b are formed from a first glass composition having an average coefficient of thermal expansion CTE clad In the embodiments described herein, the core layer or the cladding layer is formed from a second glass composition having a different CTE such that a compressive stress layer is present in at least one of the core layer or the cladding layer. core is CTE clad In some embodiments, the CTE core is CTE clad , which creates a compressive stress in the glass cladding layers 206a, 206b without ion exchange or thermal strengthening. In some other embodiments, such as when the laminated glass comprises a single core layer and a single cladding layer, the CTE clad CTE core, which creates a compressive stress in the glass core layer without ion exchange or thermal strengthening.

[0036] The laminated glass tube from which the glass container is formed may be formed as described in U.S. Patent No. 4,023,953, incorporated herein by reference. In embodiments, the glass forming the glass core layer 204 has an average coefficient of thermal expansion (CTE) of less than or equal to the average coefficient of thermal expansion (CTE) of one of the glass cladding layers 206a, 206b. clad Average coefficient of thermal expansion CTE greater than core As the glass core layer 204 and the glass cladding layers 206a, 206b cool, compressive stress layers are generated in the glass cladding layers 206a, 206b due to the difference between the average thermal expansion coefficient of the glass core layer 204 and the average thermal expansion coefficient of the glass cladding layers 206a, 206b. When a container is formed using the laminated glass, these compressive stress layers extend from the outer surface 106 of the glass container 100 to the thick wall portion T. W Extending to the thick part T W In some embodiments, the compressive stress layer is formed at a thickness T from the outer surface of the body of the glass container to a thickness T of about 1 μm. W The thickness of the wall is approximately 90% of the thickness of the layer. W In some other embodiments, the compressive stress layer may extend from the outer surface of the body of the glass container to a thickness T W The thickness of the wall is approximately 33% of the thickness T W In yet another embodiment, the compressive stress layer may extend from the outer surface of the body of the glass container to a thickness T W The thickness of the wall is approximately 10% of the thickness T W It may extend into

[0037] After forming the laminate tube, the tube may be formed into a container shape using conventional tube converting techniques.

[0038] In some embodiments where the glass container is formed from laminated glass, at least one cladding layer forms the inner surface of the body of the glass container, such that the at least one glass cladding layer is in direct contact with the product stored in the glass container. In these embodiments, the at least one cladding layer may be formed from a glass composition that is resistant to delamination, as described in more detail herein. Thus, it should be understood that the at least one cladding layer may have a delamination factor of 10 or less, as described in more detail herein.

[0039] In other alternative embodiments, glass containers can be strengthened by applying a coating to the glass body. For example, a coating of an inorganic material, such as titania, can be applied to at least a portion of the exterior surface of the glass body by a soot deposition or vapor deposition process. The titania coating has a lower coefficient of thermal expansion than the glass onto which it is deposited. Upon cooling of the coating and glass, titania contracts less than the glass, resulting in tension at the surface of the glass body. In these embodiments, it should be understood that the surface compressive stress and depth of layer are measured from the surface of the coating, not the surface of the coated glass body. Although the inorganic coating material is described herein as including titania, it should be understood that other inorganic coating materials having suitably low coefficients of thermal expansion are also contemplated. In embodiments, the inorganic coating can have a coefficient of friction of less than 0.7 compared to a similarly coated container. As further described herein, the inorganic coating can also be thermally stable at temperatures of 250° C. or higher.

[0040] In other alternative embodiments, the glass body can be strengthened by a glass body with a high modulus coating that has a coefficient of thermal expansion equal to or greater than that of the underlying glass body. Strengthening is achieved by the difference in elastic modulus that imparts damage resistance, while the difference in thermal expansion creates compressive stresses at the glass surface (balanced with tensions in the high modulus coating). In these embodiments, it should be understood that the surface compressive stresses and layer depths are measured from the surface of the glass body, not the surface of the coated glass body. The high modulus makes it difficult to scratch and damage, and the underlying compressive layer prevents scratches and defects from progressing. Exemplary material pairs that demonstrate this effect are a sapphire coating on a 33-expansion borosilicate glass, or a zirconium oxide coating deposited on a 51-expansion borosilicate glass.

[0041] Based on the above, it should be understood that in some embodiments, the glass container may include a compressive stress layer that extends from at least the outer surface of the body into the thickness of the glass container. The compressive stress layer increases the mechanical strength of the glass container compared to a glass container that does not include a compressive stress layer. The compressive stress layer also increases the damage resistance of the glass container, such that the glass container can withstand more severe surface damage (i.e., scratches, chips, etc. that extend deep into the thickness of the glass container) without breaking compared to a glass container that does not include a compressive stress layer. Furthermore, it should also be understood that in some embodiments, the compressive stress layer may be formed in the glass container by ion exchange, by heat strengthening, by forming the glass container from laminated glass, or by applying a coating to the glass body. In some embodiments, the compressive stress layer may be formed by a combination of these techniques. Resistance to delamination In some embodiments, the glass container 100 may also resist delamination even after long-term exposure to certain chemical compositions stored in the container. As mentioned above, delamination may result from the release of silica-rich glass flakes into a solution contained in the glass container after long-term exposure to the solution. Thus, resistance to delamination may be characterized by the number of glass particles present in a solution contained in the glass container after exposure to the solution under certain conditions. To evaluate the long-term resistance of a glass container to delamination, an accelerated delamination test is utilized. This test may be performed on both ion-exchanged and non-ion-exchanged glass containers. This test consists of washing the glass container at room temperature for 1 minute and depyrogenating the container at about 320° C. for 1 hour. Then, fill the glass vessel with 20 mM glycine solution at pH 10 to 80-90%, cover the glass vessel, and heat the glass vessel rapidly to 100°C, then heat from 100°C to 121°C at a heating rate of 1 deg / min under a pressure of 2 atmospheres. The glass vessel and solution are kept at this temperature for 60 minutes, cooled to room temperature at a rate of 0.5 deg. / min, and this heating cycle and holding are repeated. The glass vessel is then heated to 50°C and held for 10 days or more for high temperature conditions. After heating, the glass vessel is dropped from a height of at least 18 inches (45.72 centimeters) onto a solid surface such as a laminate tile floor to remove any flakes or particles that are weakly attached to the inner surface of the glass vessel. The drop height can be appropriately estimated to prevent damage to large vials due to impact.

[0042] The solution contained in the glass vessel is then analyzed to determine the number of glass particles present per liter of solution. Specifically, the solution from the glass vessel is poured directly into the center of a Millipore Isopore membrane filter (Millipore #ATTP02500 held in an assembly with part numbers AP1002500 and M000025A0) connected to vacuum suction, and 5 mL is filtered through the filter within 10-15 seconds. An additional 5 mL of water is then used to rinse to remove buffer residues from the filter media. Granular flakes are then counted in reflectance mode by differential interference contrast microscopy (DIC) as described in "Differential interference contrast (DIC) microscopy and modulation contrast microscopy", Fundamentals of light microscopy and digital imaging. New York: Wiley-Liss, pp153-168. The field of view is set to approximately 1.5 mm x 1.5 mm, and particles larger than 50 μm are counted manually. Nine such measurements are made in the center of each filter membrane in a 3 × 3 pattern with no image overlap. If a larger area of ​​filter media was analyzed, the results are reported as equivalent areas (i.e., 20.25 mm2). 2) can be scaled to the original size (XY) of the glass flakes. Images retrieved from the optical microscope are examined with an image analysis program (Media Cybernetic's ImagePro Plus version 6.1) to measure and count the number of glass flakes present. This is accomplished as follows: highlight all of the features in the image that appear darker than the background by simple greyscale segmentation; then measure the length, width, area and perimeter of all of the highlighted features that have a length greater than 25 micrometers; then remove from the data all that are not obviously glass particles; then export the measurement data to a spreadsheet. Then extract and measure all of the features that are greater than 25 micrometers in length and that are lighter than the background; measure the length, width, area, perimeter and XY aspect ratio of all of the highlighted features that have a length greater than 25 micrometers; remove from the data all that are not obviously glass particles; and add the measurement data to the already exported data in the spreadsheet. The data in the spreadsheet is then sorted by feature length and binned according to size. Results reported are for features greater than 50 micrometers in length. Each of these groups is then counted and the counts reported for each of the samples.

[0043] A minimum of 100 mL of solution is tested. Thus, solutions from multiple smaller containers may be pooled to provide a total solution volume of 100 mL. For containers with a volume greater than 10 mL, the test is repeated for 10 containers formed from the same glass composition under the same processing conditions, and the particle count results are averaged for the 10 containers to determine the average particle count. Alternatively, for small containers, the test is repeated for 10 vials, each of which is analyzed, and the particle counts are averaged for the multiple tests to determine the average particle count per test. The particle count average for multiple containers encompasses potential differences in delamination behavior of individual containers. Table 1 summarizes some non-limiting examples of sample volumes and numbers of containers for testing.

[0044] [Table 1]

[0045] It should be understood that the above test is used to identify particles that are shed from the inner wall of the glass container due to delamination, not contaminant particles present in the container from the molding process, or particles that precipitate from a solution contained in the glass container due to a reaction between the solution and the glass. Specifically, delamination particles can be distinguished from contaminant glass particles based on the aspect ratio of the particle (i.e., the ratio of the maximum length of the particle to the thickness of the particle, or the ratio of the maximum dimension to the minimum dimension). Delamination produces granular flakes or slabs that have irregular shapes and have a maximum length that is typically greater than about 50 μm, and often greater than about 200 μm. The thickness of the flakes is usually greater than about 100 nm, and can be as thick as about 1 μm. Thus, the minimum aspect ratio of the flakes is typically greater than about 50. The aspect ratio can be greater than about 100, and often greater than about 1000. In contrast, contaminant glass particles will generally have a low aspect ratio, less than about 3. Thus, particles originating from delamination can be differentiated from contaminating particles based on their aspect ratio in microscopic observation. Other common non-glass particles include hair, fibers, metal particles, plastic particles and other contaminants and are therefore excluded during the course of inspection. Verification of the results can be achieved by evaluating the interior area of ​​the tested container. During the course of observation, evidence of epidermal erosion / pitting / flake removal is noted as described in "Nondestructive Detection of Glass Vial Inner Surface Morphology with Differential Interference Contrast Microscopy", Journal of Pharmaceutical Sciences, 101(4), 2012, pages 1378-1384.

[0046] The number of particles present after the accelerated peel test can be used to establish a peel factor for the set of vials tested. When the glass container has an average of less than 10 glass particles per test after the accelerated peel test, the peel factor is considered to be 10. When the glass container has an average of less than 9 glass particles per test after the accelerated peel test, the peel factor is considered to be 9. When the glass container has an average of less than 8 glass particles per test after the accelerated peel test, the peel factor is considered to be 8. When the glass container has an average of less than 7 glass particles per test after the accelerated peel test, the peel factor is considered to be 7. When a glass container is tested after an accelerated delamination test, it is considered to have a delamination factor of 6 when the glass container has an average of less than 6 glass particles per test having a minimum length of about 50 μm and an aspect ratio of more than about 50. When a glass container is tested after an accelerated delamination test, it is considered to have a delamination factor of 5 when the glass container has an average of less than 5 glass particles per test having a minimum length of about 50 μm and an aspect ratio of more than about 50. When a glass container is tested after an accelerated delamination test, it is considered to have a delamination factor of 4 when the glass container has an average of less than 3 glass particles per test having a minimum length of about 50 μm and an aspect ratio of more than about 50. Testing of glass containers that, after an accelerated delamination test, have an average of less than two glass particles per test having a minimum length of about 50 μm and an aspect ratio greater than about 50 is considered to have a delamination factor of 2. Testing of glass containers that, after an accelerated delamination test, have an average of less than one glass particle per test having a minimum length of about 50 μm and an aspect ratio greater than about 50 is considered to have a delamination factor of 1.After accelerated delamination testing, the glass container is considered to have a delamination factor of 0 when the glass particles have a minimum length of about 50 μm and an aspect ratio of more than about 50 per test. It should therefore be understood that the smaller the delamination factor, the more resistant the glass container is to delamination. In some embodiments described herein, at least the inner surface of the body of the glass container has a delamination factor of 10 or less (e.g., a delamination factor of 3, 2, 1 or 0). In some other embodiments, the entire body of the glass container, including both the inner surface and the outer surface, has a delamination factor of 10 or less (e.g., a delamination factor of 3, 2, 1 or 0).

[0047] In some embodiments, a glass container having a delamination factor of 10 or less can be obtained by forming a glass container with a barrier coating on the inner surface of the body such that the barrier coating is on the inner surface of the body. Referring to FIG. 5 as an example, a glass container 100 is shown generally with a barrier coating 131 disposed on at least a portion of the inner surface 104 of the body 102. The barrier coating 131 does not delaminate or degrade and prevents contact between a product stored in the interior space 108 of the glass container 100, such as a pharmaceutical composition, and the inner surface 104 of the body 102, thereby mitigating delamination of the glass container. The barrier coating is generally impermeable to aqueous solutions, water-insoluble, and hydrolytically stable.

[0048] In some embodiments described herein, the barrier coating 131 is a robust inorganic coating permanently adhered to the inner surface 104 of the glass container 100. The barrier coating 131 can be a metal nitride coating, a metal oxide coating, a metal sulfide coating, SiO2, diamond-like carbide, graphene, or a carbide coating. For example, in some embodiments, the robust inorganic coating can be formed from at least one metal oxide, such as Al2O3, TiO2, ZrO2, SnO, SiO2, Ta2O5, Nb2O5, Cr2O3, VO5, ZnO, or HfO2. In some other embodiments, the robust inorganic coating can be formed from a combination of two or more metal oxides, such as Al2O3, TiO2, ZrO2, SnO, SiO2, Ta2O5, Nb2O5, Cr2O3, VO5, ZnO, or HfO2. In some other embodiments, the barrier coating 131 may comprise a first layer of a first metal oxide deposited on the interior surface of the glass container and a second layer of a second metal oxide deposited on the first layer. In these embodiments, the barrier coating 131 may be deposited using a variety of deposition techniques, including but not limited to atomic layer deposition, chemical vapor deposition, physical vapor deposition, and the like. Alternatively, the barrier coating may be applied with one or more liquid application techniques, such as dip coating, spray coating, or plasma coating. Spray coating techniques may include high volume low pressure (HVLP) and low volume low pressure (LVLP) spray coating, electrostatic spray coating, airless spray coating, ultrasonic spray with airless spray coating, aerosol jet coating, and inkjet coating. Plasma coating techniques may include standard primary and secondary plasma coating, microwave assisted plasma coating, and atmospheric pressure plasma coating, and the like.

[0049] Although embodiments of the barrier coating 131 are described herein as including inorganic materials, it should be understood that in some embodiments, the barrier coating 131 can be an organic coating. For example, in embodiments in which the barrier coating 131 is an organic coating, the organic coating can be selected from polybenzimidazoles, polybisoxazoles, polybisthiazoles, polyetherimides, polyquinolines, polythiophenes, phenylene sulfides, polysulfones, polycyanurates, parylenes, fluorinated polyolefins including polytetrafluoroethylene and other fluoro-substituted polyolefins, perfluoroalkoxy polymers, polyetheretherketones (PEEK), polyamides, epoxies, polypolyphenols, polyurethane acrylates, cyclic olefin copolymers and cyclic olefin polymers. The organic coating may include polyolefins including polyethylene, polyethylene oxide, polypropylene, polyethylene / propylene copolymers, polyethylene / vinyl acetate copolymers, polyvinyl chloride, polyacrylates, polymethacrylates, polystyrene, polyterpenes, polyanhydrides, polymaleic anhydrides, polyformaldehyde, polyacetals and copolymers of polyacetals, dimethyl or diphenyl or mixed methyl / phenyl polysiloxanes, perfluorinated siloxanes and other substituted siloxanes, polyimides, polycarbonates, polyesters, paraffins and waxes, or various combinations thereof. In some embodiments, the organic coating used as the barrier coating 131 may include dimethyl, diphenyl or mixed methyl / phenyl polysiloxanes. Alternatively, the organic coating may be polycarbonate or polyethylene terephthalate. In some embodiments, the barrier coating 131 may be formed from a laminate structure including one or more of the aforementioned polymers and / or copolymers.

[0050] The barrier coating may be utilized in conjunction with glass containers formed from any glass composition. However, the barrier coating is particularly suitable for use in conjunction with glass containers formed from glass compositions that do not exhibit resistance to delamination when formed into glass containers. Such glass compositions may include, but are not limited to, those referred to as Type I Class A, Type I Class B, and Type II glass compositions in accordance with ASTM standard E438-92 (2011), entitled "Standard Specification for Glasses in Laboratory Apparatus." Such glass compositions may have the requisite chemical durability requirements of the ASTM standard, but do not exhibit resistance to delamination. For example, Table 2 below lists a number of non-limiting examples of Type I Class B glass compositions that do not exhibit resistance to delamination. Thus, the barrier coatings described herein may be utilized on at least the interior surfaces of containers formed from these compositions, resulting in the containers having a delamination factor of 10 or less.

[0051] [Table 2]

[0052] In some alternative embodiments, a glass container having a delamination factor of 10 or less is achieved by forming the glass container such that it has homogeneous compositional characteristics, thereby reducing the susceptibility of the glass container to delamination, as described in co-pending U.S. Patent Application No. 13 / 912,457, filed June 7, 2013, entitled "Delamination Resistant Glass Containers," and assigned to Corning Incorporated. Specifically, it is believed that delamination of the glass container may be at least partially attributable to inhomogeneity in the glass composition at least within the glass container, as described above. Reducing such compositional inhomogeneity results in a glass container having a delamination factor of 10 or less.

[0053] 1 and 6, in some embodiments, the glass containers described herein are compositionally homogenous across the thickness of the glass body 102 in each of the wall, heel and floor portions, such that at least the inner surface 104 of the body has a delamination factor of 10 or less. Specifically, FIG. 6 illustrates a schematic cross-section of a portion of a wall portion 110 of a glass container 100. The glass body 102 of the glass container 100 is approximately 10 nm (D in FIG. 6) below the inner surface 104 of the glass container 100. LR1 ) from the inner surface 104 of the glass container to a depth D LR2 The inner region 120 extends into the thickness of the wall portion 110 up to about 10 nm below the inner surface 104. The inner region, which extends from about 10 nm below the inner surface 104, is distinguished from the composition in the first 5-10 nm below the surface by experimental artifacts. At the start of the Dynamic Secondary Ion Mass Spectroscopy (DSIMS) analysis to determine the composition of the glass, the first 5-10 nm are not included in the analysis due to three concerns: variable sputtering rates of ions from the surface due to extrinsic carbon, establishment of a partial steady state charge due to variable sputtering rates, and mixing of species while steady state sputtering conditions are established. As a result, the first two analytical data points are eliminated. Thus, the inner region 120 is a region of the D LR2 ~DLR1 The thickness T is equal to LR It should be understood that the glass composition in the inner region has a thickness T LR In relation to the thickness T, the thickness T has sufficient continuous layer homogeneity to prevent delamination of the glass body even after prolonged exposure to the solution contained in the interior space of the glass container. LR is at least about 100 nm. LR In some other embodiments, the thickness T LR is at least about 200 nm, or even about 250 nm. LR is at least about 300 nm, or even about 350 nm. LR In some embodiments, the interior region 120 has a thickness T of at least about 1 μm, or even at least about 2 μm. LR It may extend up to.

[0054] The inner region extends from 10 nm below the inner surface 104 of the glass container 100 to a depth D LR2 Although described herein as extending into the thickness of portion 110 to 100 mm, it should be understood that other embodiments are possible. For example, despite the experimental artifacts discussed above, the interior region having continuous layer homogeneity may actually extend from the inner surface 104 of glass container 100 into the thickness of the wall portion, and thus, in some embodiments, the thickness T LR is a depth D from the inner surface 104 LR2 It is hypothesized that the thickness T LR may be at least about 100 nm. In some embodiments, the thickness T LR may be at least about 150 nm. LR may be at least about 200 nm, or even about 250 nm.LR may be at least about 300 nm, or even about 350 nm. LR In some embodiments, the interior region 120 has a thickness T of at least about 1 μm, or even at least about 2 μm. LR It may extend to.

[0055] In embodiments where the glass container is formed such that it has continuous layer homogeneity, the phrase "continuous layer homogeneity" means that the concentration of a component of the glass composition (e.g., SiO2, Al2O3, Na2O, etc.) in the interior region does not differ from the concentration of the same component at a midpoint in the thickness of the glass layer that comprises the interior region to an extent that would result in delamination of the glass body upon prolonged exposure to the solution contained in the glass container. For example, in embodiments where the glass container is formed from a single glass composition, the glass body comprises a single layer of glass, and the concentration of the component in the interior region is compared to the concentration of the same component at a point along a midpoint line MP that bisects the glass body between the inner surface 104 and the outer surface 106 to determine whether continuous layer homogeneity exists. However, in embodiments where the glass container is formed from a laminated glass in which a glass cladding layer of the laminated glass forms the interior surface of the glass container, the concentration of the component in the interior region is compared to the concentration of the same component at a point along a midpoint line that bisects the glass cladding layer that forms the interior surface of the glass container. In embodiments described herein, the continuous layer homogeneity in the interior region of the glass body is such that the extremes (i.e., minimum or maximum) of the layer concentration of each of the components of the glass composition in the interior region 120 are about 80% or more and about 120% or less of the same component at the midpoint of the glass layer that includes the interior region 120. As used herein, continuous layer homogeneity refers to the state of the glass container when the glass container is in an as-formed state or after one or more surface treatments, such as etching, that are applied to at least the interior surface of the glass container. In other embodiments, the continuous layer homogeneity in the interior region of the glass body is such that the extremes of the layer concentration of each of the components of the glass composition in the interior region 120 are about 90% or more and about 110% or less of the same component at the midpoint of the thickness of the glass layer that includes the interior region 120.In yet other embodiments, the continuous layer homogeneity in the interior region of the glass body is such that the extremes of the layer concentrations of each of the components of the glass composition in the interior region 120 are greater than or equal to about 92% and less than or equal to about 108% of the same component at the midpoint of the glass thickness of the glass layer that comprises the interior region 120. In some embodiments, the continuous layer homogeneity does not include components of the glass composition present in an amount less than about 2 mol.%.

[0056] As used herein, the term "as-formed" refers to the composition of the glass container 100 after it has been formed from glass stock, but before it has been subjected to any of the additional processing steps, such as ion exchange strengthening, coating, ammonium sulfate treatment, etc. In some embodiments, the term "as-formed" includes the composition of the glass container 100 after it has been formed and subjected to an etching process to selectively remove all or a portion of at least the interior surface of the glass container. In the embodiments described herein, the layer concentrations of constituents in the glass composition are determined by collecting composition samples from the thickness of the glass body in the region of interest using dynamic secondary ion mass spectroscopy (DSIMS) analysis. In the embodiments described herein, the composition profile is sampled from a region of the interior surface 104 of the glass body 102. The sampled region is 1 mm 2 This technique provides a composition profile of species in the glass as a function of depth from the inner surface of the glass body for a sample area.

[0057] Forming a glass container with continuous layer homogeneity as described above generally improves the glass container's resistance to delamination. Specifically, providing an interior region that is compositionally homogeneous (i.e., the extremes of the concentration of a component in the interior region are within + / - 20% of the same component at the midpoint of the thickness of the glass layer that includes the interior region) prevents localized concentrations of components of the glass composition that may be susceptible to leaching, thereby reducing the loss of glass particles from the interior surface of the glass container even if those components are leached from the glass surface.

[0058] As described herein, a container having continuous layer homogeneity in the as-formed state does not have a coating, including an inorganic coating and / or an organic coating, applied to the inner surface of the glass body. It should therefore be understood that the body of the glass container is formed of a substantially single composition that extends from the inner surface of the body to a depth of at least 250 nm, or even at least 300 nm. The term "single composition" refers to the fact that the glass forming the portion of the body that extends into the wall thickness of the body to a depth of at least 250 nm, or even at least 300 nm from the inner surface is a single composition of matter, as compared to coating materials applied to other materials of the same or different composition. For example, in some embodiments, the body of the container may be composed of a single glass composition. In other embodiments, the body of the container may be composed of laminated glass such that the inner surface of the body has a single composition that extends from the inner surface to a depth of at least 250 nm, or even at least 300 nm. The glass container may comprise an interior region, as described above, extending from the interior surface or from 10 nm to a depth of at least 100 nm below the interior surface, and the interior region may have a continuous layer homogeneity.

[0059] 1 and 7, in some embodiments, the glass containers described herein may also have a homogenous surface composition across the inner surface 104 of the body 102 such that, in the as-formed state of the glass container, at least the inner surface 104 of the body 102, including in the wall, heel and floor portions, has a delamination factor of 10 or less. FIG. 7 illustrates a schematic cross-section of a portion of a wall portion 110 of a glass container 100. The glass container 100 has a surface region 130 that extends across the entire inner surface of the glass container. The surface region 130 is a depth D from the inner surface 104 of the glass container 100 into the thickness of the glass body toward the outer surface. SR Thus, the surface region 130 has a depth D SR The thickness T is equal to SR It should be understood that in some embodiments, the surface region has a depth D of at least about 10 nm from the inner surface 104 of the glass container 100. SR In some other embodiments, the surface region 130 extends to a depth D of at least about 50 nm. SR In some other embodiments, the surface region 130 may extend to a depth D of about 10 nm to about 50 nm. SR It should therefore be understood that surface region 130 extends to a shallower depth than interior region 120. The glass composition of the surface region may extend to a depth D of the interior region. SR In this regard, the glass body has sufficient continuous surface homogeneity to prevent delamination even after prolonged exposure to solutions contained within the interior space of the glass vessel.

[0060] In the embodiments described herein, the phrase "continuous surface homogeneity" means that the concentration of a component of the glass composition (e.g., SiO2, Al2O3, Na2O, etc.) at an independent point in the surface region does not differ to an extent that the concentration of the same component at any second independent point in the surface region would result in delamination of the glass body upon prolonged exposure to the solution contained in the glass container. In the embodiments described herein, the continuous surface homogeneity in the surface region is such that for an independent point on the inner surface 104 of the glass container, the extreme (i.e., minimum or maximum) surface concentration of each of the components in the surface region 130 at the independent point is about 70% or more and about 130% or less of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100 in the as-molded state. For example, in FIG. 7, three independent points (A, B, and C) are illustrated on the inner surface 104 of the wall portion 110. Each point is spaced at least about 3 mm from an adjacent point. The extreme surface concentrations of each of the constituents at point "A" in surface region 130 are about 70% or more and about 130% or less than the same constituents at points "B" and "C" in surface region 130. With reference to the heel portion of the container, the separate points may be centered approximately at the apex of the heel, and adjacent points are located at least 3 mm from the apex of the heel along the container floor and container wall, with the distance between the points being limited by the container radius and the height of the sidewall (i.e., the transition from the sidewall to the container shoulder).

[0061] In some embodiments, the continuous surface homogeneity in the surface region is such that the extremes of the surface concentration of each of the components of the glass composition in the surface region 130, for any independent point on the inner surface 104 of the glass container 100, are about 75% or more and about 125% or less of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100. In some other embodiments, the continuous surface homogeneity in the surface region is such that the extremes of the surface concentration of each of the components of the glass composition in the surface region 130, for any independent point on the inner surface 104 of the glass container 100, are about 80% or more and about 120% or less of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100. In yet other embodiments, the continuous surface homogeneity in the surface region is such that the extremes of the surface concentration of each of the components of the glass composition in the surface region 130, for any independent point on the inner surface 104 of the glass container 100, are greater than or equal to about 85% and less than or equal to about 115% of the same component in the surface region 130 at any second independent point on the inner surface 104 of the glass container 100. In embodiments described herein, the surface concentrations of the components of the glass composition in the surface region are measured by X-ray photoelectron spectroscopy. In some embodiments, the continuous surface homogeneity in the surface region excludes components of the glass composition present in an amount less than about 2 mol.%.

[0062] The uniformity of the surface concentration of the glass component in the surface region 130 is generally indicative of the tendency of a glass composition to delaminate and shed glass particles from the inner surface 104 of the glass container 100. A glass composition has improved resistance to delamination when it has continuous surface uniformity in the surface region 130 (i.e., when the extremes of the surface concentration of a glass component in the surface region 130 at any independent point on the inner surface 104 are + / - 30% of the same component in the surface region 130 at any second independent point on the inner surface 104).

[0063] Glass containers with continuous layer homogeneity and / or continuous surface homogeneity can be achieved using various techniques. For example, in some embodiments, at least the inner surface 104 of the body 102 of the glass container is etched such that at least the inner surface of the glass container has a delamination factor of 10 or less, resulting in a glass container with continuous layer homogeneity and / or continuous surface homogeneity. Specifically, as described above, compositional variations in the glass due to volatilization of species from the glass and subsequent re-deposition of the volatilized species during container formation are believed to be one mechanism that results in delamination. The thin skin of volatilized and re-deposited species on the inner surface of the glass container is compositionally heterogeneous and hydrolytically vulnerable, and thus alkali and boron species are rapidly lost from the skin during exposure to a pharmaceutical composition. This behavior leaves a large surface area silica-rich layer. Exposure of the pharmaceutical composition to the silica-rich layer causes the layer to swell and eventually peel off from the inner surface of the body (i.e., delamination). However, etching the inner surface of the glass container body removes this thin skin layer and provides a continuous layer uniformity and / or continuous surface uniformity to at least the inner surface of the glass container body.

[0064] In some embodiments described herein, the body of the glass container is etched to remove a layer of glass material from the inner surface of the glass body. The etching is sufficient to remove a thin skin layer of volatilized and redeposited species, thereby providing a continuous layer homogeneity and / or continuous surface homogeneity to at least the inner surface of the glass body, such that at least the inner surface of the glass body has a delamination factor of 10 or less. For example, in some embodiments, the body of the glass container is etched to remove glass material from the inner surface of the glass body to a depth of 1 μm, or even 1.5 μm. In some other embodiments, the body of the glass container may be etched to remove glass material to a depth of more than 1.5 μm, including but not limited to 2 μm, 3 μm, or even 5 μm. In these embodiments, at least the interior surface of the glass container may be formed from a glass composition that meets the criteria for Type I, Class A (Type IA) or Type I, Class B (Type IB) glass according to ASTM standard E438-92 (2011), entitled "Standard Specification for Glasses in Laboratory Apparatus." Borosilicate glasses meet the Type I (A or B) criteria and are routinely used in pharmaceutical packaging. Examples of borosilicate glasses include, but are not limited to, Corning® Pyrex® 7740, 7800, Wheaton 180, 200 and 400, Schott Duran®, Schott Fiolax®, KIMAX® N-51A, Gerresheimer GX-51 Flint, and others.

[0065] In one embodiment, etching can be accomplished by exposing the interior surface of the glass container to an acid solution or combination of acid solutions. The acid solutions can include, but are not limited to, sulfuric acid, nitric acid, hydrochloric acid, hydrofluoric acid, hydrobromic acid, and phosphoric acid. For example, the acid solution can include a mixture of 1.5M hydrofluoric acid and 0.9M sulfuric acid. These acid solutions effectively remove a thin skin layer of volatilized and redeposited organic solution without leaving a deficient "leach layer" on the interior surface of the glass container. Alternatively, etching can be accomplished by exposing the interior surface of the glass container to a base solution or combination of base solutions. Suitable base solutions include, for example, sodium hydroxide, potassium hydroxide, ammonium hydroxide, or combinations thereof. Alternatively, etching can be accomplished in the order of acid solution followed by base solution, or in the reverse order.

[0066] Although one particular etching process is described herein, it should be understood that other etching processes may also be used, for example, the etching processes disclosed in U.S. Patent No. 2,106,744, U.S. Patent Application Publication No. 2011 / 0165393, U.S. Patent Application Publication No. 2013 / 0122306, and U.S. Patent Application Publication No. 2012 / 0282449 may also be used to etch at least the interior surface of the glass container.

[0067] In yet another embodiment, continuous layer homogeneity and / or continuous surface homogeneity may be achieved in a glass container by forming the glass container from a glass composition whose components form species with relatively low vapor pressure (i.e., species with low volatility) at the temperatures required for remolding from the glass stock into a glass container of the desired container shape. Because these components form species with relatively low vapor pressure at the remolding temperatures, the components are less likely to volatilize and vaporize from the surface of the glass, thereby forming a glass container having a compositionally homogeneous surface on the interior surface of the glass container and through the thickness of the glass container.

[0068] Certain components of the glass composition may be sufficiently volatile at glass forming and reforming temperatures that may result in compositional inhomogeneity and subsequent delamination. The forming and reforming temperatures of the glass composition generally correspond to temperatures at which the glass composition has a viscosity in the range of about 200 poise to about 100 kpoise. Thus, in some embodiments, the glass composition from which the glass container is formed forms species that are significantly volatile at temperatures corresponding to a viscosity in the range of about 200 poise to about 100 kpoise (i.e., about 10 -3 In some embodiments, the glass composition forming the glass container does not include any components that significantly volatilize at a temperature corresponding to a viscosity in the range of about 1 kpoise to about 50 kpoise. In some other embodiments, the glass composition forming the glass container does not include any components that significantly volatilize at a temperature corresponding to a viscosity in the range of about 1 kpoise to about 20 kpoise. In some other embodiments, the glass composition forming the glass container does not include any components that significantly volatilize at a temperature corresponding to a viscosity in the range of about 1 kpoise to about 10 kpoise. Without wishing to be bound by theory, compounds that significantly volatilize under these conditions include, but are not limited to, boron and boron compounds, phosphorus and phosphorus compounds, zinc and zinc compounds, fluorine and fluorine compounds, chlorine and chlorine compounds, tin and tin compounds, and sodium and sodium compounds.

[0069] In some embodiments described herein, the glass container is generally formed from an aluminosilicate glass composition, such as an alkali aluminosilicate glass composition or an alkaline earth aluminosilicate glass composition. As described herein above, boron-containing species in the glass can be highly volatile at the high temperatures used in forming and reforming the glass, which can lead to delamination of the resulting glass container. Moreover, glass compositions containing boron are also susceptible to phase separation. Thus, in the embodiments described herein, the boron concentration in the glass composition forming the glass container is limited to reduce both delamination and phase separation. In some embodiments, the glass composition forming the glass container comprises about 1.0 mol.% or less of oxides of boron and / or boron-containing compounds, including but not limited to B2O3. In some of these embodiments, the concentration of boron and / or oxides of boron-containing compounds in the glass composition can be about 0.5 mol.% or less, about 0.4 mol.% or less, or even about 0.3 mol.% or less. In some of these embodiments, the concentration of oxides of boron and / or boron-containing compounds in the glass composition may be about 0.2 mol.% or less, or even about 0.1 mol.% or less. In some other embodiments, the glass composition is substantially free of boron and boron-containing compounds.

[0070] Like boron, phosphorus also forms species in the glass composition that are generally highly volatile at the high temperatures used in forming and reforming glass. Thus, phosphorus in the glass composition can lead to compositional inhomogeneity in the final glass container, which can result in delamination. Thus, in the embodiments described herein, the concentration of phosphorus and phosphorus-containing compounds (such as P2O5, etc.) in the glass composition from which the glass container is formed is limited to mitigate delamination. In some embodiments, the glass composition from which the glass container is formed contains about 0.3 mol.% or less of oxides of phosphorus and / or phosphorus-containing compounds. In some of these embodiments, the concentration of oxides of phosphorus and / or phosphorus-containing compounds in the glass composition can be about 0.2 mol.% or less, or even about 0.1 mol.% or less. In some other embodiments, the glass composition is substantially free of phosphorus and phosphorus-containing compounds.

[0071] Similar to boron and phosphorus, zinc also forms species in the glass composition that are generally highly volatile at the high temperatures used in forming and reforming glass. Thus, zinc in the glass composition can lead to compositional inhomogeneity in the final glass container, which can result in delamination. Thus, in the embodiments described herein, the concentration of zinc and zinc-containing compounds (such as ZnO, etc.) in the glass composition from which the glass container is formed is limited to mitigate delamination. In some embodiments, the glass composition from which the glass container is formed comprises about 0.5 mol.% or less of oxides of zinc and / or zinc-containing compounds. In some other embodiments, the glass composition from which the glass container is formed comprises about 0.3 mol.% or less of oxides of zinc and / or zinc-containing compounds. In some of these embodiments, the concentration of oxides of zinc or zinc-containing compounds in the glass composition can be about 0.2 mol.% or less, or even about 0.1 mol.% or less. In some other embodiments, the glass composition is substantially free of zinc and zinc-containing compounds.

[0072] Lead and bismuth also form highly volatile species in the glass composition at the high temperatures used in forming and reforming glass. Thus, in the embodiments described herein, the concentrations of lead, bismuth, lead-containing compounds, and bismuth-containing compounds in the glass composition forming the glass container are limited to mitigate delamination. In some embodiments, the oxides of lead, the oxides of bismuth, the lead-containing compounds, and / or the bismuth-containing compounds are each present in the glass composition at a concentration of about 0.3 mol.% or less. In some of these embodiments, the oxides of lead, the oxides of bismuth, the lead-containing compounds, and / or the bismuth-containing compounds are each present in the glass composition at a concentration of about 0.2 mol.% or less, or even less than about 0.1 mol.%. In some other embodiments, the glass composition is substantially free of lead and / or bismuth, and compounds containing lead and / or bismuth.

[0073] The oxides of tin, chlorine and fluorine containing species are also highly volatile at the high temperatures used in forming and reforming glass. Thus, in the embodiments described herein, chlorine, fluorine and tin oxides, as well as tin-, chlorine- or fluorine-containing compounds, are present in the glass composition at concentrations that do not adversely affect the resistance to delamination of the resulting glass. Specifically, chlorine, fluorine and tin oxides, as well as tin-, chlorine- or fluorine-containing compounds, are present in the glass composition forming the glass container at concentrations of about 0.5 mol.% or less, or even about 0.3 mol.% or less. In some embodiments, the glass composition is substantially free of tin, chlorine and fluorine, as well as tin-, chlorine- or fluorine-containing compounds.

[0074] While some embodiments of the glass container may be free of readily volatile components as described above, in certain other embodiments, the glass container may be formed from a glass composition that includes these volatile components, such as when the glass container includes a barrier layer.

[0075] The glass composition from which the container is formed is one that does not undergo phase separation. As used herein, the term "phase separation" refers to the separation of a glass composition into distinct phases, each phase having different compositional characteristics. For example, alkali borosilicate glasses are generally known to phase separate into boron-rich and silica-rich phases at elevated temperatures (such as molding and remolding temperatures). In some embodiments described herein, the concentration of oxides of boron in the glass composition is sufficiently low (i.e., about 1.0 mol.% or less) so that the glass composition does not undergo phase separation.

[0076] In one exemplary embodiment, the glass container is formed from a delamination-resistant glass composition, such as the alkaline earth alumino-silicate glass composition described in U.S. Patent Application Serial No. 13 / 660,141, filed October 25, 2012, entitled "Alkaline Earth Alumino-Silicate Glass Compositions with Improved Chemical and Mechanical Durability" (Attorney Docket No. SP11-241), which is incorporated by reference in its entirety. This first exemplary glass composition generally includes a combination of SiO2, Al2O3, at least one alkaline earth oxide, and alkali oxides including at least Na2O and KO. In some embodiments, the glass composition may also be free of boron and boron-containing compounds. The combination of these components provides a glass composition that is resistant to chemical decomposition and also suitable for chemical strengthening by ion exchange. In some embodiments, the glass composition may further include trace amounts of one or more additional oxides, such as, for example, SnO2, ZrO2, ZnO, and the like. These components may be added as fining agents and / or to further enhance the chemical durability of the glass composition.

[0077] In a first exemplary glass composition embodiment, the glass composition generally includes SiO2 in an amount of about 65 mol.% or more and about 75 mol.% or less. In some embodiments, SiO2 is present in the glass composition in an amount of about 67 mol.% or more and about 75 mol.% or less. In some other embodiments, SiO2 is present in the glass composition in an amount of about 67 mol.% or more and about 73 mol.% or less. In each of these embodiments, the amount of SiO2 present in the glass composition can be about 70 mol.% or more, or even about 72 mol.% or more.

[0078] The first exemplary glass composition also includes Al2O3. Al2O3, together with alkali oxides such as Na2O present in the glass composition, improves the susceptibility of the glass to ion exchange strengthening. Moreover, the addition of Al2O3 to the composition reduces the tendency of alkali constituents (such as Na and K) to leach from the glass, thereby increasing the resistance of the composition to hydrolysis. In addition, the addition of Al2O3 above about 12.5 mol.% may also increase the softening point of the glass, thereby reducing the formability of the glass. Thus, the glass compositions described herein generally include Al2O3 in an amount of about 6 mol.% or more and about 12.5 mol.% or less. In some embodiments, the amount of Al2O3 in the glass composition is about 6 mol.% or more and about 10 mol.% or less. In some other embodiments, the amount of Al2O3 in the glass composition is about 7 mol.% or more and about 10 mol.% or less.

[0079] The first exemplary glass composition also includes at least two alkali oxides. The alkali oxides promote the ion exchangeability of the glass composition, which in turn promotes chemical strengthening of the glass. The alkali oxides also lower the softening point of the glass, thereby offsetting the increase in the softening point due to the high SiO2 concentration in the glass composition. The alkali oxides also help improve the chemical durability of the glass composition. The alkali oxides are generally present in the glass composition in an amount of about 5 mol.% or more and about 12 mol.% or less. In some of these embodiments, the amount of alkali oxides can be about 5 mol.% or more and about 10 mol.% or less. In some other embodiments, the amount of alkali oxides can be about 5 mol.% or more and about 8 mol.% or less. In all of the glass compositions described herein, the alkali oxides include at least Na2O and KO. In some embodiments, the alkali oxides further include Li2O.

[0080] The ion exchangeability of the glass composition is imparted to the glass composition primarily by the amount of alkali oxide Na2O initially present in the glass composition prior to ion exchange. Specifically, to achieve a desired compressive stress and depth of layer in the glass composition upon ion exchange strengthening, the glass composition includes Na2O in an amount of about 2.5 mol.% or more and about 10 mol.% or less, based on the molecular weight of the glass composition. In some embodiments, the glass composition may include Na2O in an amount of about 3.5 mol.% or more and about 8 mol.% or less. In some of these embodiments, the glass composition may include Na2O in an amount of about 6 mol.% or more and about 8 mol.% or less.

[0081] As mentioned above, the alkali oxides in the glass composition also include K2O. The amount of K2O present in the glass composition is also related to the ion exchangeability of the glass composition. Specifically, as the amount of K2O present in the glass composition increases, the compressive stress obtained through ion exchange decreases. Therefore, it is desirable to limit the amount of K2O present in the glass composition. In some embodiments, the amount of K2O is greater than 0 mol.% and not greater than about 2.5 mol.% based on the molecular weight of the glass composition. In some of these embodiments, the amount of K2O present in the glass composition is not greater than about 0.5 mol.% based on the molecular weight of the glass composition.

[0082] In some embodiments, the alkali oxide in the first exemplary glass composition further comprises Li2O. The inclusion of Li2O in the glass composition further reduces the softening point of the glass. In embodiments in which the alkali oxide comprises Li2O, Li2O may be present in an amount greater than or equal to about 1 mol.% and less than or equal to about 3 mol.%. In some embodiments, Li2O may be present in the glass composition in an amount greater than about 2 mol.% and less than or equal to about 3 mol.%. However, in some other embodiments, the glass composition may be substantially free of lithium and lithium-containing compounds.

[0083] The alkaline earth oxides in the first exemplary glass composition improve the meltability of the glass batch materials and enhance the chemical durability of the glass composition. The presence of alkaline earth oxides in the glass composition also reduces the susceptibility of the glass to delamination. In the glass compositions described herein, the glass composition generally includes at least one alkaline earth oxide in a concentration of about 8 mol.% or more, or even 8.5 mol.% and about 15 mol.% or less. In some embodiments, the glass composition may include about 9 mol.% to about 15 mol.% alkaline earth oxide. In some of these embodiments, the amount of alkaline earth oxide in the glass composition may be about 10 mol.% to about 14 mol.%.

[0084] The alkaline earth oxides in the first exemplary glass composition may include MgO, CaO, SrO, BaO, or combinations thereof. For example, in the embodiments described herein, the alkaline earth oxides may include MgO. In some embodiments, MgO may be present in the glass composition in an amount that is about 2 mol.% or more and about 7 mol.% or less based on the molecular weight of the glass composition, or even in an amount that is about 3 mol.% or more and about 5 mol.% or less based on the molecular weight of the glass composition.

[0085] In some embodiments, the alkaline earth oxide in the first exemplary glass composition also includes CaO. In these embodiments, CaO is present in the glass composition in an amount of about 2 mol.% to about 7 mol.% or less, based on the molecular weight of the glass composition. In some embodiments, CaO is present in the glass composition in an amount of about 3 mol.% to about 7 mol.% or less, based on the molecular weight of the glass composition. In some of these embodiments, CaO may be present in the glass composition in an amount of about 4 mol.% or more and about 7 mol.% or less. In some other embodiments, CaO may be present in the glass composition in an amount of about 5 mol.% or more and about 6 mol.% or less, such as when CaO substitutes for MgO in the alkaline earth oxides to lower the liquid temperature and increase the liquid viscosity. In still other embodiments, CaO may be present in the glass in an amount of about 2 mol.% or more and about 5 mol.% or less, such as when SrO substitutes for MgO in the alkaline earth oxides to lower the liquid temperature and increase the liquid viscosity.

[0086] In some embodiments described herein, the alkaline earth oxide further comprises at least one of SrO or BaO. The inclusion of SrO reduces the liquidus temperature of the glass composition, thereby improving the formability of the glass composition. In some embodiments, the glass composition may comprise SrO in an amount greater than 0 mol.% and less than or equal to about 6.0 mol.%. In some other embodiments, the glass composition may comprise SrO in an amount greater than about 0 mol.% and less than or equal to about 5 mol.%. In some of these embodiments, the glass composition may comprise SrO in an amount greater than or equal to about 2 mol.% and less than or equal to about 4 mol.% in order to reduce the liquidus temperature and increase the liquidus viscosity, such as when CaO substitutes for MgO in the alkaline earth oxides. In some other embodiments, the glass composition may comprise SrO in an amount between about 1 mol.% and about 2 mol.%. In still other embodiments, SrO may be present in the glass composition in an amount greater than or equal to about 3 mol.% and less than or equal to about 6 mol.% in order to reduce the liquidus temperature and increase the liquidus viscosity, such as when SrO substitutes for MgO in the alkaline earth oxides.

[0087] In embodiments in which the glass composition includes BaO, BaO may be present in an amount greater than about 0 mol.% and less than about 2 mol.%. In some of these embodiments, BaO may be present in the glass composition in an amount less than or equal to about 1.5 mol.%, or even less than or equal to about 0.5 mol.%. However, in some other embodiments, the glass composition is substantially free of barium and compounds of barium.

[0088] In embodiments of the glass compositions described herein, the glass compositions generally contain less than about 1 mol.% boron or an oxide of boron, such as B2O3. For example, in some embodiments, the glass compositions may include about 0 mol.% or more B2O3 and 1 mol.% or less B2O3. In some other embodiments, the glass compositions may include about 0 mol.% or more B2O3 and 0.6 mol.% or less B2O3. In still other embodiments, the glass compositions are substantially free of boron and boron compounds, such as B2O3. Specifically, it has been determined that forming the glass compositions with relatively small amounts of boron or boron compounds (i.e., 1 mol.% or less) or without boron or boron compounds significantly enhances the chemical durability of the glass compositions. Additionally, it has been determined that by forming the glass composition with a relatively small amount of boron or boron compounds or without boron or boron compounds, the ion exchangeability of the glass composition is improved by reducing the process time and / or process temperature required to achieve a particular compressive stress and / or depth of layer value.

[0089] In some embodiments of the glass compositions described herein, the glass compositions are substantially free of phosphorus and phosphorus-containing compounds, including but not limited to P2O5. Specifically, it has been determined that forming the glass composition without phosphorus or compounds of phosphorus enhances the chemical durability of the glass composition.

[0090] In addition to SiO2, Al2O3, alkali oxides and alkaline earth oxides, the first exemplary glass composition described herein may optionally contain, for example, SnO2, As2O3 and / or Cl -The glass composition may further include one or more fining agents, such as from NaCl. If a fining agent is present in the glass composition, the fining agent may be present in an amount of about 1 mol.% or less, or even about 0.5 mol.% or less. For example, in some embodiments, the glass composition may include SnO2 as a fining agent. In these embodiments, SnO2 may be present in the glass composition in an amount greater than about 0 mol.% and less than or equal to about 0.30 mol.%.

[0091] Moreover, the glass compositions described herein may include one or more additional metal oxides to further improve the chemical durability of the glass composition. For example, the glass composition may further include ZnO or ZrO2, each of which further improves the resistance of the glass composition to chemical attack. In these embodiments, the additional metal oxide may be present in an amount that is greater than or equal to about 0 mol.% and less than or equal to about 2.0 mol.%. For example, if the additional metal oxide is ZrO2, ZrO2 may be present in an amount less than or equal to about 1.5 mol.%. Alternatively, or additionally, the additional metal oxide may include ZnO in an amount less than or equal to about 2.0 mol.%. In some embodiments, ZnO may be included as a substitution for one or more of the alkaline earth oxides. For example, in embodiments in which the glass composition includes the alkaline earth oxides MgO, CaO, and SrO, the amount of MgO may be reduced to lower the liquidus temperature and increase the liquidus viscosity, as described above. In these embodiments, in addition to or instead of CaO and / or SrO, ZnO may be added to the glass composition as a partial replacement for MgO.

[0092] Based on the above, in one embodiment, the first exemplary glass composition may include about 65 mol.% to about 75 mol.% SiO2; about 6 mol.% to about 12.5 mol.% Al2O3; and about 5 mol.% to about 12 mol.% alkali oxides, which should be understood to include Na2O and K2O. K2O may be present in an amount of 0.5 mol.% or less. The glass composition may also include about 8.0 mol.% to about 15 mol.% alkaline earth oxides. The glass composition may be susceptible to strengthening by ion exchange.

[0093] In another embodiment of the first exemplary glass composition, the glass composition includes about 67 mol.% to about 75 mol.% SiO2; about 6 mol.% to about 10 mol.% Al2O3; about 5 mol.% to about 12 mol.% alkali oxides; and about 9 mol.% to about 15 mol.% alkaline earth oxides. The alkali oxides include at least Na2O and KO. The glass composition is free of boron and boron compounds and is susceptible to ion exchange, which promotes chemical strengthening of the glass and improves mechanical durability.

[0094] In yet another embodiment of the first exemplary glass composition, the glass composition may include about 67 mol.% to about 75 mol.% SiO2; about 6 mol.% to about 10 mol.% Al2O3; about 5 mol.% to about 12 mol.% alkali oxides; and about 9 mol.% to about 15 mol.% alkaline earth oxides. The alkaline earth oxides include at least one of SrO and BaO. The glass composition is free of boron and boron compounds and is susceptible to ion exchange, which promotes chemical strengthening of the glass and improves mechanical durability.

[0095] In some embodiments described herein, glass containers with continuous surface homogeneity and / or continuous layer homogeneity can be obtained by utilizing a forming process that provides a uniform temperature history for at least the inner surface of the glass container body. For example, in one embodiment, the glass container body can be formed at a forming temperature and / or forming speed that reduces the volatilization of chemical species from the glass composition from which the body is formed. Specifically, in order to form the glass stream into the desired shape, both the viscosity of the glass and the forming speed need to be controlled. If the viscosity is high, the forming speed needs to be slow, while if the viscosity is low, the forming speed can be high. The bulk composition and temperature of the glass are the most important factors that affect the viscosity. By adjusting the temperature to match the viscosity at each stage in the forming process, it is possible to use the same forming process for different glasses. Thus, one approach to reduce volatilization from the glass melt is to carry out the process at a lower temperature (higher viscosity). This approach is disadvantageous because it also requires a reduction in the yield and capacity of the forming tool, which ultimately leads to higher costs. Temperature is a major influencing factor for volatilization in the two exemplary compositions, and in all cases, reducing the temperature (and therefore rate) reduces the driving force for volatilization losses, as shown in FIG. 16. Viscosities relevant to the tube-to-vial conversion process range from 200P (maximum temperature, during the cutting and drilling operations) to 20,000P (minimum temperature, during the tube forming and finishing steps). For a typical 51-expansion borosilicate glass, these viscosities are approximately 1100-1650°C. The main temperature range of interest is 1350-1650°C, as volatilization is significantly reduced at lower temperatures.

[0096] In other embodiments, glass containers with continuous surface homogeneity and / or continuous layer homogeneity can be obtained by molding the body. There are numerous methods of forming a glass melt into a container shape using a mold. All are based on introducing a "gob" of molten glass at a uniformly high temperature into a molding machine. In blow-blow molding, the gob is first blown with pressurized air through an orifice (shaping the lip / finish) to form a preform (smaller than the final product). The preform (or parison) is then placed into a second mold where it is further blown against the mold surface, which defines the final shape of the container. In press-blow molding, the gob is held by a ring that defines the lip / finish, and a plunger is pressed into the gob to form a preform. The preform is then placed into a second mold and blown against the mold surface to form the final container shape. The molding process generally provides a uniform temperature history for the body during forming, resulting in continuous surface homogeneity and / or continuous layer homogeneity on at least the interior surface of the glass body, which may reduce the susceptibility of the glass body to delamination. For example, molten glass may be formed into a container shape and the temperature of the glass controlled during cooling, such that the glass body cools monotonically from the glass melt. Monotonic cooling is achieved when the temperature of the glass body is reduced from a molten state to solidification without any intermediate temperature increases. This results in less volatilization compared to processes that convert tubes into vials. This type of cooling may be facilitated by using molding processes such as blow molding, press-blow molding, and blow-blow molding. In some embodiments, these techniques may be used to form glass containers having a delamination factor of 10 or less from Type I Class B glass compositions.

[0097] The glass compositions described herein are formed by mixing a batch of frits (e.g., powders of SiO2, Al2O3, alkali oxides, alkaline earth oxides, etc.) such that the batch of frits has a desired composition. The batch of frits is then heated to form a molten glass composition, which is then cooled and solidified to form the glass composition. During solidification (i.e., if the glass composition is plastically deformable), the glass composition may be formed using standard shaping techniques to shape the glass composition into the desired final form. Alternatively, the glass composition may be shaped into a stock form, such as a sheet, tube, etc., which is then reheated and formed into a glass container 100.

[0098] The glass compositions described herein may be formed into various forms, such as, for example, sheets, tubes, and the like. The chemically durable glass compositions are particularly suitable for use in forming pharmaceutical packages for containing pharmaceutical formulations, such as liquids, powders, and the like. For example, the glass compositions described herein may be used to form glass containers, such as vials, ampoules, cartridges, syringe bodies, and / or any other glass containers for storing pharmaceutical formulations. Moreover, the ability to chemically strengthen the glass compositions via ion exchange can be utilized to improve the mechanical durability of such pharmaceutical packaging. Thus, it should be appreciated that in at least one embodiment, the glass compositions are incorporated into pharmaceutical packages to improve the chemical and / or mechanical durability of the pharmaceutical packaging.

[0099] Further, in some embodiments, the glass container may be made in accordance with DIN 12116, ISO 695, ISO 719, ISO 720, USP <660> The glass composition may be formed from a glass composition that is chemically durable and resistant to degradation as determined by the European Pharmacopoeia 3.2.1 test and / or the European Pharmacopoeia 3.2.1 test.

[0100] Specifically, the DIN 12116 standard is a measure of the resistance of glass to decomposition when placed in an acidic solution. The DIN 12116 standard is divided into individual classes. Class S1 has a 0.7 mg / dm 2 The following weight losses are specified: Class S2: 0.7 mg / dm 2 ~1.5mg / dm 2 The following weight losses are specified: Class S3: 1.5 mg / dm 2 ~15mg / dm 2 The following weight loss limits are specified: 2 A weight loss of more than 100% is specified. The glass compositions described herein have an acid resistance of class S3 or better according to DIN 12116, with some embodiments having an acid resistance of at least class S2 or better, or even class S1. It should be understood that a lower class rank has improved acid resistance performance. Thus, a composition graded S1 has better acid resistance than a composition graded class S2.

[0101] The ISO 695 standard is a measure of the resistance of glass to decomposition when placed in an alkaline solution. The ISO 695 standard is divided into separate classes. Class A1 includes a 0.01% to 0.01% alkali metal salt content of 75 mg / dm 2 The following weight losses are specified: Class A2: 75 mg / dm 2 ~175mg / dm 2 The following weight losses are specified: 2 The glass compositions described herein have a base resistance of Class A2 or better according to ISO 695, with some embodiments having Class A1 base resistance. It should be understood that a lower class rank has improved base resistance performance. Thus, a composition graded A1 has better base resistance than a composition graded Class A2.

[0102] The glass composition forming the glass container is chemically durable and resistant to degradation as determined by the ISO 720 standard, which is a measure of the resistance of glass to degradation in distilled water (i.e., hydrolytic resistance of glass). Non-ion-exchanged samples of glass are evaluated according to the ISO 720 protocol. Ion-exchanged samples of glass are evaluated according to a modified ISO 720 protocol in which the glass is crushed to the particle size required by the ISO 720 standard, ion-exchanged in a molten salt bath of 100% KNO3 at a temperature of 450°C for at least 5 hours to induce a compressive stress layer in the individual glass particles, and then tested according to the ISO 720 standard. The ISO 720 standard is divided into individual types. Type HGA1 specifies an extracted Na2O equivalent of 62 μg or less; Type HGA2 specifies an extracted Na2O equivalent of greater than 62 μg and less than or equal to 527 μg; and Type HGA3 specifies an extracted Na2O equivalent of greater than 527 μg and less than or equal to 930 μg. The glass compositions described herein have ISO 720 hydrolysis resistance of Type HGA2 or greater, with some embodiments having Type HGA1 hydrolysis resistance or greater. It should be understood that a lower class rank has improved hydrolysis resistance performance. Thus, compositions graded HGA1 have better hydrolysis resistance than compositions graded HGA2.

[0103] The glass compositions forming the glass containers are also chemically durable and resistant to degradation as determined by ISO 719, which is a measure of the resistance of glass to degradation in distilled water (i.e., hydrolytic resistance of glass). Non-ion-exchanged samples of glass are evaluated according to the ISO 719 protocol. Ion-exchanged samples of glass are evaluated with a modified ISO 719 protocol in which the glass is crushed to the particle size required by ISO 719, ion-exchanged in a molten salt bath of 100% KNO3 at a temperature of 450°C for at least 5 hours to induce a compressive stress layer in the individual glass particles, and then tested according to ISO 719. The ISO 719 standard is divided into individual types. Type HGB1 specifies an extracted Na2O equivalent of 31 μg or less; Type HGB2 specifies an extracted Na2O equivalent of more than 31 μg and less than or equal to 62 μg; Type HGB3 specifies an extracted Na2O equivalent of more than 62 μg and less than or equal to 264 μg; Type HGB4 specifies an extracted Na2O equivalent of more than 264 μg and less than or equal to 620 μg; and Type HGB5 specifies an extracted Na2O equivalent of more than 620 μg and less than or equal to 1085 μg. The glass compositions described herein have an ISO 719 hydrolysis resistance of Type HGB2 or greater, with some embodiments having a Type HGB1 hydrolysis resistance. It should be understood that a lower class rank has improved hydrolysis resistance performance. Thus, compositions graded as HGB1 have better hydrolysis resistance than compositions graded as HGB2.

[0104] USP <660> With respect to the USP 3.2.1 test and / or the European Pharmacopoeia 3.2.1 test, the glass containers described herein have a Type 1 chemical durability. <660> and European Pharmacopoeia 3.2.1 testing is performed on intact glass vessels rather than on crushed glass particles, and therefore USP <660> and the European Pharmacopoeia 3.2.1 test can be used to directly assess the chemical durability of the inner surface of glass containers.

[0105] When referring to the above-mentioned classifications according to ISO 719, ISO 720, ISO 695 and DIN 12116, it should be understood that a glass composition or glass article having a particular classification "or better" means that the performance of the glass composition is as good as or better than the particular classification. For example, a glass article having an ISO 719 hydrolytic resistance of "HGB2" or better may have an ISO 719 classification of HGB2 or HGB1. Damage resistance As described herein above, glass containers may be subject to damage, such as impact damage, scratches, and / or abrasions, as the containers are processed and filled. Such damage often occurs from contact between separate glass containers or between the glass containers and manufacturing equipment. This damage may generally result in through cracks that may reduce the mechanical strength of the container and compromise the integrity of the contents of the container. Thus, in some embodiments described herein, the glass container 100 further comprises a smooth coating 160 disposed about at least a portion of the exterior surface 106 of the body 102, as shown in FIG. 8. In some embodiments, the smooth coating 160 may be disposed on at least the exterior surface 106 of the body 102 of the glass container, while in other embodiments, one or more intermediate coatings may be disposed between the smooth coating and the exterior surface 106 of the body 102, such as when an inorganic coating is used to induce compressive stress on the surface of the body 102. The smooth coating reduces the coefficient of friction of a portion of the body 102 due to the coating, thereby reducing the occurrence of abrasion and surface damage to the exterior surface 106 of the glass body 102. In essence, the coating allows the container to "slide" relative to other objects (or containers), thereby reducing the likelihood of surface damage to the glass. Additionally, the smooth coating 160 also acts as a cushion on the body 102 of the glass container 100, thereby reducing the damaging effects of blunt impacts on the glass container.

[0106] As used herein, the term smooth means that the coefficient of friction of a coating applied to the exterior surface of a glass container is lower than that of an uncoated glass container, resulting in a glass container with improved resistance to damage such as scratches, abrasions, etc.

[0107] Various properties of the coated glass containers (i.e., coefficient of friction, horizontal compressive strength, four-point bend strength, transparency, colorlessness, etc.) may be measured while the coated glass containers are in an as-coated state (i.e., after application of the coating and without any additional processing) or after one or more processing steps, such as those similar or equivalent to those performed on a pharmaceutical filling line, including, but not limited to, washing, lyophilization, depyrogenation, autoclaving, etc.

[0108] Depyrogenation is a process of removing pyrogens from a substance. Depyrogenation of glass articles, such as pharmaceutical packages, can be performed by subjecting a sample to a heat treatment, where the sample is heated to an elevated temperature for a period of time. For example, depyrogenation can include heating a glass container at a temperature of about 250° C. to about 380° C. for a period of about 30 seconds to about 72 hours, including but not limited to 20 minutes, 30 minutes, 40 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, 24 hours, 48 ​​hours, and 72 hours. After heat treatment, the glass container is cooled to room temperature. One conventional depyrogenation condition commonly employed in the pharmaceutical industry is a heat treatment at a temperature of about 250° C. for about 30 minutes. However, it is expected that the heat treatment time can be reduced if a higher temperature is used. The coated glass containers described herein can be exposed to an elevated temperature for a period of time. The elevated temperature and time associated with the heating step described herein may or may not be sufficient to depyrogenate the glass container. However, it should be understood that some of the temperatures and times associated with the heating steps described herein are sufficient to dehydrogenate a coated glass container, such as the coated glass containers described herein. For example, a coated glass container as described herein may be exposed to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for a time period of 30 minutes.

[0109] As used herein, lyophilization conditions (i.e., the lyophilization step) refers to a process in which a sample is filled with a liquid containing the protein and then frozen at -100°C, followed by sublimation of the water at -15°C under reduced pressure for 20 hours.

[0110] As used herein, autoclave conditions refer to steam purging the sample at 100°C for 10 minutes, followed by exposing the sample to a 121°C environment with a 20 minute dwell time, followed by heat treatment at 121°C for 30 minutes.

[0111] The coefficient of friction (μ) of a portion of a coated glass container having a smooth coating may have a lower coefficient of friction than the surface of an uncoated glass container formed from the same glass composition. The coefficient of friction (μ) is a quantitative measurement of friction between two surfaces and depends on the mechanical and chemical properties of the first and second surfaces, including surface roughness and environmental conditions such as, but not limited to, temperature and humidity. As used herein, the coefficient of friction measurement for a coated glass container 100 is reported as the coefficient of friction between the outer surface of a first glass container (having an outer diameter of about 16.00 mm to about 17.00 mm) and the outer surface of a second glass container equivalent to the first glass container, where the first glass container and the second glass container have the same body and coating composition (if applicable) and have been exposed to the same environment before, during, and after manufacture. Unless otherwise specified herein, the coefficient of friction refers to the maximum coefficient of friction measured in a vial overlap test fixture as described herein, measured at a normal load of 30N. However, it should be understood that a coated glass container that exhibits a maximum coefficient of friction at a particular applied load will also exhibit the same or better (i.e., smaller) maximum coefficient of friction when the load is smaller. For example, if a coated glass container exhibits a maximum coefficient of friction of 0.5 or less under an applied load of 50N, the coated glass container will also exhibit a maximum coefficient of friction of 0.5 or less under an applied load of 25N.

[0112] In the embodiments described herein, the coefficient of friction of glass containers (both coated and uncoated) is measured in a vial overlap test fixture. The test fixture 300 is shown diagrammatically in FIG. 9. The same apparatus can also be used to measure the friction force between two glass containers placed in the fixture. The vial overlap test fixture 300 comprises a first clamp 312 and a second clamp 322 arranged in a cross configuration. The first clamp 312 comprises a first fixed arm 314 coupled to a first base 316. The first fixed arm 314 has a first glass container 310 attached thereto, which is held fixed relative to the first clamp 312. Similarly, the second clamp 322 comprises a second fixed arm 324 coupled to a second base 326. A second glass container 320 is attached to a second fixed arm 324, and the glass container 320 is fixedly held relative to a second clamp 322. The first glass container 310 is positioned by the first clamp 312 and the second glass container 320 is positioned by the second clamp 322 such that the long axes of the first glass container 310 and the second glass container 320 are disposed at an angle of approximately 90° to each other on a horizontal plane defined by the x and y axes.

[0113] The first glass container 310 is positioned to contact the second glass container 320 at contact point 330. The normal force is applied in a direction perpendicular to the horizontal plane defined by the xy axis. The normal force may be applied by a static weight or other force applied to the second clamp 322 relative to the stationary first clamp 312. For example, a weight may be placed on the second base 326 and the first base 316 may be placed on a stable surface, thereby inducing a measurable force between the first glass container 310 and the second glass container 320 at the contact point 330. Alternatively, the force may be applied by a mechanical device such as a UMT (Universal Mechanical Tester) machine.

[0114] The first clamp 312 or the second clamp 322 may be moved relative to the other in a 45° direction with the long axis of the first glass container 310 and the long axis of the second glass container 320. For example, the first clamp 312 may be fixed and the second clamp 322 may be moved so that the second glass container 320 crosses the first glass container 310 in the direction of the x-axis. A similar mechanism is described by RL De Rosa et al., "Scratch Resistant Polyimide Coatings for Alumino Silicate Glass Surfaces", The Journal of Adhesion, 78:113-127, 2002. To measure the coefficient of friction, the force required to move the second clamp 322 and the normal force applied to the first and second glass containers 310, 320 are measured with a load cell, and the coefficient of friction is calculated as the quotient of the ratio of the friction force and the normal force. The fixture is operated in an environment of 25°C and 50% relative humidity.

[0115] In the embodiments described herein, the portion of the coated glass container having a smooth coating has a coefficient of friction of about 0.7 or less against a similar coated glass container, as measured by the above-mentioned vial stacking tool. In other embodiments, the coefficient of friction may be about 0.6 or less, or even about 0.5 or less. In some embodiments, the portion of the coated glass container having a smooth coating has a coefficient of friction of about 0.4 or less, or even about 0.3 or less. Coated glass containers having a coefficient of friction of about 0.7 or less generally exhibit high resistance to damage caused by friction, and therefore have high mechanical properties. For example, conventional glass containers (without a smooth coating) may have a coefficient of friction of more than 0.7.

[0116] In some embodiments described herein, the coefficient of friction of a portion of a coated glass container having a smooth coating is at least 20% lower than the coefficient of friction of a surface of an uncoated glass container formed from the same glass composition. For example, the coefficient of friction of a portion of a coated glass container having a smooth coating may be at least 20%, at least 25%, at least 30%, at least 40%, or even at least 50% lower than the coefficient of friction of a surface of an uncoated glass container formed from the same glass composition.

[0117] In some embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after exposure to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for 30 minutes (i.e., depyrogenated conditions). In other embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after exposure for 30 minutes to a temperature of about 250° C., about 260° C., about 270° C., about 280° C., about 290° C., about 300° C., about 310° C., about 320° C., about 330° C., about 340° C., about 350° C., about 360° C., about 370° C., about 380° C., about 390° C., or about 400° C. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase by more than about 30% after exposure for 30 minutes to a temperature of about 260° C. In other embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after being exposed to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for 30 minutes. In other embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase by more than about 0.5 (i.e., about 0.45, about .04, about 0.35, about 0.3, about 0.25, about 0.2, about 0.15, about 0.1, or even about 0.5) after being exposed to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for 30 minutes.In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase at all after being exposed to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for 30 minutes.

[0118] In some embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after being immersed in a water bath for 10 minutes at a temperature of about 70° C. In other embodiments, a portion of a coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after being immersed in a water bath for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour at a temperature of about 70° C. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase by more than about 30% after being immersed in a water bath for 10 minutes at a temperature of about 70° C. In other embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after being immersed in a water bath for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour at a temperature of about 70° C. In some embodiments, the coefficient of friction of a portion of a coated glass container having a smooth coating may not increase at all after being immersed in a water bath for 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or even 1 hour at a temperature of about 70° C.

[0119] In some embodiments, the portion of the coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after exposure to freeze-drying conditions. In other embodiments, the portion of the coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after exposure to freeze-drying conditions. In some embodiments, the coefficient of friction of the portion of the coated glass container having a smooth coating may not increase by more than about 30% after exposure to freeze-drying conditions. In other embodiments, the coefficient of friction of the portion of the coated glass container having a smooth coating may not increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after exposure to freeze-drying conditions. In some embodiments, the coefficient of friction of the portion of the coated glass container having a smooth coating may not increase at all after exposure to freeze-drying conditions.

[0120] In some embodiments, the portion of the coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less after exposure to autoclave conditions. In other embodiments, the portion of the coated glass container having a smooth coating may have a coefficient of friction of about 0.7 or less (i.e., about 0.6 or less, about 0.5 or less, about 0.4 or less, or even about 0.3 or less) after exposure to autoclave conditions. In some embodiments, the coefficient of friction of the portion of the coated glass container having a smooth coating may not increase by more than about 30% after exposure to autoclave conditions. In other embodiments, the coefficient of friction of the portion of the coated glass container having a smooth coating may not increase by more than about 30% (i.e., about 25%, about 20%, about 15%, or even about 10%) after exposure to autoclave conditions. In some embodiments, the coefficient of friction of the portion of the coated glass container having a smooth coating may not increase at all after exposure to autoclave conditions.

[0121] In some embodiments, after a glass container 100 having a smooth coating 160 is rubbed by a comparable glass container with a normal force of 30 N, the coefficient of friction of the rubbed area of ​​the glass container 100 does not increase by more than about 20% after further rubbed by the comparable glass container at the same location with a normal force of 30 N. In other embodiments, after a glass container 100 having a smooth coating 160 is rubbed by a comparable glass container with a normal force of 30 N, the coefficient of friction of the rubbed area of ​​the glass container 100 does not increase by more than about 15%, or even more than 10%, after further rubbed by the comparable glass container at the same location with a normal force of 30 N. However, it is not necessary that all embodiments of a glass container 100 having a smooth coating 160 exhibit such properties.

[0122] The coated glass containers described herein have horizontal compressive strength. The horizontal compressive strength described herein is measured by a horizontal compression apparatus 500, which is shown in FIG. 4 as a schematic diagram. The coated glass container 100 is tested by placing the container horizontally between two platens 502a, 502b oriented parallel to the long axis of the glass container, as shown in FIG. 4. A mechanical load 504 is then applied to the coated glass container 100 by the platens 502a, 502b in a direction perpendicular to the long axis of the glass container. The loading rate for compressing the vial is 0.5 in / min, which means that the platens move towards each other at a rate of 0.5 in / min. The horizontal compressive strength is measured at 25° C. and 50% relative humidity. The horizontal compressive strength measurement can be determined as the probability of failure at a selected vertical compressive load. As used herein, failure occurs when the glass container breaks under horizontal compression in at least 50% of the samples. In some embodiments, the coated glass container may have a horizontal compressive strength that is at least 10%, 20%, or 30% greater than an uncoated vial.

[0123] 8 and 9, horizontal compression strength measurements can also be performed on abraded glass containers. Specifically, the test fixture 300 can be operated to create damage such as surface scratches or marring on the outer surface of the coated glass container 100 that reduces the strength of the coated glass container. The glass container is then subjected to the horizontal compression method described above, but now the container is placed between two platens with the scratches facing outward parallel to the platens. The scratches can be characterized by a selected vertical pressure applied by the vial overlapping fixture and the scratch length. Unless otherwise specified, scratches on abraded glass containers for the horizontal compression method are characterized by a scratch length of 20 mm created with a vertical load of 30 N.

[0124] The coated glass container can be evaluated for horizontal compressive strength after heat treatment. The heat treatment can be exposure to a temperature of about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C or about 400°C for 30 minutes. In some embodiments, the horizontal compressive strength of the coated glass container is not reduced by more than about 20%, 30%, or even 40% after being exposed to a heat treatment such as those described above and then scraped as described above. In one embodiment, the horizontal compressive strength of the coated glass container is not reduced by more than about 20% after being exposed to a heat treatment at about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C or about 400°C for 30 minutes and then abraded.

[0125] In some other embodiments, the glass container 100 having the smooth coating 160 may be thermally stable at high temperatures. As used herein, the phrase "thermally stable" means that the smooth coating 160 applied to the glass container remains substantially intact on the surface of the glass container even after exposure to high temperatures, such that the mechanical properties of the coated glass container, specifically the coefficient of friction and horizontal compressive strength, are minimally, if at all, affected after exposure. This indicates that the smooth coating remains adhered to the surface of the glass even after exposure to high temperatures, and continues to protect the glass container from mechanical damage, such as abrasion, impact, and the like. The glass container having the smooth coating described herein may be thermally stable after heating to a temperature of at least about 250°C, or even about 260°C, for 30 minutes.

[0126] In the embodiments described herein, a coated glass container having a smooth coating (i.e., a coated glass container) is considered to be thermally stable if it meets both the coefficient of friction criterion and the horizontal compressive strength criterion after heating to a specific temperature and holding at that temperature for a specific time. To determine whether the coefficient of friction criterion is met, the coefficient of friction of a first coated glass container is measured in an as-received state (i.e., before heat exposure) using a test fixture shown in FIG. 9 with a 30N applied load. A second coated glass container (i.e., a glass container having the same glass composition and the same coating composition as the first coated glass container) is exposed to heat under specified conditions and cooled to room temperature. The coefficient of friction of the second glass container is then measured using the test fixture shown in FIG. 9 by scraping the coated glass container with a 30N applied load to produce a scrape (i.e., a "scratch") having a length of approximately 20 mm. If the coefficient of friction of the second coated glass container is less than 0.7 and the surface of the glass of the second glass container in the scratched area does not have any observable damage, the coefficient of friction criterion meets the purpose of measuring the thermal stability of the smooth coating. As used herein, the term "observable damage" means that the surface of the glass of the scratched area of ​​the glass container contains less than 6 glass cracks per 0.5 cm long scratched area when observed under a Nomarski or differential interference contrast (DIC) spectroscopic microscope with an LED or halogen light source at 100 times magnification. The definition of the criteria for glass cracks or glass breaks is given in GD Quinn, "NIST Recommended Practice Guide: Fractography of Ceramics and Glasses", NIST special publication, 960-17 (2006).

[0127] To determine whether the horizontal compressive strength criterion is met, the first coated glass container is abraded under a load of 30N in a test fixture shown in FIG. 9 to form a 20 mm scratch. The first coated glass container is then subjected to a horizontal compression test as described herein to measure the residual strength of the first coated glass container. A second coated glass container (i.e., a glass container having the same glass composition and the same coating composition as the first coated glass container) is exposed to heat under specified conditions and cooled to room temperature. The second coated glass container is then abraded under a load of 30N in a test fixture as shown in FIG. 9. The second coated glass container is then subjected to a horizontal compression test as described herein to measure the residual strength of the second coated glass container. If the residual strength of the second coated glass container is not reduced by more than about 20% compared to the first coated glass container, the horizontal compressive strength criterion meets the objective of determining the thermal stability of the smooth coating.

[0128] In embodiments described herein, a coated glass container is considered thermally stable if the coefficient of friction and horizontal compressive strength criteria are met after exposing the coated glass container to a temperature of at least about 250° C., or even about 260° C., for about 30 minutes (i.e., the coated glass container is thermally stable at a temperature of at least about 250° C., or even about 260° C., for a time of about 30 minutes). Thermal stability may also be evaluated at temperatures from about 250° C. to about 400° C. or less. For example, in some embodiments, a coated glass container will be considered thermally stable if the criteria are met at a temperature of at least about 270° C., or even about 280° C., for a time of about 30 minutes. In yet other embodiments, a coated glass container will be considered thermally stable if the criteria are met at a temperature of at least about 290° C., or even about 300° C., for a time of about 30 minutes. In further embodiments, the coated glass container will be considered thermally stable if the criteria are met at a temperature of at least about 310° C., or even at a temperature of about 320° C., for a time period of about 30 minutes. In yet other embodiments, the coated glass container will be considered thermally stable if the criteria are met at a temperature of at least about 330° C., or even at a temperature of about 340° C., for a time period of about 30 minutes. In still other embodiments, the coated glass container will be considered thermally stable if the criteria are met at a temperature of at least about 350° C., or even at a temperature of about 360° C., for a time period of about 30 minutes. In some other embodiments, the coated glass container will be considered thermally stable if the criteria are met at a temperature of at least about 370° C., or even at a temperature of about 380° C., for a time period of about 30 minutes. In still other embodiments, the coated glass container will be considered thermally stable if the criteria are met at a temperature of at least about 390° C., or even at a temperature of about 400° C., for a time period of about 30 minutes.

[0129] The coated glass containers disclosed herein may also be thermally stable over a range of temperatures, meaning that the coated glass container is thermally stable by meeting the coefficient of friction criteria and horizontal compressive strength criteria at each temperature in the range. For example, in the embodiments described herein, the coated glass container may be thermally stable at temperatures of at least about 250°C or even about 260°C to about 400°C. In some embodiments, the coated glass container may be thermally stable at temperatures of at least about 250°C or even about 260°C to about 350°C. In some other embodiments, the coated glass container may be thermally stable at temperatures of at least about 280°C to about 350°C. In still other embodiments, the coated glass container may be thermally stable at least about 290°C to about 340°C. In other embodiments, the coated glass container may be thermally stable over a range of temperatures from about 300°C to about 380°C. In other embodiments, the coated glass container may be thermally stable over a range of temperatures from about 320°C to about 360°C.

[0130] Mass loss refers to a measurable characteristic of a coated glass container that is related to the amount of volatiles liberated from the coated glass container when the coated glass container is exposed to a selected elevated temperature for a selected time. Mass loss generally indicates mechanical degradation of the coating due to thermal exposure. Because the glass body of the coated glass container does not exhibit measurable mass loss at the measured temperature, the mass loss test provides mass loss data only for smooth coatings applied to the glass container as detailed herein. Several factors can affect mass loss. For example, the amount of organic material that is removable from the coating can affect mass loss. Breaking of the carbon backbone and side chains in the polymer will theoretically result in 100% removal of the coating. Organometallic polymer materials typically lose all of the organic components, but leave the inorganic components behind. Therefore, mass loss results are scaled based on how much of the coating is organic and inorganic (e.g., % silica of the coating) in a complete theoretical oxidation.

[0131] To measure mass loss, a coated sample, such as a coated glass container, is first heated to 150° C. and maintained at this temperature for 30 minutes to dry the coating and completely evaporate H2O from the coating. The sample is then heated from 150° C. to 350° C. at a heating rate of 10° C. / min in an oxidizing environment, such as air. For the purpose of measuring mass loss, only data collected between 150° C. and 350° C. are considered. In some embodiments, the smooth coating has a mass loss of less than about 5% of its mass when heated to a temperature of 150° C. to 350° C. at a heating rate of about 10° C. / min. In other embodiments, the smooth coating has a mass loss of less than about 3%, or even less than about 2%, when heated to a temperature of 150° C. to 350° C. at a heating rate of about 10° C. / min. In some other embodiments, the smooth coating has a mass loss of less than about 1.5% when heated to a temperature of 150° C. to 350° C. at a heating rate of about 10° C. / min. In some other embodiments, the smooth coating has a mass loss of less than about 0.75% when heated at a heating rate of about 10° C. / min to a temperature of 150° C. to 350° C. In some other embodiments, the smooth coating loses substantially no mass when heated at a heating rate of about 10° C. / min to a temperature of 150° C. to 350° C.

[0132] The mass loss results are based on a technique of comparing the weight of the coated glass container before and after a heat treatment, such as a 10° / min ramp from 150° C. to 350° C., as described herein. By comparing the pre-heat treatment weight of the coating (weight after the pre-heat step, not including the glass body of the container) with the weight of the uncoated glass container and the weight of the coated glass container before treatment, the difference in weight between the vial before and after heat treatment is the weight loss of the coating, which can be normalized as a percentage weight loss of the coating. Alternatively, the total mass of the coating can be determined by a total organic carbon test or other similar means.

[0133] Referring now to FIG. 10, outgassing refers to a measurable characteristic of a coated glass container 100 that relates to the amount of volatiles liberated from the coated glass container 100 when the coated glass container is exposed to a selected elevated temperature for a selected time. Outgassing measurements are reported herein as the amount of volatiles liberated by weight per surface area of ​​the coated glass container during a given time of exposure to an elevated temperature. Since the glass body of the coated glass container does not measurably exhibit outgassing at the temperatures reported for outgassing, the outgassing tests, as detailed above, provide outgassing data substantially only for smooth coatings applied to the glass container. The outgassing results are based on the manner in which the coated glass container 100 is placed in the glass sample chamber 402 of the apparatus 400 illustrated in FIG. 10. A background sample of an empty sample chamber is collected prior to each sample test. The sample chamber is held under a constant air purge of 100 ml / min as measured by a rotometer 406 while the furnace 404 is heated to 350° C. and held at that temperature for 1 hour to collect a background sample of the chamber. The coated glass vessel 100 is then placed in the sample chamber 402 and the sample chamber is held under a constant air purge of 100 ml / min and heated to an elevated temperature and held at that temperature for a period of time to collect a sample from the coated glass vessel 100. The glass sample chamber 402 is made of “Pyrex” and is limited to a maximum analytical temperature of 600° C. A Carbotrap 300 sorbent trap 408 is constructed at the sample chamber exhaust port to adsorb volatile species released from the sample and carried by blowing the air purge gas 410 through an absorbent resin for volatile species adsorption. The absorbent resin is then placed directly into a Gerstel Thermal Desorption unit which is directly coupled to a Hewlett Packard 5890 Series II Gas Chromatography / Hewlett Packard 5989 MS engine.The outgassed species are thermally desorbed from the sorbent resin at 350 °C and cryogenically collected at the head of a non-polar gas chromatography column (DB-5MS). The temperature during gas chromatography is increased at a rate of 10 °C / min to a final temperature of 325 °C to achieve separation and purification of the volatile and semi-volatile organic species. The separation mechanism is demonstrated as being based on the heat of vaporization of the different organic species resulting in a substantially boiling point or distillation chromatogram. After separation, the purified species are analyzed by conventional electron impact ionization mass spectrometry protocols. Operating under standard conditions, the resulting mass spectra can be compared to existing mass spectral libraries.

[0134] In some embodiments, the coated glass containers described herein exhibit outgassing of about 54.6 ng / cm2 or less, about 27.3 ng / cm2 or less, or even about 5.5 ng / cm2 or less during exposure to high temperatures of about 250°C, about 275°C, about 300°C, about 320°C, about 360°C, or even about 400°C for about 15 minutes, about 30 minutes, about 45 minutes, or about 1 hour. Furthermore, the coated glass containers may be thermally stable in a certain temperature range, meaning that the coated containers exhibit a constant outgassing as described above at all temperatures in the certain range. Prior to the outgassing measurement, the coated glass containers may be in a bare coating state (i.e., immediately after application of the smooth coating) or after any one of depyrogenation, lyophilization, or autoclaving. In some embodiments, the coated glass containers 100 may exhibit substantially no outgassing.

[0135] In some embodiments, the outgassing data can be used to measure the mass loss rate of the smooth coating. The pre-heat treatment coating mass can be measured by the thickness of the coating (measured by SEM image or other modality), the density of the smooth coating, and the surface area of ​​the coating. The coated glass container can then be subjected to the outgassing process, and the mass loss rate can be measured by finding the ratio of the mass released in the outgassing to the mass before the heat treatment.

[0136] The coated glass container described herein has a four-point bending strength. To measure the four-point bending strength of the glass container, a glass tube, which is a precursor of the coated glass container 100, is used for the measurement. The glass tube has the same diameter as the glass container, but does not have a glass container bottom or a glass container mouth (i.e., before forming the glass container from the tube). The glass tube is then subjected to a four-point bending stress test to induce mechanical failure. The test is performed at a relative humidity of 50%, with the outer contact members spaced 9 inches (22.86 centimeters) apart and the inner contact members spaced 3 inches (7.62 centimeters) apart, and a loading rate of 10 mm / min.

[0137] Four-point bending stress measurements can also be performed on coated and scratched tubes. As described in the measurement of horizontal compressive strength of scratched vials, the test fixture 300 can be operated to form abrasions on the tube surface, such as surface scratches that reduce the strength of the tube. The glass tube is then subjected to a four-point bending stress test to induce mechanical failure. The test is performed at 25° C. and 50% relative humidity, using outer probes spaced 9 inches (22.86 centimeters) apart and inner contact members spaced 3 inches (7.62 centimeters) apart, with a loading rate of 10 mm / min, while the tube is positioned under tension to form scratches during the test.

[0138] In some embodiments, the four-point bend strength of a glass tube with a smooth coating after scratching exhibits, on average, at least 10%, 20%, or even 50% greater mechanical strength than that for an uncoated glass tube scratched under the same conditions.

[0139] Referring to FIG. 11, the clarity and color of the coated container can be evaluated by measuring the light transmittance of the container with a spectrophotometer at a series of wavelengths from 400 to 700 nm. Measurements are made by directing a light beam at the container perpendicular to the wall of the container such that the light beam passes through the smooth coating twice, once at the entrance to the container and once at the exit. In some embodiments, the light transmittance of the coated glass container can be about 55% or greater than the light transmittance of the uncoated glass container for wavelengths from about 400 nm to about 700 nm. As described herein, the light transmittance can be measured before or after a heat treatment, such as the heat treatments described herein. For example, for each wavelength from about 400 nm to about 700 nm, the light transmittance can be about 55% or greater than the light transmittance of the uncoated glass container. In other embodiments, the light transmittance of the coated glass container is greater than or equal to about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or even about 90% of the light transmittance of the uncoated glass container for wavelengths between about 400 nm and about 700 nm.

[0140] As described herein, the light transmittance can be measured before or after an environmental treatment, such as a heat treatment, as described herein. For example, after heat treatment at about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, or about 400°C for 30 minutes, or after exposure to freeze-drying conditions, or after exposure to autoclave conditions, the light transmittance of the coated glass container is at least about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or even about 90% of the light transmittance of the uncoated glass container for wavelengths from about 400 nm to about 700 nm.

[0141] In some embodiments, the coated glass container 100 may be perceived as colorless and transparent to the naked human eye when viewed from all angles. In some other embodiments, the smooth coating 160 may have a perceptible tint, such as when the smooth coating 160 comprises a polyimide formed from poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amic acid, commercially available from Aldrich.

[0142] In some embodiments, the glass container 100 having the smooth coating 160 may have an exterior surface to which an adhesive label can be attached. In other words, the smooth coating 160 has a low coefficient of friction, but the coating is capable of receiving an adhesive label such that the adhesive label can be securely attached. However, the ability to receive an adhesive label is not required for all embodiments of the glass container 100 having the smooth coating 160 described herein.

[0143] Referring again to Figure 8, in some embodiments, the smooth coating 160 may be a temporary coating. As used herein, the phrase "temporary coating" means that the coating is not permanently adhered to the glass container 100, but rather may be removed from the glass container 100, such as by washing, heating (i.e., pyrolysis), and the like. For example, in embodiments in which the smooth coating 160 is a temporary coating that may be removed by pyrolysis, the coating may be pyrolyzed at a temperature of about 300°C or less. Alternatively, the smooth coating 160 may be a temporary coating that may be removed by washing the glass container with a solution of detergent and water.

[0144] In the embodiments described herein, the glass container may be coated with an inorganic coating, a temporary organic coating, and / or a robust organic coating to achieve the desired low coefficient of friction and resistance to damage. Inorganic Coating With further reference to FIG. 8, in some embodiments described herein, the smooth coating 160 is an inorganic coating. The inorganic coating can be a robust inorganic coating permanently adhered to the exterior surface 106 of the glass container body 102. The properties of the robust inorganic coating are not degraded by exposure to high temperatures, and thus the coefficient of friction and horizontal compressive strength of the glass container having the robust inorganic coating are substantially the same before and after exposure to high temperatures, including, but not limited to, temperatures in the range of about 250° C. to about 400° C. The robust inorganic coating is a continuous coating applied to at least a portion of the exterior surface of the body, and is generally insoluble in water and / or organic solvents. For example, in some embodiments, the robust inorganic coating can include a metal nitride coating, a metal sulfide coating, a metal oxide coating, SiO2, diamond-like carbon, or a carbide coating. For example, the robust inorganic coating may include at least one of tin, BN, hBN, TiO2, Ta2O5, HfO2, Nb2O5, VO5, SnO, SnO2, ZrO2, Al2O3, SiO2, ZnO, MoS2, BC, SiC, or similar metal oxide, metal nitride, and carbide coatings that exhibit a relatively low coefficient of friction and have relatively high thermal stability compared to similar coated glass containers. In these embodiments, the coating may be applied to the exterior surface of the glass container by physical vapor deposition techniques such as evaporation, electron beam evaporation, dc magnetron sputtering, unbalanced dc magnetron sputtering, ac magnetron sputtering, and unbalanced ac magnetron sputtering. Alternatively, the coating may be applied by powder coating. Chemical vapor deposition (CVD) techniques may also be used to apply the coatings, including ultra-high vacuum CVD, low pressure CVD, atmospheric pressure CVD, metal-organic CVD, laser CVD, photochemical CVD, aerosol assisted CVD, microwave plasma assisted CVD, plasma assisted CVD, direct liquid injection CVD, atomic layer CVD, combustion CVD, hot wire CVD, rapid thermal CVD, chemical vapor infiltration, and chemical beam epitaxy.

[0145] In a particular embodiment, the robust inorganic coating is diamond-like carbon. Films or coatings formed from diamond-like carbon generally exhibit low coefficients of friction and high hardness. Specifically, a significant amount of carbon in DLC coatings is SP3 hybridized carbon. This material imparts certain properties of diamond to these coatings, such as high hardness and excellent wear resistance. The hardness of DLC coatings is directly proportional to the content of SP3 hybridized inclusions. DLC coatings can be deposited on the exterior surface of glass containers by ion beam deposition, cathodic arc spraying, pulsed laser ablation, argon ion sputtering and plasma-assisted chemical vapor deposition. Depending on the thickness of the deposited DLC coating, the particular deposition method, and the composition of the coating, the color of the deposited layer can vary from optically transparent yellow (i.e., a 0.1 μm thick DLC film can be optically transparent with a slight yellow tint) to amber and black.

[0146] Alternatively, the smoothing coating 160 can be an inorganic coating that is temporarily affixed to the exterior surface of the glass container, such as a temporary coating. In these embodiments, the temporary coating can include inorganic salts such as MgSO4, CaSO4, Ca3(PO4)2, Mg3(PO4)2, KNO3, K3PO4, and the like. Organic Coating In some alternative embodiments, the smooth coating 160 may be an organic coating that is temporarily affixed to the exterior surface of the glass container, such as a temporary coating, or may be a durable organic coating that is permanently affixed to the exterior surface of the glass container.

[0147] For organic temporary coatings, it is desirable to protect the surface of glass articles (such as glass containers, etc.) from damage during manufacturing, to reduce the loss of mechanical strength of glass due to surface defects caused by contact with glass. This is generally achieved by applying a coating with a low coefficient of friction, as described above. However, since the glass container may be subjected to further processing, it is not necessary for the coating to be permanently adhered to the outer surface of the glass container, and instead, it may be removed in a downstream processing step after the coating has served its purpose of protecting the glass article. For example, the temporary coating may be removed by pyrolysis. In the embodiments described herein, the temporary coating may be pyrolyzed at a temperature of 300° C. or less for a time of 1 hour or less. Alternatively, the temporary coating may be pyrolyzed at a temperature of 265° C. for 2.5 hours, or even at a temperature of 360° C. for 10 minutes or less.

[0148] A variety of organic materials can be utilized to form the temporary coating. For example, in some embodiments, the temporary coating can include a mixture of polyoxyethylene glycol, methacrylate resin, melamine formaldehyde resin, and polyvinyl alcohol, as disclosed in U.S. Pat. No. 3,577,256. Such coatings can be applied to the exterior surface of a molded glass container and pyrolyzed from the glass surface in an annealing lehr.

[0149] In other embodiments, the temporary organic coating may include one or more polysaccharides, as disclosed in U.S. Patent No. 6,715,316 B2, which describes a removable protective coating. Such coatings are removable from the glass surface using a mild aqueous cleaner, such as 2% Semiclean KG in water.

[0150] In other embodiments, the temporary organic coating can be a "cold end" coating as described in U.S. Patent No. 4,055,441 or a similar coating. Such coatings include poly(ethylene oxide), poly(propylene oxide), ethylene oxide-propylene oxide copolymers, polyvinyl-pyrrolidinone, polyethyleneamines, poly(methyl vinyl ether), polyacrylamides, polymethacrylamides, polyurethanes, poly(vinyl acetate), polyvinyl formal, polyformaldehyde including polyacetals and acetal copolymers, poly(alkyl methacrylates), methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose, methyl hydroxypropyl cellulose, poly(acrylic acid) and its salts, poly(methacrylic acid) and its salts, ethylene-maleic anhydride copolymers, ethylene -vinyl alcohol copolymers, ethylene-acrylic acid copolymers, vinyl acetate-vinyl alcohol copolymers, methyl vinyl ether-maleic anhydride copolymers, emulsifying polyurethanes, polyoxyethylene stearate, and polyolefins including polyethylene, polypropylene and their copolymers, starch and modified starches, hydrocolloids, polyacrylamide, vegetable and animal fats, waxes, tallow, soaps, stearin-paraffin emulsions, dimethyl or diphenyl or mixed methyl / phenyl polysiloxanes, perfluorinated siloxanes and other substituted siloxanes, alkyl silanes, aromatic silanes, and oxidized polyethylene and combinations thereof or similar coatings.

[0151] A temporary organic coating can be applied by directly contacting such a coating to the glass container. For example, the coating can be applied by a dipping process or by spraying or other suitable means. The coating can then be dried and, optionally, cured at elevated temperatures.

[0152] 8 and 12A, in some embodiments, the smooth coating 160 is a robust organic coating adhered to at least a portion of the exterior surface 106 of the glass body 102. The robust organic coating has a low coefficient of friction and is also thermally stable at high temperatures, as described above. The smooth coating 160 has an exterior surface 162 and a glass-contacting surface 164. In embodiments in which the smooth coating 160 is a robust organic coating, the smooth coating 160 may include a coupling agent layer 180 in direct contact with the exterior surface 106 of the glass body 102 and a polymer layer 170 in direct contact with the coupling agent layer 180. However, it should be understood that in some embodiments, the smooth coating 160 may not include the coupling agent layer 180, and the polymer layer 170 may be in direct contact with the exterior surface 106 of the glass body 102. In some embodiments, the smooth coating 160 is a coating layer described in U.S. Provisional Patent Application No. 13 / 780,754, filed February 28, 2013, entitled "Glass Articles with Low Friction Coatings," which is incorporated by reference in its entirety herein.

[0153] 8 and 12A, in one embodiment, the smooth coating 160 comprises a two-layer structure. FIG. 12A shows a cross-section of a portion of a coated glass container, where the smooth coating 160 includes a polymer layer 170 and a coupling agent layer 180. The polymer chemical composition may be contained in the polymer layer 170 and the coupling agent may be contained in the coupling agent layer 180. The coupling agent layer 180 may be in direct contact with the outer surface 106 of the glass body 102. The polymer layer 170 may be in direct contact with the coupling agent layer 180 and may form the outer surface 162 of the smooth coating 160. In some embodiments, the coupling agent layer 180 is adhered to the outer surface 106 of the glass body 102, and the polymer layer 170 is adhered to the coupling agent layer 180 at an interface 174. However, it should be understood that in some embodiments, the smooth coating 160 may be free of a coupling agent and the polymer chemical composition may be present in the polymer layer 170 that is in direct contact with the outer surface 106 of the glass body 102. In other embodiments, the polymer chemical composition and the coupling agent may be substantially mixed in a single layer. In some other embodiments, the polymer layer 170 may be located on top of the coupling agent layer 180, meaning that the polymer layer 170 is an outer layer relative to the coupling agent layer 180 and the outer surface 106 of the glass body 102. As used herein, a first layer located "on top" of a second layer means that the first layer can be in direct contact with the second layer or can be separate from the second layer, such as with a third layer disposed between the first and second layers.

[0154] 12B, in one embodiment, the smooth coating 160 may further include an interfacial layer 190 located between the coupling agent layer 180 and the polymer layer 170. The interfacial layer 190 may include one or more chemical compositions of the polymer layer 170 combined with one or more chemical compositions of the coupling agent layer 180. In this embodiment, the interface between the coupling agent layer 180 and the polymer layer 170 forms the interfacial layer 190, where a bond occurs between the polymer chemical composition and the coupling agent. However, it should be understood that in some embodiments, as described above with reference to FIG. 12A, there may be no layer corresponding to the interface between the coupling agent layer 180 and the polymer layer 170, in which case the polymer and the coupling agent are chemically bonded to each other.

[0155] In other embodiments, the polymer chemical composition and the coupling agent may be substantially mixed in a single layer to form a homogenous layer of the smooth coating. Such a mixed single layer may be in direct contact with the exterior surface 106 of the glass body 102. As described herein, the materials of the polymer layer 170 and the coupling agent layer 180 (i.e., at least the polymer and at least the coupling agent, respectively) may be mixed to form at least one layer of the smooth coating 160. The mixed layer smooth coating 160 may further include materials other than the polymer chemical composition and the coupling agent. To form the mixed layer smooth coating 160, the various materials of such layers may be mixed together in a solution prior to application of the smooth coating 160 to the glass container 100. In other embodiments, the mixed layer may be above or below a non-mixed layer, such as, for example, a mixed layer of polymer and coupling agent below a layer consisting essentially of only polymer material. In other embodiments, the smooth coating may include three or more layers, such as three or four layers.

[0156] The smooth coating 160 applied to the exterior surface 106 of the glass body 102 may have a thickness of less than about 100 μm, or even less than about 1 μm. In some embodiments, the thickness of the smooth coating 160 may be less than about 100 nm thick. In other embodiments, the smooth coating 160 may be less than about 90 nm thick, less than about 80 nm thick, less than about 70 nm thick, less than about 60 nm thick, less than about 50 nm, or even less than about 25 nm thick. In some embodiments, the smooth coating 160 may not have a uniform thickness over the entire surface of the glass body 102. For example, the coated glass container 100 may have a thicker smooth coating 160 in certain areas due to the process of contacting the exterior surface 106 of the glass body 102 with one or more coating solutions that form the smooth coating 160. In some embodiments, the smooth coating 160 may have a non-uniform thickness. For example, the thickness of the coating may vary over different areas of the coated glass container 100, which may facilitate protection in selected areas. In other embodiments, only selected portions of the exterior surface 106 of the glass body are coated with the smooth coating 160 .

[0157] In embodiments including at least two layers, such as polymer layer 170, interfacial layer 190 and / or coupling agent layer 180, each layer may have a thickness of less than about 100 μm, or even less than about 1 μm. In some embodiments, the thickness of each layer may be less than about 100 nm. In other embodiments, each layer may be less than about 90 nm thick, less than about 80 nm thick, less than about 70 nm thick, less than about 60 nm thick, less than about 50 nm thick, or even less than about 25 nm thick.

[0158] As described herein, in some embodiments, the smooth coating 160 includes a coupling agent. The coupling agent may improve the adhesion or bond of the polymeric chemical composition to the exterior surface 106 of the glass body 102, and is typically located between the glass body 102 and the polymeric chemical composition of the chemical composition layer 170 or is mixed therewith. As used herein, adhesion refers to the strength of adhesion or bond of the polymeric layer before and after a treatment applied to the coated glass container, such as a heat treatment. Heat treatments include, but are not limited to, autoclaving, depyrogenation, freeze drying, and the like.

[0159] In one embodiment, the coupling agent may include at least one silane chemical composition. As used herein, a "silane" chemical composition is any chemical composition that includes an organosilane functional group and a silane moiety that includes a silanol formed from the silane in aqueous solution. The silane chemical composition of the coupling agent may be aromatic or aliphatic. In some embodiments, the at least one silane chemical composition may include an amine moiety, such as a primary amine moiety or a secondary amine moiety. Additionally, the coupling agent may include hydrolyzates and / or oligomers of such silanes, such as one or more silsesquioxane chemical compositions formed from the one or more silane chemical compositions. The silsesquioxane chemical composition may include a full cage structure, a partial cage structure, or a non-cage structure.

[0160] The coupling agent may include any number of different chemical compositions, such as one chemical composition, two different chemical compositions, or more than two different chemical compositions, including oligomers formed from two or more monomeric chemical compositions. In one embodiment, the coupling agent may include at least one of (1) a first silane chemical composition, a hydrolyzate thereof or an oligomer thereof, and (2) a chemical composition formed from the oligomerization of at least a first silane chemical composition and a second silane chemical composition. In another embodiment, the coupling agent includes a first and a second silane. As used herein, a "first" silane chemical composition and a "second" silane chemical composition are silanes having different chemical compositions. The first silane chemical composition may be an aromatic or aliphatic chemical composition, may optionally include an amine moiety, and may optionally be an alkoxysilane. Similarly, the second silane chemical composition may be an aromatic or aliphatic chemical composition, may optionally include an amine moiety, and may optionally be an alkoxysilane.

[0161] For example, in one embodiment, only one silane chemical composition is applied as the coupling agent. In such an embodiment, the coupling agent may include the silane chemical composition, a hydrolysate thereof, or an oligomer thereof.

[0162] In other embodiments, multiple silane chemical compositions may be applied as the coupling agent. In such embodiments, the coupling agent may include at least one of: (1) a mixture of a first silane chemical composition and a second silane chemical composition; and (2) a chemical composition formed from the oligomerization of at least the first silane chemical composition and the second silane chemical composition.

[0163] With reference to the above embodiments, the first silane chemical composition, the second silane chemical composition, or both may be aromatic chemical compositions. As used herein, an aromatic chemical composition contains one or more six-membered carbon rings characteristic of benzene-based and related organic moieties. The aromatic silane chemical composition may be an alkoxysilane, such as, but not limited to, a dialkoxysilane chemical composition, a hydrolysate thereof, or an oligomer thereof, or a trialkoxysilane chemical composition, a hydrolysate thereof, or an oligomer thereof. In some embodiments, the aromatic silane may include an amine moiety, and may be an alkoxysilane that includes an amine moiety. In other embodiments, the aromatic silane chemical composition may be an aromatic alkoxysilane chemical composition, an aromatic acyloxysilane chemical composition, an aromatic halogen silane chemical composition, or an aromatic aminosilane chemical composition. In other embodiments, the aromatic silane chemical composition may be selected from the group consisting of aminophenyl, 3-(m-aminophenoxy)propyl, N-phenylaminopropyl, or (chloromethyl)phenyl substituted alkoxy, acyloxy, halogen, or aminosilane. For example, the aromatic alkoxysilane can be, but is not limited to, aminophenyltrimethoxysilane (sometimes referred to herein as "APhTMS"), aminophenyldimethoxysilane, aminophenyltriethoxysilane, aminophenyldiethoxysilane, 3-(m-aminophenoxy)propyltrimethoxysilane, 3-(m-aminophenoxy)propyldimethoxysilane, 3-(m-aminophenoxy)propyltriethoxysilane, 3-(m-aminophenoxy)propyldiethoxysilane, N-phenylaminopropyltrimethoxysilane, N-phenylaminopropyldimethoxysilane, N-phenylaminopropyltriethoxysilane, N-phenylaminopropyldiethoxysilane, hydrolyzates thereof, or oligomerized chemical compositions thereof. In an exemplary embodiment, the aromatic silane chemical composition can be aminophenyltrimethoxysilane.

[0164] Referring again to the above embodiment, the first silane chemical composition, the second silane chemical composition, or both may be aliphatic chemical compositions. As used herein, aliphatic chemical compositions are non-aromatic, such as chemical compositions with open-chain structures, including but not limited to alkanes, alkenes, and alkynes. For example, in some embodiments, the coupling agent may include chemical compositions such as alkoxysilanes, including but not limited to dialkoxysilane chemical compositions, aliphatic alkoxysilanes, such as hydrolysates thereof or oligomers thereof, or trialkoxysilane chemical compositions, such as hydrolysates thereof or oligomers thereof. In some embodiments, the aliphatic silane may include an amine moiety, such as an alkoxysilane including an amine moiety, such as an aminoalkyltrialkoxysilane. In one embodiment, the aliphatic silane chemical composition can be selected from the group consisting of 3-aminopropyl, N-(2-aminoethyl)-3-aminopropyl, vinyl, methyl, N-phenylaminopropyl, (N-phenylamino)methyl, N-(2-vinylbenzylaminoethyl)-3-aminopropyl substituted alkoxy, acyloxy, halogen, or aminosilanes, hydrolysates thereof, or oligomers thereof. Aminoalkyltrialkoxysilanes include, but are not limited to, 3-aminopropyltrimethoxysilane (sometimes referred to herein as "GAPS"), 3-aminopropyldimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyldiethoxysilane, hydrolyzates thereof, and oligomerized chemical compositions thereof. In other embodiments, the aliphatic alkoxysilane chemical composition may include an amine moiety, such as an alkyltrialkoxysilane or an alkylbialkoxysilane.Such alkyltrialkoxysilanes or alkylbialkoxysilanes include, but are not limited to, vinyltrimethoxysilane, vinyldimethoxysilane, vinyltriethoxysilane, vinyldiethoxysilane, methyltrimethoxysilane, methyldimethoxysilane, methyltriethoxysilane, methyldiethoxysilane, hydrolysates thereof, or oligomerized chemical compositions thereof, including, but not limited to, amino-functional silsesquioxane oligomers such as WSA-7011, WSA-9911, WSA-7021, WSAV-6511 from Gelest, etc. In an exemplary embodiment, the aliphatic silane chemical composition is 3-aminopropyltrimethoxysilane.

[0165] In other embodiments, coupling agent layer 180 may include species that are hydrolyzed analogs of aminoalkoxysilanes, such as, but not limited to, (3-aminopropyl) silanetriol, N-(2-aminoethyl)-3-aminopropyl-silanetriol, and / or mixtures thereof.

[0166] In other embodiments, coupling agent layer 180 may include species that are aminoalkylsilsesquioxanes. In one embodiment, coupling agent layer 180 includes aminopropylsilsesquioxane (APS) oligomers (commercially available as an aqueous solution from Gelest).

[0167] In other embodiments, coupling agent layer 180 can be an inorganic material, such as a metal and / or ceramic film. Non-limiting examples of suitable inorganic materials for use as coupling agent layer 180 include tin, titanium and / or oxides thereof.

[0168] It has been found that forming the coupling agent from a combination of different chemical compositions, particularly a combination of silane chemical compositions, can improve the thermal stability of the lubricant coating 160. For example, it has been found that a combination of aromatic and aliphatic silanes, such as those described above, can improve the thermal stability of the lubricant coating, resulting in a coating that retains its mechanical properties, such as coefficient of friction and adhesion performance, even after heat treatment at high temperatures. Thus, in one embodiment, the coupling agent comprises a combination of aromatic and aliphatic silanes. In these embodiments, the ratio of aliphatic silane to aromatic silane (aliphatic:aromatic) can be from about 1:3 to about 1:0.2. When the coupling agent comprises two or more chemical compositions, such as at least an aliphatic silane and an aromatic silane, the weight ratio of the two chemical compositions can be any ratio, such as a weight ratio of the first silane chemical composition to the second silane chemical composition (first silane:second silane) of from about 0.1:1 to about 10:1. For example, in some embodiments, the ratio can be from 0.5:1 to about 2:1, such as 2:1, 1:1, 0.5:1, etc. In some embodiments, the coupling agent can include a combination of aliphatic silanes and / or aromatic silanes, which can be applied to the glass container in one or more steps, with or without organic or inorganic fillers. In some embodiments, the coupling agent includes oligomers, such as silsesquioxanes, formed from both aliphatic and aromatic silanes.

[0169] In an exemplary embodiment, the first silane chemical composition is an aromatic silane chemical composition and the second silane chemical composition is an aliphatic silane chemical composition. In one exemplary embodiment, the first silane chemical composition is an aromatic alkoxysilane chemical composition comprising at least one amine moiety and the second silane chemical composition is an aliphatic alkoxysilane chemical composition comprising at least one amine moiety. In another exemplary embodiment, the coupling agent comprises an oligomer of one or more silane chemical compositions, the oligomer being a silsesquioxane chemical composition, and at least one of the silane chemical compositions comprises at least one aromatic moiety and at least one amine moiety. In one particular exemplary embodiment, the first silane chemical composition is aminophenyltrimethoxysilane and the second silane chemical composition is 3-aminopropyltrimethoxysilane. The ratio of aromatic silane to aliphatic silane can be about 1:1. In another particular exemplary embodiment, the coupling agent comprises an oligomer formed from aminophenyltrimethoxy and 3-aminopropyltrimethoxy. In other embodiments, the coupling agent may include both a mixture of aminophenyltrimethoxy and 3-aminopropyltrimethoxy, as well as oligomers formed from the two.

[0170] In one embodiment, the coupling agent is applied to the exterior surface 106 of the glass body 102 by contacting the surface with the diluted coupling agent by a dipping process. The coupling agent may be mixed into a solvent as it is applied to the glass body 102. In other embodiments, the coupling agent may be applied to the glass body 102 by spraying or other suitable means. The glass body 102 with the coupling agent applied may then be dried at about 120° C. for about 15 minutes, or any time and temperature sufficient to adequately liberate water and / or other organic solvents present on the exterior surface 106 of the wall portion 110.

[0171] 12A, in one embodiment, the coupling agent is placed in a glass container as coupling agent layer 180 and applied as a solution including about 0.5% by weight of a first silane and about 0.5% by weight of a second silane (total of 1% by weight silane) mixed with at least one of an organic solvent, such as, but not limited to, methanol and water. However, it should be understood that the total silane concentration in the solution can be greater than or less than about 1% by weight, such as about 0.1% to about 10% by weight, about 0.3% to about 5.0% by weight, or about 0.5% to about 2.0% by weight. For example, in one embodiment, the weight ratio of organic solvent to water (organic solvent:water) can be about 90:10 to about 10:90, and in one embodiment, about 75:25. The weight ratio of silane to solvent can affect the thickness of the coupling agent layer, where a greater proportion of the silane chemical composition in the coupling agent solution can result in a greater thickness of coupling agent layer 180. However, it should be understood that other variables, such as, but not limited to, the details of the dip coating process, such as the withdrawal speed from the bath, can affect the thickness of the coupling agent layer 180. For example, a faster withdrawal speed can result in a thicker coupling agent layer 180 being formed.

[0172] In one embodiment, the coupling agent layer 180 is applied as a solution including a first silane species and a second silane species that may enhance the thermal stability and / or mechanical properties of the smooth coating 160. For example, the first silane species may be an aliphatic silane such as GAPS, and the second silane species may be an aromatic silane such as APhTMS. In this example, the ratio of aliphatic silane to aromatic silane (aliphatic:aromatic) may be about 1:1. However, as noted above, it should be understood that other ratios are possible, including from about 1:3 to about 1:0.2. The aromatic and aliphatic silane species may be mixed with at least one of an organic solvent, such as, but not limited to, methanol, and water. The solution is then coated onto the exterior surface 106 of the glass body 102 and cured to form the coupling agent layer 180.

[0173] In another embodiment, coupling agent layer 180 is applied as a solution containing 0.1 vol% of a commercially available aminopropyl silsesquioxane oligomer. Other concentrations of coupling agent layer solutions may be used, including, but not limited to, 0.01 to 10.0 vol% aminopropyl silsesquioxane oligomer solutions.

[0174] In some embodiments, coupling agent layer 180 is sufficiently thermally stable such that coupling agent layer 180 can act alone as smooth coating 160 without any additional coatings, such as chemical composition layer 170, etc. Thus, in these embodiments, it should be understood that smooth coating 160 comprises a single composition, specifically a coupling agent.

[0175] As described herein, when the smooth coating 160 is a robust organic coating, the coating may also include a polymeric chemical composition as a polymeric chemical composition layer 170. The polymeric chemical composition may include, but is not limited to, polyimides, polybenzimidazoles, polysulfones, polyetheretherketones, polyetherimides, polyamides, polyphenylenes, polybenzothiazoles, polyisocyanates ... Polybenzoxazole The polymeric chemical composition may be a thermally stable polymer or a mixture of polymers, such as polybisthiazoles and polyaromatic heterocyclic polymers. The polymeric chemical composition may be formed from other thermally stable polymers, such as polymers that do not degrade at temperatures in the range of 200° C. to 400° C., including 250° C., 300° C., and 350° C. These polymers may be applied with or without a coupling agent.

[0176] In one embodiment, the polymer chemical composition is a polyimide chemical composition. When the smooth coating 160 includes a polyimide, the polyimide composition may be derived from a polyamic acid formed in solution by polymerization of a monomer. One such polyamic acid is Novastrat® 800 (available from NeXolve). A curing step imidizes the polyamic acid to form a polyimide. A polyamic acid may be formed from the reaction of a diamine monomer, such as a diamine, with an anhydride monomer, such as a dianhydride. As used herein, polyimide monomers are described as diamine monomers and dianhydride monomers. However, while a diamine monomer contains two amine moieties, it should be understood that in the following description, any monomer containing at least two amine moieties may be suitable as a diamine monomer. Similarly, a dianhydride monomer contains two anhydride moieties, it should be understood that in the following description, any monomer containing at least two anhydride moieties may be suitable as a dianhydride monomer. A polyamic acid is formed by the reaction of the anhydride moiety of an anhydride monomer with the amine moiety of a diamine monomer. Thus, as used herein, a polyimide chemical composition formed from the polymerization of specific monomers refers to a polyimide formed after imidization of the polyamic acid formed from those specific monomers. In general, the molar ratio of the sum of the anhydride monomers to the diamine monomers may be about 1:1. Although a polyimide may be formed from only two different chemical compositions (one anhydride monomer and one diamine monomer), at least one anhydride monomer may be polymerized and at least one diamine monomer may be polymerized from the polyimide. For example, one anhydride monomer may be polymerized with two different diamine monomers. Any number of combinations of monomer types may be used.Additionally, the ratio of one anhydride monomer to a different anhydride monomer or the ratio of one or more diamine monomers to a different diamine monomer can be any ratio, such as about 1:0.1 to 0.1:1, such as about 1:9, 1:4, 3:7, 2:3, 1:1, 3:2, 7:3, 4:1, or 9:1.

[0177] The anhydride monomer with which the polyimide is formed with the diamine monomer may include any anhydride monomer. In one embodiment, the anhydride monomer includes a benzophenone structure. In an exemplary embodiment, benzophenone-3,3',4,4'-tetracarboxylic dianhydride may be at least one of the anhydride monomers from which the polyimide is formed. In other embodiments, the diamine monomer may have an anthracene structure, a phenanthrene structure, a pyrene structure, or a pentacene structure, including substituted versions of the above dianhydrides.

[0178] The diamine monomer with which the polyimide is formed with the anhydride monomer may include any diamine monomer. In one embodiment, the diamine monomer includes at least one aromatic ring moiety. Figures 13 and 14 show examples of diamine monomers that may form polyimide containing polymer chemical compositions with one or more selected anhydride monomers. The diamine monomer may have one or more carbon molecules connecting two aromatic ring moieties as shown in Figure 13, where R corresponds to an alkyl moiety containing one or more carbon atoms. Alternatively, the diamine monomer may have two aromatic ring moieties that are directly bonded and are not separated by at least one carbon molecule as shown in Figure 14. The diamine monomer may have one or more alkyl moieties, represented by R' and R'' in Figures 13 and 14. For example, in Figures 13 and 14, R' and R'' may represent alkyl moieties bonded to one or more aromatic ring moieties, such as methyl, ethyl, propyl, or butyl moieties. For example, a diamine monomer may have two aromatic ring moieties, each having an alkyl moiety attached thereto and an adjacent amine moiety attached to the aromatic ring moiety. It should be understood that R' and R" in both Figures 13 and 14 may be the same chemical moiety or different chemical moieties. Alternatively, R' and / or R" in both Figures 13 and 14 may not represent an atom.

[0179] Two different chemical compositions of diamine monomers may be formed from the polyimide. In one embodiment, the first diamine monomer includes two aromatic ring moieties that are directly bonded and not separated by a connecting carbon molecule, and the second diamine monomer includes two aromatic ring moieties that are connected with at least one carbon molecule connecting the two aromatic ring moieties. In an exemplary embodiment, the first diamine monomer, the second diamine monomer, and the anhydride monomer have a molar ratio (first diamine monomer:second diamine monomer:anhydride monomer) of about 0.465:0.035:0.5. However, the ratio of the first diamine monomer to the second diamine monomer may vary within a range of about 0.01:0.49 to about 0.40:0.10, while the anhydride monomer ratio is held at about 0.5.

[0180] In one embodiment, the polyimide composition is formed from the polymerization of at least a first diamine monomer, a second diamine monomer, and an anhydride monomer, the first and second diamine monomers being of different chemical composition. In one embodiment, the anhydride monomer is benzophenone, the first diamine monomer comprises two aromatic rings directly bonded, and the second diamine monomer comprises two aromatic rings bonded with at least one carbon molecule connecting the first and second aromatic rings. The first diamine monomer, the second diamine monomer, and the anhydride monomer may have a molar ratio (first diamine monomer:second diamine monomer:anhydride monomer) of about 0.465:0.035:0.5.

[0181] In an exemplary embodiment, the first diamine monomer is orthotolidone, the second diamine monomer is 4,4'-methylene-bis(2-methylaniline) and the anhydride monomer is benzophenone-3,3',4,4'-tetracarboxylic dianhydride. The first diamine monomer, second diamine monomer and anhydride monomer may have a molar ratio of about 0.465:0.035:0.5 (first diamine monomer:second diamine monomer:anhydride monomer).

[0182] In some embodiments, the polyimide is selected from the group consisting of: bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxyl 1,2;3,4-dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride, 4arH,8acH)-decahydro-1t,4t:5c,8c-dimethanonaphthalene-2t,3t,6c,7c-tetracarboxyl 2,3:6,7-dianhydride, 2c,3c,6c,7c-tetracarboxyl 2,3:6,7-dianhydride, 5 -endo-Carboxymethylbicyclo[2.2.1]heptane-2-exo, 3-exo, 5-exo-tricarboxylic acid 2,3:5,5-dianhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, isomers of bis(aminoethyl)bicyclo[2.2.1]heptane, or 4,4'-methylenebis(2-methylcyclohexylamine), pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyl dianhydride (4,4'-BPDA), 3,3',4,4'-biphenyl dianhydride (3,3',4,4'-biphenyl dianhydride), 3,3',4,4'-biphenyl dianhydride (3,3',4,4'-biphenyl dianhydride), 3,3',4,4'-biphenyl dianhydride (3,3',4,4'-biphenyl dianhydride), 3,3',4,4'-biphenyl dianhydride (3,3',4,4'-biphenyl dianhydride), 3,3',4,4'-biphenyl dianhydride, ... '-Benzophenone dianhydride (4,4'-BTDA), 3,3',4,4'-oxydiphthalic anhydride (4,4'-ODPA), 1,4-bis(3,4-dicarboxyl-phenoxy)benzene dianhydride (4,4'-HQDPA), 1,3-bis(2,3-dicarboxyl-phenoxy)benzene dianhydride (3,3'-HQDPA), 4,4'-bis(3,4-dicarboxylphenoxyphenyl)-isopropylidene dianhydride (4,4'-BPADA), 4,4'-(2,2,2-trifluoro-1-pentafluorophenylethylidene ) diphthalic dianhydride (3FDA), 4,4'-oxydianiline (ODA), m-phenylenediamine (MPD), p-phenylenediamine (PPD), m-toluenediamine (TDA), 1,4-bis(4-aminophenoxy)benzene (1,4,4-APB), 3,3'-(m-phenylenebis(oxy))dianiline (APB), 4,4'-diamino-3,3'-dimethyldiphenylmethane (DMMDA), 2,2'-bis(4-(4-aminophenoxy)phenyl)propane (BAPP), 1,4-cyclohexanediamine 2,2'-Bis[4-(4-amino-phenoxy)phenyl]hexafluoroisopropylidene (4-BDAF), 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane (DAPI), maleic anhydride (MA), citraconic anhydride (CA), nadic anhydride (NA), 4-(phenylethynyl)-1,2-benzenedicarboxylic anhydride (PEPA), 4,4'-diaminobenzanilide 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA), pyromellitic dianhydride, benzophenone-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, 4,4'-o 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-(4,4'-isopropylidenediphenoxy)bis(phthalic anhydride), 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, and the compounds described in U.S. Pat. Nos. 7,619,042, 8,053,492, and 6,113,741. The polyimide coating may be formed from the polymerization of one or more of the materials described in U.S. Pat. Nos. 4,880,895, 6,232,428, 4,595,548, WO 2007 / 016516, U.S. Pat. App. Pub. No. 2008 / 0214777, 6,444,783, 6,277,950, and 4,680,373. FIG. 15 depicts the chemical structures of some suitable monomers that may be used to form the polyimide coating applied to the glass body 102. In other embodiments, the polyamic acid solution from which the polyimide is formed may include poly(pyromellitic dianhydride-co-4,4'-oxydianiline) amic acid (commercially available from Aldrich).

[0183] In other embodiments, the polymer chemical composition may include a fluorinated polymer. The fluorinated polymer may be a copolymer in which both monomers are highly fluorinated. Some of the monomers of the fluorinated polymer may be fluoroethylene. In one embodiment, the polymer chemical composition includes an amorphous fluorinated polymer, such as, but not limited to, Teflon AF (commercially available from DuPont). In another embodiment, the polymer chemical composition includes perfluoroalkoxy (PFA) resin particles, such as, but not limited to, Teflon PFA TE-7224 (commercially available from DuPont).

[0184] In another embodiment, the polymeric chemical composition may include a silicone resin. The silicone resin may be represented by the general formula R n Si(X) m O y where R is a non-reactive substituent, typically methyl or phenyl, and X is OH or H. Without wishing to be bound by theory, it is believed that the curing of the resin occurs via a condensation reaction of Si-OH moieties with the formation of Si-O-Si bonds. The silicone resin may have at least one of four possible types of siloxane-functional monomer units, including M-resin, D-resin, T-resin, and Q-resin, where M-resin refers to a resin with the general formula RSiO, D-resin refers to a resin with the general formula RSiO, T-resin refers to a resin with the general formula RSiO, and Q-resin refers to a resin with the general formula SiO (fused quartz). In some embodiments, the resin is formed from D and T units (DT resin) or M and Q units (MQ resin). In other embodiments, other combinations (MDT, MTQ, QDT) are also used.

[0185] In one embodiment, the polymeric chemical composition includes a phenylmethyl silicone resin for its high thermal stability compared to methyl or phenyl silicone resins. The ratio of phenyl to methyl moieties in the silicone resin can vary in the polymeric chemical composition. In one embodiment, the ratio of phenyl to methyl is about 1.2. In another embodiment, the ratio of phenyl to methyl is about 0.84. In another embodiment, the ratio of phenyl to methyl moieties can be about 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.3, 1.4, or 1.5. In one embodiment, the silicone resin is DC255 (commercially available from Dow Corning). In another embodiment, the silicone resin is DC806A (commercially available from Dow Corning). In another embodiment, the polymeric chemical composition can include any of the DC series resins (commercially available from Dow Corning) and / or Hardsil Series AP and AR resins (commercially available from Gelest). The silicone resin can be used without or with a coupling agent.

[0186] In other embodiments, the polymeric chemical composition may include silsesquioxane-based polymers, such as, but not limited to, T-214 (commercially available from Honeywell), SST-3M01 (commercially available from Gelest), POSS Imiclear (commercially available from Hybrid Plastics), and FOX-25 (commercially available from Dow Corning). In one embodiment, the polymeric chemical composition may include silanol moieties.

[0187] 8 and 12A, the smooth coating 160 may be applied in a multi-step process, where the glass body 102 is contacted with a coupling agent solution to form a coupling agent layer 180 (as described above), dried, and then contacted with a polymer chemical composition solution, such as a polymer or polymer precursor solution, such as by a dipping process, or, alternatively, the polymer layer 170 may be applied by spraying or other suitable means, dried, and then cured at an elevated temperature. Alternatively, if the coupling agent layer 180 is not used, the polymer chemical composition of the polymer layer 170 may be applied directly to the exterior surface 106 of the glass body 102. In other embodiments, the polymer chemical composition and the coupling agent may be mixed in the smooth coating 160, and a solution including the polymer chemical composition and the coupling agent may be applied to the glass body 102 in a single coating step.

[0188] In one embodiment, the polymer chemical composition includes a polyimide, where a polyamic acid solution is applied onto the coupling agent layer 180. In other embodiments, polyamic acid derivatives may be used, such as, for example, polyamic acid salts, polyamic acid esters, and the like. For example, a suitable polyamic acid salt may include a polyamic acid salt formed from triethylamine. Other suitable salts may include salts formed by deprotonation of the carboxylic acid groups of the polyamic acid with a basic additive resulting in an ionic interaction between the resulting carboxylate group and its conjugate acid. The basic additive may include organic, inorganic, or organometallic species, or combinations thereof. The inorganic species may include moieties such as alkali, alkaline earth, or metal bases. The organic bases (proton acceptors) may include aliphatic amines, aromatic amines, or other organic bases. The aliphatic amines include primary amines, such as, but not limited to, ethylamine, secondary amines, such as, but not limited to, diethylamine, and tertiary amines, such as triethylamine. The aromatic amines include aniline, pyridine, and imidazole. The organometallic bases may include 2,2 dimethylpropyl magnesium chloride, or others. In one embodiment, the polyamic acid solution may include a mixture of 1 vol.% polyamic acid and 99 vol.% organic solvent. The organic solvent may include a mixture of toluene and at least one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF) and 1-methyl-2-pyrrolidinone (NMP) solvents or mixtures thereof. In one embodiment, the organic solvent solution includes about 85 vol.% of at least one of DMAc, DMF and NMP, and about 15 vol.% of toluene. However, other suitable organic solvents may be used. The coated glass container 100 may then be dried at about 150° C. for about 20 minutes, or any time and temperature sufficient to suitably liberate the organic solvent present in the smooth coating 160.

[0189] In the laminated temporary organic smooth coating embodiment, after the glass body 102 is contacted with the coupling agent to form the coupling agent layer 180 and with the polyamic acid solution to form the polymer layer 170, the coated glass container 100 may be subjected to curing at an elevated temperature. The coated glass container 100 may be cured at 300° C. for about 30 minutes or less, or may be cured at temperatures above 300° C. for a shorter period of time, such as at least 320° C., 340° C., 360° C., 380° C., or 400° C. It is believed that the curing step imidizes the polyamic acid in the polymer layer 170 by reaction of the carboxylic acid moiety with the amide moiety to form the polymer layer 170 including the polyimide. The curing step may also promote bonding between the polyimide and the coupling agent. The coated glass container 100 is then cooled to room temperature.

[0190] Further, without being bound by any limitation, it is believed that the curing step of the coupling agent, polymeric chemical composition, or both, drives off volatile materials such as water and other organic molecules. Thus, these volatile materials liberated during the curing step are not present when the article, when used as a container, is heat treated (such as for depyrogenation) or contacts materials such as pharmaceuticals in which it is packaged. It should be understood that the curing process described herein is a heat treatment similar or equivalent to processes in the pharmaceutical packaging industry, such as depyrogenation, or a separate heat treatment from the heat treatments described herein, such as the heat treatments used to define thermal stability as described herein.

[0191] In one embodiment, the coupling agent comprises a silane chemical composition, such as an alkoxysilane, which can improve the adhesion of the polymer chemical composition to the glass body. Without being bound by theory, it is believed that the alkoxysilane molecules are rapidly hydrolyzed in water to form isolated monomers, cyclic oligomers, and large intramolecular rings. In various embodiments, control of which species predominates can be determined by silane type, concentration, pH, temperature, storage conditions, and time. For example, aminopropyltrialkoxysilane (APS) can be stable at low concentrations in aqueous solution and can form trisilanol monomers and very low molecular weight oligomeric rings.

[0192] Without being bound by theory, it is believed that the reaction of one or more silane chemical compositions to a glass body may involve a number of steps. As shown in FIG. 17, in some embodiments, reactive silanol moieties may be formed after hydrolysis of the silane chemical composition, which may condense with other silanol moieties on the surface of the substrate, such as a glass body. After the first and second hydrolyzable moieties are hydrolyzed, a condensation reaction may be initiated. In some embodiments, the tendency toward self-condensation may be controlled by the use of fresh solutions, alcohol-based solvents, dilution, and careful selection of the pH range. For example, silanetriols are most stable at pH 3-6, but may rapidly condense at pH 7-9.3, producing silsesquioxanes by partial condensation of silanol monomers. As shown in FIG. 17, the silanol moieties of the formed species may form hydrogen bonds with silanol moieties on the substrate, and during the drying or curing step, covalent bonds may be formed with the substrate with the loss of water. For example, a moderate cure cycle (110° C. for 15 minutes) may leave silanol moieties in a free form which, along with any silane organofunctional groups, may bond with subsequent topcoats resulting in improved adhesion.

[0193] In some embodiments, one or more of the silane chemical compositions of the coupling agent may include an amine moiety. It is believed, without being bound by theory, that the amine moiety may act as a basic catalyst in hydrolysis and co-condensation polymerization to enhance the adsorption rate of silanes having amine moieties onto glass surfaces. This may also result in a high pH (9.0-10.0) in aqueous solutions, which conditions the glass surface and increases the density of surface silanol moieties. Strong interactions with water and protic solvents maintain the solubility and stability of silanes having amine moiety chemical compositions such as APS.

[0194] In an exemplary embodiment, the glass body may include an ion-exchanged glass and the coupling agent may be a silane. In some embodiments, the adhesion of the smooth coating to the ion-exchanged glass body may be stronger than the adhesion of the smooth coating to the non-ion-exchanged glass body. Without being bound by theory, it is believed that any of a number of aspects of the ion-exchanged glass may promote bonding and / or adhesion relative to non-ion-exchanged glass. First, the ion-exchanged glass may have high chemical / hydrolytic stability that may affect the stability of the coupling agent and / or adhesion to the glass surface. Non-ion-exchanged glasses typically have low hydrolytic stability, and under moist and / or high temperature conditions, alkali metals may migrate from the glass body to the interface between the glass surface and the coupling agent layer (if present), or even to the coupling agent layer, if present. If alkali metals migrate as described above, and there is a change in pH, hydrolysis of Si-O-Si bonds at the glass / coupling agent layer interface or in the coupling agent layer itself may weaken the coupling agent mechanical properties or its adhesion to the glass. Second, the ion-exchanged glass can be exposed to a strong oxidizer bath, such as a potassium nitrite bath, at high temperatures, such as 400° C. to 450° C., and upon removal, the organic chemical compositions on the surface of the glass are removed, making it particularly suitable for silane coupling agents without further cleaning. For example, non-ion-exchanged glass may need to be subjected to additional surface cleaning treatments, adding time and expense to the process.

[0195] In an exemplary embodiment, the coupling agent may include at least one silane containing an amine moiety, and the polymer chemical composition may include a polyimide chemical composition. Now, referring to FIG. 18, without being bound by theory, it is believed that this amine moiety interaction with the polyamic acid precursor of the polyimide proceeds by a stepwise process. As shown in FIG. 18, the first step is the formation of a polyamic acid salt between the carboxyl moiety and the amine moiety of the polyamic acid. The second step is the thermal conversion of the salt to an amide moiety. The third step is the further conversion of the amide moiety to an imide moiety with cleavage of the polymer amide bond. The result is a covalent imide bond of the shortened polymer chain (polyimide chain) to the amine moiety of the coupling agent, as shown in FIG. 18. EXAMPLES

[0196] Various embodiments of the glass container having improved properties are further illustrated by the following examples, which are illustrative and should not be construed as limiting the subject matter of the present disclosure. Example 1 Glass vials were formed from Type IB glass having the same composition as Table 2 of Example 2 above, and the glass composition identified as "Example E" in Table 1 of U.S. Patent Application Serial No. 13 / 660,394, filed October 25, 2012, entitled "Glass Compositions with Improved Chemical and Mechanical Durability," and assigned to Corning Incorporated (hereinafter the "reference glass composition"). The vials were washed with deionized water, blown dry with nitrogen, and dip coated with a 0.1% solution of APS (aminopropylsilsesquioxane). The APS coating was dried at 100° C. for 15 minutes in a convection oven. The vials were then immersed in a 0.1% solution of Novastrat® 800 polyamic acid in 15 / 85 toluene / DMF (dimethylformamide) solution or a 0.1% to 1% solution of poly(pyromellitic dianhydride-co-4,4'-oxydianiline) amido acid (PMDA-ODA (Poly(4,4'-oxydiphenylene-pyromellitimide))) in N-methyl-2-pyrrolidone (NMP). The coated vials were heated to 150°C and held for 20 minutes to evaporate the solvent. The coating was then cured by placing the coated vials in a preheated oven at 300°C for 30 minutes. After curing, the vials coated with the 0.1% solution of Novastrat® 800 had no visible color. However, the vials coated with the solution of poly(pyromellitic dianhydride-co-4,4'oxydianiline) were visually yellow in color due to the thickness of the coating. Both coatings exhibited low coefficients of friction in vial overlap contact tests. Example 2 Glass vials (as received / uncoated) and vials coated with a smooth coating made from Type IB glass vials made from the same composition as in Table 2 of Example 2 above were compared to evaluate the loss of mechanical strength due to scratching. The coated vials were first made by ion exchange strengthening the glass vials made from the reference glass composition. Ion exchange strengthening was performed at 450°C for 8 hours in a 100% KNO3 bath. The vials were then washed with deionized water, blown dry with nitrogen, and dip coated with a 0.1% solution of APS (aminopropylsilsesquioxane) in water. The APS coating was dried in a convection oven at 100°C for 15 minutes. The vials were then immersed in a 0.1% solution of Novastrat® 800 polyamic acid in a 15 / 85 toluene / DMF solution. The coated vials were heated to 150°C and held for 20 minutes to allow the solvent to evaporate. The coating was then cured for 30 minutes at 300° C. by placing the coated vial in a preheated oven. The coated vial was then immersed in deionized water at 70° C. for 1 hour and heated in air at 320° C. for 2 hours to simulate actual processing conditions.

[0197] Unscrewed vials formed from Type IB glass formed from the same composition as in Table 2 of Example 2 above, and unscrewed vials formed from the reference glass composition that was ion-exchange strengthened and coated were tested for fracture in a horizontal compression test (i.e., a plate was placed on top of the vial and a plate was placed on the bottom of the vial, and both plates were pressed together to measure the applied load at fracture with a load meter). FIG. 19 illustrates the fracture probability as a function of applied load in a horizontal compression test for vials formed from the reference glass composition, vials formed from the coated and scratched reference glass composition, vials formed from Type IB glass, and vials formed from the scratched Type IB glass. The fracture loads of the unscrewed vials are illustrated in a Weibull plot. The sample vials formed from Type IB glass and the unscrewed vials formed from the ion-exchange strengthened and coated glass were then placed in the vial stacking fixture of FIG. 9 to scrape and rub the vials together to measure the coefficient of friction between the vials. The load on the vials under test was applied by the UMT machine and varied between 24N and 44N. The applied load and the corresponding maximum friction coefficient are reported in the table included in FIG. 20. For the uncoated vials, the maximum friction coefficient varied between 0.54 and 0.71 (shown in FIG. 20 as vial samples "3&4" and "7&8", respectively), whereas for the coated vials, the maximum friction coefficient varied between 0.19 and 0.41 (shown in FIG. 20 as vial samples "15&16" and "12&14", respectively). The scratched vials were then tested in a horizontal compression test to evaluate the loss of mechanical strength relative to the unscratched vials. The fracture load applied to the unscratched vials is illustrated in the Weibull plot in FIG. 19.

[0198] As shown in Figure 19, the uncoated vial lost significant strength after scratching, while the coated vial lost relatively little strength after scratching. Based on these results, it is believed that to reduce the loss of strength after vial overlap scratching, the coefficient of friction between the vials should be less than 0.7 or 0.5, or even less than 0.45. Example 3 In this example, sets of glass tubes were tested in four-point bending to evaluate their respective strengths. A first set of tubes made from the reference glass composition was tested in four-point bending as received (uncoated and not ion-exchange tempered). A second set of tubes made from the reference glass composition was ion-exchange tempered in a 100% KNO3 bath at 450°C for 8 hours and then tested in four-point bending. A third set of tubes made from the reference glass composition was ion-exchange tempered in a 100% KNO3 bath at 450°C for 8 hours and coated with 0.1% APS / 0.1% Novastrat® 800 as described in Example 2 and then tested in four-point bending. The coated tubes were also soaked in 70°C deionized water for 1 hour and heated in air at 320°C for 2 hours to simulate actual processing conditions. The coated tubes were also scraped in a vial overlapping fixture as shown in Figure 9 under a 30N load prior to bending testing. A fourth set of tubes made from the reference glass composition were tested in four-point bend after ion-exchange tempering in a 100% KNO3 bath at 450°C for 1 hour. These uncoated ion-exchange tempered tubes were also scraped in the vial stacking fixture shown in Figure 9 under a 30N load prior to bend testing. A fifth set of tubes made from Type IB glass were tested in four-point bend as received (uncoated, non-ion-exchange tempered). A sixth set of tubes made from Type IB glass were tested in four-point bend after ion-exchange tempering in a 100% KNO3 bath at 450°C for 1 hour. The test results are illustrated in the Weibull plot shown in Figure 21.

[0199] Referring to Figure 21, the second set of tubes, which were not abraded and were formed from the reference glass composition and were ion-exchange strengthened, endured the highest stress before breaking. The third set of tubes, which were coated with 0.1% APS / 0.1% Novastrat® 800 before abrasion, showed a slight decrease in strength compared to their uncoated, unabraded counterparts (i.e., the second set of tubes). However, the decrease in strength was relatively minor despite being subjected to abrasion after coating. Example 4 Two sets of vials were prepared and run through a pharmaceutical filling line. Pressure sensitive tape (commercially available from Fujifilm Corporation) was inserted between the vials to measure contact / impact forces between the vials and between the vials and the instrument. The first set of vials was formed from Type IB glass and was uncoated. The second set of vials was formed from a reference glass composition as described above and was coated with a low friction polyimide-based coating having a coefficient of friction of about 0.25. The pressure sensitive tape was analyzed after the vials had been run through a pharmaceutical filling line, demonstrating that the second set of coated vials exhibited a 2-3 fold reduction in stress compared to the first set of uncoated vials. Example 5 Three sets of four vials were prepared each. All vials were formed from the reference glass composition. The first set of vials was coated with APS / Novastrat® 800 coating as described in Example 2. The second set of vials was dip coated with 0.1% DC806A in toluene. The solvent was evaporated at 50° C. and the coating was cured at 300° C. for 30 minutes. Each set of vials was placed in a tube and heated at 320° C. for 2.5 hours under an air purge to remove trace contaminants that were adsorbed in the vials in the laboratory environment. Each set of samples was then heated in the tube for an additional 30 minutes and the outgassed volatiles were collected in an activated carbon adsorbent trap. The trap was heated to 350° C. for 30 minutes to desorb all the collected material, which was fed into a gas chromatography-mass spectrometry. Figure 22 shows the gas chromatography-mass spectrometry output data for the APS / Novastrat® 800 coating. Figure 23 shows the gas chromatography-mass spectrometry output data for the DC806A coating. No outgassing was detected from the 0.1% APS / 0.1% Novastrat® 800 coating or the DC806A coating.

[0200] A set of four vials was coated with a tie layer using a 0.5% / 0.5% GAPS / APhTMS (3-aminopropyltrimethoxysilane / aminophenyltrimethoxysilane) solution in a methanol / water mixture. The coated surface area of ​​each vial was approximately 18.3 cm. 2The solvent was evaporated from the coated vials at 120° C. for 15 minutes. A 0.5% solution of Novastrat® 800 in dimethylacetamide was then applied to the samples. The solvent was evaporated at 150° C. for 20 minutes. These uncured vials were subjected to the degassing test described above. The vials were heated to 320° C. in air flow (100 mL / min) and after reaching 320° C., the released volatiles were collected every 15 minutes in an activated carbon adsorbent trap. The trap was then heated at 350° C. for 30 minutes or more to desorb the collected material, which was then placed in a gas chromatography-mass spectrometer. Table 3 shows the amount of material collected over the time segment in which the sample was held at 320° C. Time zero corresponds to the time when the sample first reached a temperature of 320° C. As shown in Table 3, after 30 minutes of heating, the amount of volatiles was reduced to less than 100 ng, which is the detection limit of the instrument. Table 3 also reports the volatiles loss per square centimeter of coating surface.

[0201] [Table 3]

[0202] Example 6 Vials were prepared with various silicone or polyimide-based coatings with and without coupling agents. When coupling agents were used, they included APS and GAPS, a precursor of APS. The outer coating layer was prepared from silicone resins such as Novastrat® 800, poly(pyromellitic dianhydride-co-4,4'-oxydianiline), or DC806A and DC255. APS / poly(4,4'-oxydiphenylene-pyromellitimide) coatings were prepared using a 0.1% solution of APS (aminopropylsilsesquioxane) and a 0.1%, 0.5% or 1.0% solution of poly(pyromellitic dianhydride-co-4,4'-oxydianiline) amic acid (PMDA-ODA-poly(4,4'-oxydiphenylene-pyromellitimide)) in N-methyl-2-pyrrolidone (NMP). Poly(4,4'-oxydiphenylene-pyromellitimide) coatings were also applied using a 1.0% solution of poly(pyromellitic dianhydride-co-4,4'oxydianiline) in NMP without a coupling agent. APS / Novastrat® 800 coatings were prepared using a 0.1% solution of APS and a 0.1% solution of Novastrat® 800 polyamic acid in a 15 / 85 toluene / DMF solution. DC255 coatings were applied directly to the glass using a 1.0% solution of DC255 in toluene without a coupling agent. APS / DC806A coatings were prepared by first applying a 0.1% solution of APS in water, followed by a 0.1% or 0.5% solution of DC806A in toluene. The GAPS / DC806A coating was applied using a 1.0% solution of GAPS in 95% by weight ethanol in water as the coupling agent, followed by a 1.0% solution of DC806A in toluene. The coupling agent and coating were applied using the dip coating method described herein, where the coupling agent was heat treated after application, and the silicone and polyimide coatings were dried and cured after application. The thickness of the coating was estimated based on the concentration of the solution used.The table contained in FIG. 24 lists the various coating compositions, estimated coating thicknesses and test conditions.

[0203] Some of the vials were then tumbled to simulate damage to the coating, while others were subjected to abrasion under 30N and 50N loads in a vial stacking fixture as shown in Figure 9. All vials were then subjected to lyophilization (freeze-drying process) in which the vials were filled with 0.5mL of sodium chloride solution and then frozen at -100°C. Freeze-drying was then carried out at -15°C under reduced pressure for 20 hours. The vials were inspected in an optical quality assurance instrument and under a microscope. No damage to the coating due to freeze-drying was observed. Example 7 Three sets of six vials were prepared to evaluate the effect of increasing load on the coefficient of friction of uncoated vials and vials coated with Dow Corning DC 255 silicone resin. The first set of vials was formed from Type IB glass and left uncoated. The second set of vials was formed from a reference glass composition, coated with a 1% solution of DC255 in toluene, and cured at 300° C. for 30 minutes. The third set of vials was formed from Type IB glass and coated with a 1% solution of DC255 in toluene. Each set of vials was placed in the vial stacking fixture depicted in FIG. 9, and the coefficient of friction against similarly coated vials was measured during abrasion under static loads of 10 N, 30 N, and 50 N. The results are reported graphically in FIG. 25. As shown in FIG. 25, the coated vials exhibited significantly lower coefficients of friction compared to uncoated vials when abraded under the same conditions, regardless of glass composition. Example 8 Three sets of two glass vials were prepared with APS / poly(4,4'-oxydiphenylene-pyromellitimide) coatings. First, each of the vials was dip coated in a 0.1% solution of APS (aminopropylsilsesquioxane). The APS coating was dried in a convection oven at 100°C for 15 minutes. The vials were then immersed in a 0.1% solution of poly(pyromellitic dianhydride-co-4,4'-oxydianiline) amic acid (PMDA-ODA (poly(4,4'-oxydiphenylene-pyromellitimide))) in N-methyl-2-pyrrolidone (NMP). The coating was then cured by placing the coated vials in a preheated oven at 300°C for 30 minutes.

[0204] Two vials were placed in the vial stacking fixture shown in FIG. 9 and rubbed with a 10N load. The rub procedure was repeated four more times over the same area and the coefficient of friction was measured for each rub. The vials were wiped between the scratches and the starting point of each scratch was placed in an area that had not yet been rubbed. However, each scratch moved on the same "track". The same procedure was repeated for loads of 30N and 50N. The coefficients of friction for each scratch (i.e., A1-A5) are plotted in FIG. 26 for each load. As shown in FIG. 26, the coefficients of friction for the APS / poly(4,4'-oxydiphenylene-pyromellitimide) coated vials were generally less than 0.30 for all rubs at all loads. This example demonstrates the improved resistance to scratching of polyimide coatings when applied over glass surfaces treated with a coupling agent. Example 9 Three sets of two glass vials were prepared with APS coatings. Each of the vials was dip coated in a 0.1% solution of APS (aminopropylsilsesquioxane) and heated in a convection oven at 100° C. for 15 minutes. The two vials were placed in a vial stacking fixture as shown in FIG. 9 and scratched under a 10N load. The scratching procedure was repeated four more times on the same area and the coefficient of friction was measured for each scratch. The scratches on these vials were wiped between and the starting point of each scratch was placed in an area that had not yet been scratched. However, each scratch moved on the same "track". The same procedure was repeated for loads of 30N and 50N. The coefficient of friction for each scratch (i.e., A1-A5) is shown for each load in FIG. 27. As shown in FIG. 27, the coefficient of friction for the vials coated with APS alone was generally higher than 0.3, often reaching 0.6 or higher. Example 10 Three sets of two glass vials were prepared with APS / poly(4,4'-oxydiphenylene-pyromellitimide) coatings. Each of the vials was dip coated in a 0.1% solution of APS (aminopropylsilsesquioxane). The APS coating was heated in a convection oven at 100°C for 15 minutes. The vials were then immersed in a 0.1% poly(pyromellitic dianhydride-co-4,4'-oxydianiline) amic acid solution (PMDA-ODA-poly(4,4'-oxydiphenylene-pyromellitimide)) in N-methyl-2-pyrrolidone (NMP). The coating was then cured by placing the coated vials in a preheated oven at 300°C for 30 minutes. The coated vials were then depyrogenated (heated) at 300°C for 12 hours.

[0205] Two vials were placed in the vial stacking fixture shown in FIG. 9 and rubbed with a 10 N load. The rub procedure was repeated four more times over the same area, and the coefficient of friction was measured for each rub. The vials were wiped between the rubs, the start of each rub was placed on an area already rubbed, and each rub was performed on the same "track." The same procedure was repeated for loads of 30 N and 50 N. The coefficient of friction for each rub (i.e., A1-A5) is shown in FIG. 28 for each load. As shown in FIG. 28, the coefficient of friction for the APS / poly(4,4'-oxydiphenylene-pyromellitimide) coated vials was generally uniform, approximately 0.20 or less for rubs introduced with loads of 10 N and 30 N. However, when the applied load was increased to 50 N, the coefficient of friction increased for each successive rub, with the fifth rub having a coefficient of friction slightly less than 0.40. Example 11 Three sets of two glass vials were prepared with an APS (aminopropylsilsesquioxane) coating. Each of the vials was dip coated in a 0.1% solution of APS and heated in a convection oven at 100°C for 15 minutes. The coated vials were then depyrogenated (heated) at 300°C for 12 hours. The two vials were placed in a vial stacking fixture as illustrated in Figure 9 and scratched under a 10N load. The scratching procedure was repeated four more times over the same area and the coefficient of friction was measured for each scratch. The scratches on these vials were wiped between and the start of each scratch was placed on the already scratched area, with each scratch moving on the same "track". The same procedure was repeated for loads of 30N and 50N. The coefficient of friction for each scratch (i.e., A1-A5) is illustrated in Figure 29 for each load. As shown in FIG. 29, the coefficient of friction for the APS-coated vials that were depyrogenated for 12 hours was significantly higher than the APS-coated vials shown in FIG. 27 and similar to the coefficient of friction exhibited by the uncoated glass vials, indicating that the vials may have lost significant mechanical strength due to scratches. Example 12 Three sets of two glass vials made from Type IB glass were prepared with a poly(4,4'-oxydiphenylene-pyromellitimide) coating. The vials were immersed in a 0.1% poly(pyromellitic dianhydride-co-4,4'-oxydianiline) amic acid solution (PMDA-ODA-poly(4,4'-oxydiphenylene-pyromellitimide)) in N-methyl-2-pyrrolidone (NMP). The coating was then dried at 150°C for 20 minutes and then cured by placing the coated vials in a preheated oven at 300°C for 30 minutes.

[0206] Two vials were placed in the vial stacking fixture shown in Figure 9 and rubbed with a 10N load. The rub procedure was repeated four more times over the same area and the coefficient of friction was measured for each rub. These vials were wiped between the scratches and the starting point of each scratch was placed in an area that had not yet been rubbed. However, each scratch moved on the same "track". The same procedure was repeated for loads of 30N and 50N. The coefficient of friction for each scratch (i.e., A1-A5) is plotted for each load in Figure 30. As shown in Figure 30, the coefficient of friction for the poly(4,4'-oxydiphenylene-pyromellitimide) coated vials generally increased after the first rub, demonstrating the poor wear resistance of the polyimide coating applied to glass without a coupling agent. Example 13 The APS / Novastrat® 800 coated vials of Example 6 were tested for coefficient of friction after lyophilization using the vial overlapping fixture shown in Figure 9 with a load of 30 N. No increase in coefficient of friction was detected after lyophilization. Figure 31 contains a table showing the coefficient of friction for APS / Novastrat® 800 coated vials before and after lyophilization. Example 14 Reference glass composition vials were ion exchanged and coated as described in Example 2. The coated vials were autoclaved using the following protocol: 10 minutes water vapor purge at 100°C, followed by a 20 minute dwell time (the coated glass container 100 is exposed to a 121°C environment), followed by 30 minutes treatment at 121°C. The coefficient of friction for autoclaved and non-autoclaved vials was measured using the vial stacking fixture shown in Figure 9 with a 30N load. Figure 32 shows the coefficient of friction for APS / Novastrat® 800 coated vials before and after autoclaving. No increase in the coefficient of friction was detected after autoclaving. Example 15 Three sets of vials were coated with an APS / APhTMS (1:8 ratio) tie layer and the outer layer consisted of Novastrat® 800 polyimide applied as a solution of polyamic acid in dimethylacetamide and imidized at 300° C. One set was depyrogenated at 320° C. for 12 hours. A second set was depyrogenated at 320° C. for 12 hours and then autoclaved at 121° C. for 1 hour. The third set of vials was left uncoated. Each set of vials was then subjected to a vial overlap test under a 30N load. The coefficient of friction for each set of vials is reported in FIG. 33. Photographs of the vial surfaces showing the damage (or absence of damage) that occurred to each vial are also shown in FIG. 33. As shown in FIG. 33, the uncoated vials generally had a coefficient of friction greater than about 0.7. The uncoated vials also showed visually perceptible damage as a result of the test. However, the coated vials had a coefficient of friction of less than 0.45 without any visually perceptible surface damage.

[0207] The coated vials were also subjected to depyrogenation, autoclave conditions, or both as described above. Figure 34 illustrates the probability of failure as a function of applied load in horizontal compression tests on the vials. No statistical differences were observed between the depyrogenated and the depyrogenated and autoclaved vials. Example 16 Vials formed from Type IB ion-exchanged glass were prepared with lubricious coatings having various silane ratios. Referring now to FIG. 35, vials were prepared with three different coating compositions to evaluate the effect of different silane ratios on the coefficient of friction of the applied coating. The first coating composition comprised a coupling agent layer having a GAPS to aminophenyltrimethyloxysilane (APhTMS) ratio of 1:1 and an outer coating layer of 1.0% Novastrat® 800 polyimide. The second coating composition comprised a coupling agent layer having a GAPS to APhTMS ratio of 1:0.5 and an outer coating layer of 1.0% Novastrat® 800 polyimide. The third coating composition comprised a coupling agent layer having a GAPS to APhTMS ratio of 1:0.2 and an outer coating layer of 1.0% Novastrat® 800 polyimide. All vials were depyrogenated at 320° C. for 12 hours. The vials were then subjected to a vial overlap friction test under loads of 20 N and 30 N. The average applied normal force, friction coefficient and maximum frictional force (Fx) for each vial are reported in Figure 35. As shown in Figure 35, as the amount of aromatic silane (i.e., aminophenyltrimethyloxysilane) decreases, the friction coefficient between the vials as well as the frictional force experienced by the vials increases. Example 17 Vials made from Type IB ion-exchange glass were prepared with lubricious coatings having various silane ratios.

[0208] Samples were prepared with a composition comprising a coupling agent layer formed from 0.125% APS and 1.0% aminophenyltrimethyloxysilane (APhTMS) (having an APS / APhTMS ratio of 1:8) and an outer coating layer formed from 0.1% Novastrat® 800 polyimide. The thermal stability of the applied coating was evaluated by measuring the coefficient of friction and the frictional force on the vials before and after depyrogenation. Specifically, the coated vials were subjected to a vial overlap friction test under a load of 30 N. The coefficient of friction and the frictional force were measured and are plotted against time in FIG. 36. A second set of vials was depyrogenated at 320° C. for 12 hours and subjected to the same vial overlap friction test under a load of 30 N. The coefficient of friction remained the same both before and after depyrogenation, indicating that the coating was thermally stable and protected the glass surface from frictional damage. Photographs of the glass contact areas are also shown.

[0209] Samples were prepared with a composition comprising a coupling agent layer formed from 0.0625% APS and 0.5% APhTMS (having an APS / APhTMS ratio of 1:8) and an outer coating layer formed from 0.05% Novastrat® 800 polyimide. The thermal stability of the applied coating was evaluated by measuring the coefficient of friction and the force due to friction on the vials before and after depyrogenation. Specifically, the coated vials were subjected to a vial overlap friction test under a load of 30 N. The coefficient of friction and the force due to friction were measured and are plotted against time / distance in FIG. 37. A second set of vials was depyrogenated at 320° C. for 12 hours and subjected to the same vial overlap friction test under a load of 30 N. The coefficient of friction remained the same both before and after depyrogenation, indicating that the coating was thermally stable. Photographs of the glass contact areas are also shown.

[0210] Figure 38 illustrates the probability of failure as a function of applied load in horizontal compression tests for a vial with a smooth coating formed from 0.125% APS and 1.0% APhTMS, a vial with an outer coating layer formed from 0.1% Novastrat® 800 polyimide (shown as "260" in Figure 38), a vial with a smooth coating formed from 0.0625% APS and 0.5% APhTMS, and a vial with a 0.05% Novastrat® 800 polyimide outer coating layer (shown as "280" in Figure 38). The data shows that the failure load did not change from the uncoated and unscratched samples to the coated, depyrogenated, and scratched samples, demonstrating the protection of the glass from damage by the coating.

[0211] Vials were prepared with a smooth coating using GAPS hydrolysate. Samples were prepared with a composition including a coupling agent layer formed from 0.5% Dynasylan® Hydrosil 1151 (3-aminopropylsilane hydrolysate) and 0.5% aminophenyltrimethyloxysilane (APhTMS) (having a 1:1 ratio), and an outer coating layer formed from 0.05% Novastrat® 800 polyimide. Coating performance was evaluated by measuring the coefficient of friction and the force due to friction on the vials before and after depyrogenation. Specifically, Type IB vials that were ion-exchange toughened (100% KNO3, 450°C for 8 hours) were subjected to a vial overlap friction test under a load of 30N. The coefficient of friction and the force due to friction were measured and are plotted against time / distance in Figure 39. A second set of vials was depyrogenated at 320°C for 12 hours and subjected to the same vial overlap friction test under a load of 30N. The coefficient of friction remained the same both before and after depyrogenation, indicating that the coating is thermally stable. Photographs of the glass contact area are also shown, suggesting that hydrolyzates of aminosilanes may also be useful in coating formulations.

[0212] The thermal stability of the applied coating was also evaluated for a range of depyrogenation conditions. Specifically, Type IB ion-exchange glass vials were prepared with a composition including a coupling agent layer with a 1:1 ratio of GAPS (0.5%) to aminophenyltrimethyloxysilane (APhTMS) (0.5%) and an outer coating layer of 0.5% Novastrat® 800 polyimide. The vials were dip-coated in the solution using an automated dip coater with a withdrawal speed of 2 mm / s. Sample vials were subjected to one of the following depyrogenation cycles: 320° C. for 12 hours; 320° C. for 24 hours; 360° C. for 12 hours; or 360° C. for 24 hours. The coefficient of friction and the force due to friction were then measured using a vial overlap friction test and plotted against time for each depyrogenation condition, as shown in FIG. 40. As shown in FIG. 40, the coefficient of friction of the vials did not change with the depyrogenation conditions, indicating that the coating was thermally stable. FIG. 41 illustrates the coefficient of friction after various heat treatment times at 360° C. and 320° C. Example 18 Vials were coated with the APS / Novastrat 800 coating as described in Example 2. The light transmission of the coated vials as well as the uncoated vials was measured using a spectrophotometer in the wavelength range of 400-700 nm. Measurements were made by directing a light beam perpendicular to the container wall so that it passes through the smooth coating twice, once on entry to the container and once on exit. FIG. 11 illustrates the light transmission data measured in the visible light spectrum from 400-700 nm for coated and uncoated vials. Line 440 represents the uncoated glass container and line 442 represents the coated glass container. Example 19 Vials were coated with 0.25% GAPS / 0.25% APhTMS coupling agent and 1.0% Novastrat® 800 polyimide and tested for light transmission before and after 12 hours of depyrogenation at 320° C. Uncoated vials were also tested. The results are shown in FIG. Example 20 To improve the uniformity of the polyimide coating, Novastrat® 800 polyamic acid was converted to a polyamic acid salt by adding 4 g of triethylamine to 1 L of methanol, followed by the addition of Novastrat® 800 polyamic acid to form a 0.1% solution, which was dissolved in methanol, a solvent that evaporates significantly faster than dimethylacetamide. The methanol-soluble salt of poly(pyromellitic dianhydride-co-4,4'-oxydianiline)amic acid could be produced.

[0213] Coatings on Type IB ion exchange vials were formed from 1.0% GAPS / 1.0% APhTMS in a methanol / water mixture and 0.1% Novastrat® 800 polyamic acid salt in methanol. The coated vials were subjected to depyrogenation at 360° C. for 12 hours, and samples not subjected to depyrogenation and samples subjected to depyrogenation were rubbed with 10 N, 20 N and 30 N vertical loads in a vial overlapping fixture. No glass damage was observed at 10 N, 20 N and 30 N vertical forces. FIG. 43 shows the coefficient of friction, applied force and frictional force for samples after 12 hours of heat treatment at 360° C. FIG. 44 illustrates the probability of failure as a function of applied load in horizontal compression tests on samples. Statistically, the series of samples at 10 N, 20 N and 30 N were distinguishable from each other. The low load fractured samples broke from a base point away from the scratch.

[0214] The thickness of the coating layer was estimated using ellipsometry and scanning electron microscopy (SEM), as shown in Figures 45-47, respectively. Samples for coating thickness measurement were prepared using silicon wafers (ellipsometry) and glass slides (SEM). This method shows thicknesses ranging from 55 to 180 nm for the tie layer and 35 nm for the Novastrat® 800 polyamic acid salt. Example 21 Plasma cleaned Si wafer pieces were dip coated with a 0.5% GAPS / 0.5% APhTMS solution in a 75 / 25 methanol / water vol / vol mixture. The coating was exposed to 120°C for 15 minutes. The coating thickness was measured using ellipsometry. Three samples were prepared with thicknesses of 92.1 nm, 151.7 nm, and 110.2 nm, respectively, with a standard deviation of 30.6 nm.

[0215] Glass slides were dip coated and examined by scanning electron microscopy. Figure 45 shows an SEM image of a glass slide dip coated in a coating solution of 1.0% GAPS, 1.0% APhTMS, and 0.3% NMP in a 75 / 25 methanol / water mixture at a withdrawal speed of 8 mm / s, followed by curing at 150°C for 15 minutes. The coating appears to be about 93 nm thick. Figure 46 shows an SEM image of a glass slide dip coated in a coating solution of 1.0% GAPS, 1.0% APhTMS, and 0.3 NMP in a 75 / 25 methanol / water mixture at a withdrawal speed of 4 mm / s, followed by curing at 150°C for 15 minutes. The coating appears to be about 55 nm thick. Figure 47 shows an SEM image of a glass slide that was dip coated in a coating solution of 0.5% Novastrat® 800 solution at a withdrawal speed of 2 mm / s, cured for 15 minutes at 150° C., and heat treated for 30 minutes at 320° C. The coating appears to be approximately 35 nm thick. Comparative example A Glass vials formed from Type IB glass were coated with a dilute coating of Bayer Silicone aqueous emulsion of Baysilone M with a solids content of approximately 1-2%. The vials were treated at 150°C for 2 hours to evaporate the water from the surface, leaving a polydimethylsiloxane coating on the exterior surface of the glass. The nominal thickness of the coating was approximately 200 nm. One set of vials was left untreated (i.e., "barely coated vials"). A second set of vials was treated at 280°C for 30 minutes (i.e., "treated vials"). Some of the vials from each set were first mechanically tested by applying scratches approximately 20 mm long with a linearly increasing load from 0 to 48 N using a UMT-2 tribometer and vial overlap test fixture. The scratches were evaluated for coefficient of friction and morphology to determine whether the scratch procedure damaged the glass or whether the coating protected the glass from damage caused by the scratch.

[0216] FIG. 48 is a plot showing coefficient of friction, scratch penetration, applied normal force, and friction force (y coordinate) as a function of applied scratch length (x coordinate) for bare coated vials. As shown in FIG. 48, the bare coated vials exhibited a coefficient of friction of approximately 0.03 up to a load of about 30 N. The data shows that below approximately 30 N, the COF is always less than 0.1. However, above a normal force of 30 N, the coating begins to fail as indicated by the presence of glass cracks along the length of the scratch. Glass cracks indicate glass surface damage, the consequences of which increase the propensity for glass breakage.

[0217] Figure 49 is a plot showing the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of applied scratch length (x coordinate) for the treated vials. For the treated vials, the coefficient of friction remained low until the applied load reached a value of approximately 5 N. At this point the coating began to fail and the glass surface was severely damaged as evidenced by the large amount of glass cracking that occurred with increasing load. The coefficient of friction for the treated vials increased to approximately 0.5. However, the coating was unable to protect the glass surface at a load of 30 N after thermal exposure, indicating that the coating was thermally unstable.

[0218] The vials were then tested by applying a static load of 30N across the full length of the 20mm scratch. Ten samples of the bare coated vials and ten samples of the treated vials were tested in horizontal compression by applying a static load of 30N across the full length of the 20mm scratch. None of the bare coated samples failed at the scratch, whereas six of the ten treated vials failed at the scratch, indicating reduced residual strength in the treated vials. Comparative example B A solution of Wacker Silres MP50 (product no. 60078465, lot no. EB21192) was diluted to 2% and applied to vials made from the reference glass composition. The vials were first cleaned by applying plasma for 10 seconds before coating. The vials were dried at 315°C for 15 minutes to allow water to evaporate from the coating. The first set of vials was kept in the "bare coating" condition. The second set of vials was subjected to temperatures ranging from 250°C to 320°C for 30 minutes (i.e., "treated vials"). Some of the vials from each set were first mechanically tested by applying scratches approximately 20 mm long with a linearly increasing load from 0 to 48 N using a UMT-2 tribometer. The scratches were evaluated for coefficient of friction and morphology to determine whether the scratch procedure damaged the glass or whether the coating protected the glass from damage caused by the scratch.

[0219] FIG. 50 is a plot showing coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of applied scratch length (x coordinate) for plain coated vials.

[0220] Figure 51 is a plot showing the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of applied scratch length (x coordinate) for treated vials treated at 280°C. The treated vials showed significant glass surface damage at applied loads above about 20N. It was also determined that the load threshold for glass damage decreased with increasing thermal exposure temperature, indicating that the coating degraded at higher temperatures (i.e., the coating was thermally unstable). Samples treated at temperatures below 280°C showed glass damage at loads above 30N. Comparative example C Vials formed from the reference glass composition were treated with Evonik Silikophen P 40 / W diluted to 2% solids in water. The samples were then dried at 150° C. for 15 minutes and then cured at 315° C. for 15 minutes. The first set of vials remained in the “bare-coated” state. The second set of vials was treated at a temperature of 260° C. for 30 minutes (i.e., “260° C.-treated vials”). The third set of vials was treated at a temperature of 280° C. for 30 minutes (i.e., “280° C.-treated vials”). These vials were scratched with a static load of 30 N using the test fixture shown in FIG. 9. These vials were then tested in horizontal compression. The 260° C.-treated and 280° C.-treated vials were damaged by compression, while 2 of the 16 bare-coated vials were damaged by scratching. This indicates that the coating had deteriorated from exposure to high temperatures and, as a result, the coating did not adequately protect the surface from the 30N load. Example 22 Vials formed from the reference glass composition were coated with a 75 / 25 solution of 1.0% / 1.0% GAPS / m-APhTMS solution in methanol / water. The vials were dip coated in the solution with a withdrawal speed of 2 mm / s. The coating was cured at 150° C. for 15 minutes. The first set of vials was maintained in an untreated state (i.e., the “barely coated vials”). The second set of vials was subjected to depyrogenation at 300° C. for 12 hours (i.e., the “treated vials”). Some of the vials in each set were mechanically tested by applying a scratch with a 10 N load from the vial shoulder to the vial heel using a UMT-2 tribometer and vial overlap test fixture. Additional vials in each set were mechanically tested by applying a scratch with a 30 N load from the vial shoulder to the vial heel using a UMT-2 tribometer and vial overlap test fixture. The scratches were evaluated for coefficient of friction and morphology to determine if the scratch procedure damaged the glass or if the coating protected the glass from damage due to the scratch.

[0221] Figures 52 and 53 are plots showing the coefficient of friction, scratch penetration, applied normal force and friction force (y coordinate) as a function of the applied scratch length (x coordinate) for bare coated vials. As shown in Figures 52 and 53, the bare coated vials showed some scuffing and glass damage after testing. However, the coefficient of friction was approximately 0.4-0.5 during testing. Figures 54 and 55 show the results of similar tests performed on treated vials. After testing, the treated vials showed some scuffing of the surface of the coating as well as some damage to the glass. The coefficient of friction was approximately 0.7-0.8 during testing. Example 23 Vials formed from the reference glass composition were coated with a 75 / 25 solution of 1.0% / 1.0% GAPS / m-APhTMS solution in methanol / water. The vials were dip coated in the solution with withdrawal speeds ranging from 0.5 mm / s to 4 mm / s, varying the thickness of the coating on each vial. The coatings were cured at 150° C. for 15 minutes. The first set of vials was maintained in an untreated state (i.e., the “barely coated vials”). The second set of vials was subjected to depyrogenation at 300° C. for 12 hours (i.e., the “treated vials”). Some of the vials in each set were mechanically tested by applying a scratch with a UMT-2 tribometer from the shoulder of the vial to the heel of the vial with a 10 N load. Additional vials in each set were mechanically tested by applying a scratch with a UMT-2 tribometer from the shoulder of the vial to the heel of the vial with a 30 N load. The vials were then tested in horizontal compression. The results of the horizontal compression tests are reported in Figures 56 and 57. The vials scratched under a 10 N load showed fairly small differences in mechanical strength despite the varying coating thicknesses. Vials scratched with 30 N and having thinner coatings (i.e., those corresponding to a withdrawal speed of 0.5 mm / s) were more prone to fracture in horizontal compression compared to vials with thicker coatings.

[0222] It should be understood here that the glass containers described herein have at least two performance characteristics selected from resistance to delamination, improved strength, and high damage resistance.For example, the glass containers may have a combination of resistance to delamination and improved strength; improved strength and high damage resistance; or resistance to delamination and high damage resistance.These glass containers may be understood in various ways.

[0223] In a first embodiment, the glass container may include a body having an inner surface, an outer surface, and a wall thickness extending between the outer surface and the inner surface. A compressive stress layer may extend from the outer surface of the body into the wall thickness. The compressive stress layer may have a surface compressive stress of 150 MPa or more. A lubricious coating may be located about at least a portion of the outer surface of the body. The outer surface of the body including the lubricious coating may have a coefficient of friction of 0.7 or less.

[0224] In a second embodiment, a glass container may include a body having an inner surface, an outer surface, and a thickened portion extending between the outer and inner surfaces. The body may be formed from Type 1, Class B glass conforming to ASTM standard E438-92. A compressive stress layer may extend from the outer surface of the body into the thickened portion. The compressive stress layer may have a surface compressive stress of 150 MPa or greater. A smooth coating may be located about at least a portion of the outer surface of the body. The outer surface of the body with the smooth coating may have a coefficient of friction of 0.7 or less.

[0225] A third embodiment includes the glass container according to the first embodiment or the second embodiment, which has a surface compressive stress of 200 MPa or more.

[0226] A fourth embodiment includes the glass container according to any one of the first to third embodiments, which has a surface compressive stress of 300 MPa or more.

[0227] A fifth embodiment includes the glass container according to any one of the first to fourth embodiments, in which the compressive stress layer extends to a layer depth of 3 μm or more.

[0228] A sixth embodiment includes the glass container of any one of the first to fifth embodiments, in which the compressive stress layer extends to a layer depth of 25 μm or more.

[0229] A seventh embodiment includes the glass container according to any one of the first to sixth embodiments, the main body of which is strengthened by ion exchange.

[0230] An eighth embodiment includes a glass container according to any one of the first to seventh embodiments, the main body of which has been subjected to high-temperature ion exchange strengthening.

[0231] A ninth embodiment includes the glass container of any one of the first to sixth embodiments, the body of which is heat-strengthened.

[0232] A tenth embodiment includes the glass container of the ninth embodiment, wherein the compressive stress layer extends into the thickened portion to a layer depth of about 22% or less of the thickened portion.

[0233] An eleventh embodiment includes the glass container according to any one of the first to sixth embodiments, in which the body comprises laminated glass.

[0234] The twelfth aspect is that the laminated glass has a core thermal expansion coefficient CTE core a core layer fused to the core layer and having a second coefficient of thermal expansion CTE clad at least one cladding layer having a CTE core is CTE clad The present invention includes an eleventh embodiment of a glass container, which is different from the above embodiment.

[0235] A thirteenth embodiment is directed to an optical fiber having at least one cladding layer, the at least one cladding layer comprising a first cladding layer and a second cladding layer; the first cladding layer fused to a first surface of the core layer and the second cladding layer fused to a second surface of the core layer; and a CTE core is CTE clad The glass container of the twelfth embodiment is larger than

[0236] A fourteenth embodiment includes the glass container of any one of the twelfth to thirteenth embodiments, in which the compressive stress layer extends into the thick portion to a layer depth that is from about 1 μm to about 90% of the thick portion.

[0237] A fifteenth embodiment includes the glass container of any one of the twelfth to thirteenth embodiments, in which the compressive stress layer extends into the thick portion to a layer depth that is from about 1 μm to about 33% of the thick portion.

[0238] A sixteenth embodiment includes the glass container of any of the twelfth to fifteenth embodiments, wherein at least one cladding layer forms an inner surface of the body.

[0239] A seventeenth aspect includes the glass container of any of the first to sixteenth aspects, further comprising an inorganic coating positioned on at least a portion of the outer surface of the glass body, the inorganic coating having a thermal expansion coefficient smaller than the thermal expansion coefficient of the glass body.

[0240] An eighteenth embodiment comprises the glass container of any of the first to seventeenth embodiments, wherein the smooth coating is thermally stable at a temperature of at least about 250° C. for 30 minutes.

[0241] A nineteenth embodiment comprises the glass container of any of the first through eighteenth embodiments, wherein the smooth coating is thermally stable at a temperature of at least about 260° C. for 30 minutes.

[0242] A twentieth embodiment includes the glass container of any of the first to nineteenth embodiments, wherein the smooth coating is thermally stable at a temperature of at least about 280° C. for 30 minutes.

[0243] A twenty-first embodiment includes the glass container of any of the first to twentieth embodiments, wherein the smooth coating is a robust inorganic coating.

[0244] A twenty-second embodiment includes the glass container of the twenty-first embodiment, wherein the robust inorganic coating is a metal nitride coating, a metal oxide coating, a metal sulfide coating, SiO2, diamond-like carbon, graphene, or a carbide coating.

[0245] A twenty-third embodiment includes the glass container of the twenty-first embodiment, wherein the robust inorganic coating comprises at least one of tin, BN, HBN TiO2, Ta2O5, HfO2, Nb2O5, V2O5, SiO2, MoS2, SiC, SnO, SnO2, ZrO2, Al2O3, BN, ZnO, and BC.

[0246] A twenty-fourth embodiment includes the glass container of any of the first through twentieth embodiments, wherein the smooth coating comprises a robust organic coating that has a mass loss of less than about 5% of its mass when heated to a temperature of from 150° C. to 350° C. at a heating rate of about 10° C. / min.

[0247] A twenty-fifth embodiment includes the glass container of the twenty-fourth embodiment, wherein the robust organic coating comprises a polymeric chemical composition.

[0248] A twenty-sixth embodiment includes the glass container of the twenty-fifth embodiment, wherein the robust organic coating further comprises a coupling agent.

[0249] A twenty-seventh embodiment includes the glass container of any of the first to seventeenth embodiments, wherein the smooth coating is a temporary coating.

[0250] A twenty-eighth embodiment includes the glass container of the twenty-seventh embodiment, wherein the temporary coating pyrolyzes at a temperature of 300° C. or less within one hour.

[0251] A twenty-ninth embodiment includes the glass container of any of the twenty-seventh or twenty-eighth embodiments, wherein the temporary coating comprises a mixture of polyoxyethylene glycol, a methacrylate resin, a melamine formaldehyde resin, and a polyvinyl alcohol.

[0252] A thirtieth embodiment includes the glass container of either the twenty-seventh or twenty-ninth embodiment, wherein the temporary coating comprises one or more polysaccharides.

[0253] A thirty-first embodiment includes the glass container of any of the twenty-seventh to thirtieth embodiments, wherein the temporary coating includes polyacrylic acid or a derivative of polyacrylic acid.

[0254] A thirty-second embodiment includes the glass container of any of the twenty-seventh to thirty-first embodiments, wherein the temporary coating includes an inorganic salt.

[0255] A thirty-third embodiment is a coating composition comprising a temporary coating selected from the group consisting of: poly(ethylene oxide), poly(propylene oxide), ethylene oxide-propylene oxide copolymers, polyvinyl-pyrrolidinone, polyethyleneamines, poly(methyl vinyl ether), polyacrylamides, polymethacrylamides, polyurethanes, poly(vinyl acetate), polyvinyl formal, polyacetals and polyformaldehyde including acetal copolymers, poly(alkyl methacrylates), methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose, methyl hydroxypropyl cellulose, poly(acrylic acid) and salts thereof, poly(methacrylic acid) and salts thereof, ethylene-maleic anhydride copolymers, ethylene - the glass container of any of the twenty-seventh to thirty-second embodiments, comprising at least one of vinyl alcohol copolymers, ethylene-acrylic acid copolymers, vinyl acetate-vinyl alcohol copolymers, methyl vinyl ether-maleic anhydride copolymers, emulsifying polyurethanes, polyoxyethylene stearate, and polyolefins including polyethylene, polypropylene and copolymers thereof, starch and modified starches, hydrocolloids, polyacrylamide, vegetable and animal fats, waxes, tallow, soaps, stearin-paraffin emulsions, dimethyl or diphenyl or mixed methyl / phenyl polysiloxanes, perfluorinated siloxanes and other substituted siloxanes, alkyl silanes, aromatic silanes, and oxidized polyethylene.

[0256] A 34th aspect includes a glass container of any of the first to 33rd aspects, in which the light transmittance of the glass container with a smooth coating is at least about 55% of the light transmittance of the uncoated glass container for light wavelengths of about 400 nm to about 700 nm.

[0257] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, it is intended that the present specification cover modifications and variations of the various embodiments described herein only if the modifications and variations are within the scope of the appended claims and their equivalents. The following describes preferred embodiments of the present invention in separate sections.

[0258] EMBODIMENT 1 1. A coated glass pharmaceutical package comprising: USP <660> a glass body formed from either a borosilicate glass composition meeting the criteria for Type 1 in accordance with the ISO 720-1985 test, or an alkali aluminosilicate glass composition having Class HGA1 hydrolysis resistance when tested in accordance with ISO 720-1985 test, the glass body having an inner surface, an outer surface, and a wall extending therebetween; the smooth coating having a thickness of less than 100 microns disposed on at least a portion of the exterior surface; the portion of the exterior surface of the coated glass pharmaceutical package having the lubricious coating has a coefficient of friction that is at least 20% less than an uncoated glass pharmaceutical package formed from a similar glass composition; A coated glass pharmaceutical package, wherein the light transmittance through a portion of the outer surface of the coated glass pharmaceutical package is at least about 55% of the light transmittance through an uncoated glass pharmaceutical package at light wavelengths of about 400 nm to about 700 nm.

[0259] EMBODIMENT 2 the portion of the exterior surface of the coated glass medicine package having the lubricious coating has a coefficient of friction of 0.6 or less against a similar coated glass medicine package formed from a similar glass composition after a depyrogenation cycle; 2. The coated glass pharmaceutical package of embodiment 1, wherein the depyrogenation cycle comprises heating the coated glass pharmaceutical package to a temperature of at least 250° C. for at least 30 minutes in air, and wherein the coated glass pharmaceutical package is thermally stable after the depyrogenation cycle.

[0260] EMBODIMENT 3 3. The coated glass pharmaceutical package of embodiment 2, wherein the smooth coating is thermally stable at a temperature of at least 260° C. for 30 minutes.

[0261] EMBODIMENT 4 3. The coated glass pharmaceutical package of embodiment 2, wherein the depyrogenation cycle comprises heating the coated glass package to a temperature of about 250° C. to about 400° C. for at least 30 minutes.

[0262] EMBODIMENT 5 2. The coated glass pharmaceutical package of embodiment 1, wherein the coefficient of friction of the coated glass pharmaceutical package is 0.5 or less relative to a similar coated glass pharmaceutical package formed from a similar glass composition. EMBODIMENT 6 2. The coated glass pharmaceutical package of embodiment 1, wherein the glass body has an acid resistance of at least class S3 or higher according to DIN 12116.

[0263] EMBODIMENT 7 2. The coated glass pharmaceutical package of embodiment 1, wherein the lubricious coating is an inorganic coating.

[0264] EMBODIMENT 8 2. The coated glass pharmaceutical package of embodiment 1, wherein the lubricious coating is an organic coating.

[0265] EMBODIMENT 9 2. The coated glass pharmaceutical package of embodiment 1, wherein the lubricious coating comprises a polymeric chemical composition and a coupling agent, the coupling agent being in direct contact with the exterior surface, and the polymeric chemical composition being in direct contact with the coupling agent.

[0266] EMBODIMENT 10 2. The coated glass pharmaceutical package of embodiment 1, wherein the coefficient of friction of the lubricious coating does not increase by more than 30% after exposure to a lyophilization cycle consisting of filling the coated glass pharmaceutical package with a liquid containing a protein, freezing the coated glass pharmaceutical package at a temperature of -100°C, and then sublimating the water at -15°C in vacuum for 20 hours.

Claims

1. 1. A method of manufacturing a glass container for storing a pharmaceutical formulation, comprising the steps of: heating the borosilicate glass composition to form a glass melt; forming the glass melt into a glass tube; reforming the glass tube into a glass container comprising a glass body having a wall portion having an inner surface and an outer surface, a heel portion, and a floor portion; and applying a lubricating coating to the exterior surface such that the glass container having the lubricating coating has a coefficient of friction of 0.7 or less, wherein the lubricating coating is a robust organic coating, the coefficient of friction of the lubricating coating does not increase by more than 30% after exposure to a temperature of about 250° C. for 30 minutes, and the lubricating coating comprises a polymer selected from the group consisting of polyimides, polybenzimidazoles, polysulfones, polyetheretherketones, polyetherimides, polyamides, polyphenyls, polybenzothiazoles, polybenzoxazoles, polybisthiazoles, polyaromatic heterocyclic polymers, fluorinated polymers, silicone resins, and silsesquioxane-based polymers; The method includes:

2. 2. The method of claim 1, wherein the glass body has an interior region extending between the inner surface of the glass body and the outer surface of the glass body, and has continuous layer homogeneity such that an extreme (i.e., minimum or maximum) layer concentration of each of the components of the glass composition in the interior region is between about 80% and about 120% of the same component at a midpoint of the glass layer that includes the interior region.

3. 2. The method of claim 1, wherein the interior surface of the glass body has a continuous surface homogeneity such that, for each independent point on the interior surface of the glass container, the extreme (i.e., minimum or maximum) surface concentration of each of the components in a surface region at the independent point is between about 70% and about 130% of the same component in the surface region at any second independent point on the interior surface of the glass container in the as-formed state.

4. The method of claim 1 further comprising applying a barrier coating to the interior surface.

5. The glass body is Acid resistance of at least class S3 or higher according to DIN 12116, Base resistance of at least class A2 or higher according to ISO 695; Hydrolysis resistance of at least Type HGB2 or higher according to ISO 719; and Hydrolysis resistance of at least Type HGA2 or higher according to ISO 720; The method of claim 1 , comprising:

6. 2. The method of claim 1, wherein the glass body has a chemical durability of Type 1 according to USP <660>.

7. The method of claim 1 , wherein the glass body is formed from Type 1, Class B glass conforming to ASTM Standard E438-92.

8. 10. The method of claim 1, wherein the light transmittance of the glass container is greater than or equal to about 55% of the light transmittance of an uncoated glass article for wavelengths from about 400 nm to about 700 nm.

9. 10. The method of claim 1, wherein the robust organic coating has a mass loss of less than about 5% of its mass when heated from 150°C to 350°C at a heating rate of about 10°C / min.

Citation Information

Patent Citations

  • Process for producing low alkali glass containers

    WO2009116300A1